Biocontrol of Listeria monocytogenes and Salmonella Typhimurium in hydroponics: Evaluating the efficacy of plant growth promoting bioinoculants - Grace Akumu; Leslie D. Thompson; Mindy M. Brashears; Catherine R. Simpson; Christopher J. Currey; Angela M. Walla (Food Control, 2026)

Microbial analysis of Tsukinuno mine bentonite as a natural analogue for a nuclear waste repository - Rachel C. Beaver; Huan Tong; Lucas Beckering Vinckers Stofer; Nivetha Srikanthan; Erik Kremer; Greg F. Slater; Myrna J. Simpson; Josh D. Neufeld (Applied Clay Science, 2026)

Examining widely held propositions on human dietary protein needs and benefits: a critical review of the science that shapes both the data and our understanding of an essential macronutrient - Mitchell M. Kanter; Sally Aaron; Steven N. Austad; Andrew W. Brown; Nicholas A. Burd; Wayne W. Campbell; Mark Cope; Teresa A. Davis; John W. Erdman; Miguel Freitas; Kristen Hicks-Roof; Samuel Klein; et al. (Critical Reviews in Food Science and Nutrition, 2026)

Sources and dynamics of fecal pollution and antibiotic resistance across a Mediterranean land–sea continuum - Angela Freddi; Marco Basili; Antonella Penna; Silvia Casabianca; Ben J. Tscharke; Metasebia Gebrewold; Stuart L. Simpson; Elena Manini; Warish Ahmed (Journal of Environmental Management, 2026)

Early warning signs: Applications of in vivo NMR spectroscopy to understand the impacts of industrial effluents - Kiera Ronda; Sequoia Thompson; Peter M. Costa; William W. Wolff; Katelyn Downey; Owen Vander Meulen; Daniel H. Lysak; Jacob Pellizzari; Katrina Steiner; Daniel Lane; Carlos Cobas; Santiago Domínguez; et al. (Aquatic Toxicology, 2026)

Addressing Bias in Non‐Probability Fisheries Surveys Using Multilevel Regression and Poststratification Approaches - Zachary Radford; Wendy Edwards; Samantha Hook; Bridgid Bell; Rebecca Mills; Grace Farrell; Martin J. Genner; Stephen D. Simpson; Kieran Hyder (Fish and Fisheries, 2026)
Quantifying harvest of fish stocks is challenging as census data are often unavailable, so surveys are required. Traditional probability‐based surveys use random sampling to obtain representative data that can be scaled to estimate total impact. However, these surveys are costly, so cheaper, non‐probability, citizen science surveys of self‐selected participants are becoming commonplace. Respondents in these surveys may not be representative and inclusion probabilities are unknown, making weighting difficult. This resembles exit polls, which successfully predict election outcomes using Multi‐level Regression and Post‐stratification (MRP), but this has not been tested in fisheries. This study applied MRP to quantify UK recreational sea angling (RSA) participation and catches using data from the UK Sea Angling Diary Project. This represents a ‘worst‐case’ scenario, as there is no sampling frame and no mandatory reporting. Five Bayesian multi‐level models were fitted to two survey datasets: one quantifying participation and days fished, and another location, numbers, and weight of fish caught. Predictions were post‐stratified using UK census data. Estimates from the traditional reweighting and MRP were compared, and a simulation approach was used to assess the accuracy and precision of the two methods. MRP reduced self‐selection bias and improved estimates in under‐represented groups, producing a 40% and 61% improvement for participation and catch, respectively. Average annual UK RSA participation was estimated to be 688,000 anglers, with 6.1 million days fished. Annual catch estimates were 32.4 million fish, weighing 14,876 t. This study demonstrates the value of MRP for reducing bias when analysing and scaling non‐probabilistically collected survey data.

Effectiveness of ketamine-assisted psychotherapy as a treatment for treatment-resistant depression: a systematic review - Rebecca J. Simpson; Mario F. Juruena (Psychopharmacology, 2026)
Background Major Depressive Disorder (MDD) is a common and debilitating condition. Current treatments fail to provide adequate relief in roughly one-third of individuals, resulting in treatment-resistant depression (TRD). Ketamine has emerged as a promising intervention for TRD, offering rapid and sustained antidepressant effects. However, benefits often require maintenance dosing, and long-term outcomes remain unclear. This has promoted interest in adjunctive approaches such as ketamine-assisted psychotherapy (KAP), which combines ketamine with structured psychological support. Methods A comprehensive literature search was conducted via the OVID platform using Embase, Medline, Global Health, and APA PsycInfo. Keyword clusters related to “Ketamine,” “Diagnosis,” and “Psychotherapy” yielded 768 results. Screening followed PRISMA guidelines, resulting in 11 studies meeting inclusion criteria. Results The selected studies clustered into two thematic categories: structured, protocol-based interventions and individualized, experiential approaches. Across all studies, KAP was associated with reductions in depressive symptoms, with some improvements sustained up to six months. However, among the three studies with control groups, no significant differences were found between KAP and control conditions. Methodological heterogeneity—including variability in treatment protocols, outcome measures, and study designs—limits the ability to draw firm conclusions or identify mechanisms driving KAP’s effects. Conclusion KAP shows promise as a treatment for TRD, potentially offering meaningful and sustained symptom relief. However, limited evidence and methodological variability underscore the need for more rigorous research—particularly randomized controlled trials—to better understand its efficacy and mechanisms.

Likelihood-free parameter inference for spatiotemporal stochastic biological models using neural posterior estimation - Tom Kimpson; Jennifer Flegg; Matthew J. Simpson (Journal of Theoretical Biology, 2026)

Multigenerational exposure to per- and polyfluoroalkyl substances (PFAS) negatively impacts the reproductive health of male mice - Leah Gillespie; Jacinta H. Martin; Amanda L. Anderson; Natalie A. Trigg; John E. Schjenken; Shannon P. Smyth; Ilana R. Bernstein; Simone J. Stanger; Logan McElhone; Colin C. Conine; Fay Waldrip; Erin J. Campbell; et al. (Environmental Research, 2026)

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Design principles of cells for eatability and scalability of cultivated meat - Corinne S. Smith; Lucas Krusinski; Ceci A. Cohen; N. Stephanie Kawecki; Lauren Moccio; Qingwen Xie; Emily Cheng; Zoe Yee; Sydney Adler; Dorian Simpson; George Marcotte; Robert Damoiseaux; et al. (Trends in Food Science & Technology, 2026)

Early Devonian (Lochkovian–Pragian) linguliform brachiopods from the Cobar Supergroup, western New South Wales, Australia - James L. Valentine; David K. Mathieson; Andrew J. Simpson (Palaeoworld, 2026)

Three decades of continuous warming in temperate forests destabilizes persistent forms of soil organic matter - Atzín X. San Román; Serita D. Frey; Melissa A. Knorr; Huan Tong; Jerry M. Melillo; Myrna J. Simpson (Science of The Total Environment, 2026)

Assessing the potential impact of environmental land management schemes on emergent infectious disease risks - Christopher J. Banks; Katherine Simpson; Nick Hanley; Rowland R. Kao (Journal of Environmental Management, 2026)

N-Acetylcysteine Dose and Treatment Duration in High-Risk Acetaminophen Ingestions Treated Within Eight Hours: A Retrospective Cohort Study - C. James Watson; Michael D. Simpson; Nishita Saraiya; Christopher A. Wilkosz; Michael B. Yu; Michele M. Burns; Mark J. Neavyn; Karen E. Simone; Tania D. Strout (Journal of Medical Toxicology, 2026)
Introduction Toxicologists may use high dose n-acetylcysteine (HD-NAC) for early-treated high-risk acetaminophen ingestions (EHRAI) given concerns over standard NAC (S-NAC) dosing’s efficacy. We utilize the novel, clinically relevant outcome of mean additional 16-hour NAC maintenance infusions (NMI) to evaluate differences in treatment duration for EHRAI patients treated with S-NAC versus HD-NAC. Methods Retrospective multistate poison center study from 1/1/2019-7/4/2024 of patients ≥ 13-years-old who were treated with S-NAC or HD-NAC within eight hours of a high-risk acetaminophen ingestion. The primary outcome was mean additional NMI. Secondary outcomes were NAC infusion duration, hepatotoxicity, coagulopathy, transplant, and death. Sensitivity analyses evaluated for robustness of findings. Results Of 127 included cases, 52.0% (66/127) received HD-NAC. 7.1% (9/127) had anti-peristaltic co-ingestions. HD-NAC cases received more fomepizole (23.1% versus 1.6%; difference 21.1%). Acetaminophen concentrations controlled for time since ingestion were similar (mean acetaminophen ratio for HD-NAC: 2.7, IQR: 2.3, 3.3 versus S-NAC: 2.4, IQR: 2.2, 2.7; difference − 0.3). 26.0% (33/127) received NMI solely for residual detectable serum acetaminophen. There was no difference in mean additional NMI (HD-NAC: 0.53 versus S-NAC: 0.38; p = 0.240). Median NAC infusion durations were equal across groups (21.0; IQR: 21.0, 37.0; difference 0.0) ( p = 0.137). One patient per group developed hepatotoxicity; there were no transplants or deaths. Sensitivity analyses yielded similar results. Conclusions We found no difference in mean NMI for EHRAI based on NAC dose. These findings support additional NMI as an objective, common, clinically relevant outcome for acetaminophen toxicity research.

Parameter-wise predictions and sensitivity analysis for random walk models in the life sciences - Yihan Liu; David J. Warne; Matthew J. Simpson (Journal of Theoretical Biology, 2026)

Long-term biomass removal in grasslands reduces plant and soil phosphorus, increases carbon:phosphorus stoichiometry, but does not lead to microbial phosphorus limitation - Andrea Simpson; David Whitehead; Leo M. Condron; Kate H. Orwin; Keith C. Cameron; Niklas J. Lehto (Agriculture, Ecosystems & Environment, 2026)

In-season effects of winter cover crops and tillage on soil NO3- and N leaching – Analysis with generalized additive models - Jorge Federico Miranda-Vélez; Gavin L. Simpson; Elly Møller Hansen; Lars J. Munkholm (Agriculture, Ecosystems & Environment, 2026)

Boat noise alters behaviour of two coral reef macroinvertebrates, Lambis lambis and Tridacna maxima - M.N. Havlik; N.R. Geraldi; L.W. Hopkins; J. Hubert; L. Chapuis; L.P. Gaffney; R.P. Wilson; S.D. Simpson; F.J. Juanes; C.M. Duarte (Marine Pollution Bulletin, 2026)

Assessing behavioural economic demand for morphine after an acute dose in individuals with- and without childhood trauma: a double-blind, randomised, controlled trial - Martin Trøstheim; Benjamin L. Berey; Elizabeth R. Aston; Matthew J. Gullo; Lee Hogarth; Graham Simpson; Rupert Broomby; Celia J. Morgan; Molly Carlyle (Psychopharmacology, 2025)
Background Childhood trauma is associated with positive subjective responses to acute opioids in the laboratory. Yet, its impact on behavioural economic demand for opioids remains unclear. Because demand can predict future use and misuse, we investigated whether individuals with childhood trauma also display greater demand for opioids in the laboratory. Methods This secondary analysis used data from a double-blind, randomised, controlled, counterbalanced trial. Across two sessions, individuals with ( n = 26) and without ( n = 21) childhood trauma received a high (0.15 mg/kg) and low (0.01 mg/kg) dose of intramuscular morphine 120 min before a hypothetical purchase task. Participants also regularly reported their subjective desire for the study drug. Area under the consumption and expenditure curves, and specific demand indices ( O max , P max , breakpoint , intensity , elasticity ), were analysed with non-parametric mixed models. Results Consumption and expenditure for low dose morphine was lower in the childhood trauma group when compared to high dose morphine in this group, and low dose morphine in the control group ( p s ≤ 0.03). Consistent results were obtained for specific demand indices O max , P max , and breakpoint , but not intensity or elasticity . Positive correlations between subjective desire and consumption and expenditure were only observed in the childhood trauma group ( Tau-c = 0.24–0.34, p s ≤ 0.03). Conclusion Under laboratory conditions, desires to use opioids among individuals with childhood traumas may not manifest in strong intentions to acquire these drugs. Diverging results from psychometric measures of subjective and economic opioid value highlight the need for future research to explore contextual and resilience factors to understand how problematic opioid use emerges after childhood traumas.

A phylogenetic perspective on the performance of Lactococcus lactis as starter culture in milk and plant milks - Zheng Zhao; Yuxin Zhang; David J. Simpson; Michael G. Gänzle (Food Research International, 2025)

Origin and HFSE enrichment potential of a Late Cretaceous basalt to peralkaline rhyolite suite in central Queensland, Australia - D. Purdy; B. Simpson; N. Kositcin; J. Fitzherbert; H. Dalton (Australian Journal of Earth Sciences, 2025)

A solution from the past: exploring the untapped potential of museum specimens to preserve secondary metabolites - Sam Afoullouss; Jennifer Netjes; Matthew Simpson; Micah Harris; Laurent Calcul; Dale Chaput; William Keel; Bill J. Baker (Phytochemistry Letters, 2025)

Calcite priming of a hydrothermal eruption at South Orakonui, Ngā Tamariki Geothermal Field, New Zealand - Mark P. Simpson; Michael D. Rosenberg; Cristian Montanaro; Duncan J. Graham (Journal of Volcanology and Geothermal Research, 2025)

Calibration of WinSLAMM to stormwater volume and pollutant mass flux data in Ohio, USA: Informing pollutant loads in untreated stormwater from various urban land uses - Ian M. Simpson; Ryan J. Winston; Jay D. Dorsey (Journal of Hydrology, 2025)

Optimizing bromoform content in Gracilaria parvispora: the role of environmental stressors - Steven R. Cunningham; Luke Gardner; Maxime M. Grand; Jessica Metter; Ava Salmi; Evan Simpson; Michael Graham; Scott L. Hamilton; Michael R. Schuppenhauer; Daniel J. Gossard (Journal of Applied Phycology, 2025)

Surface-based morphometry reveals divergent aging trajectories in veterans with and without traumatic brain injury - Michelle C. Eliason; Amrutha Bindu Nagella; Cristian Cuadra; David S. Wack; Ghazala T. Saleem; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowki; Arthur W. Toga; et al. (GeroScience, 2025)

Combining analysis of individual and wastewater whole genome sequencing improves SARS-CoV-2 surveillance - Evan P. Troendle; Andrew J. Lee; Marina I. Reyne; Danielle M. Allen; Stephen J. Bridgett; Clara H. Radulescu; Michael Glenn; John-Paul Wilkins; Francesco Rubino; Behnam Firoozi Nejad; Cormac McSparron; Marc Niebel; et al. (Water Research, 2025)

Microfluidics enables rapid and facile fabrication of multi-component antimicrobial nanoparticles - Shaveen S.B. Gamage; Tao Huang; Neil O'Brien-Simpson; Daniel E. Heath; Andrea J. O'Connor (Chemical Engineering Journal, 2025)

Laboratory evaluation of potential climate change impacts on the larval metamorphosis of Pacific lamprey (Entosphenus tridentatus) - William G. Simpson; Timothy J. Blubaugh; Timothy A. Whitesel (Environmental Biology of Fishes, 2025)
Organisms that undergo metamorphosis can be particularly vulnerable to environmental changes. However, if these transitions are ignored as an explicit life stage in evaluations and models, such threats can be overlooked. In lamprey, larvae that achieve enough energy storage appear to metamorphose when exposed to cold winter water temperatures followed by a rise in spring temperature. Winters of the Pacific Northwest (USA) are experiencing climatic warming that may alter the conditions necessary for larval metamorphosis. Therefore, we conducted a laboratory study that compared the incidence of metamorphosis between larval Pacific lamprey ( Entosphenus tridentatus ) reared at natural winter river temperatures and those reared at water temperatures prevented from falling below 9 °C over 2 years. Repeating this experiment with two cohorts of larval lamprey resulted in no difference in the incidence of metamorphosis between temperature treatments in either rearing year. The group growth rate of cohort 1 larvae in the first year of laboratory rearing was greater than growth rates reported for stream-reared larvae, and more of these larvae metamorphosed in their first year compared to cohort 2. However, the incidence of metamorphosis was similar (about 78%) between both larval cohorts over 2 years, despite experiencing differences in collection years, temperature regimes, body sizes, and initial metamorphosis. We found no evidence that warming winter stream temperatures driven by climate change would limit Pacific lamprey metamorphosis the following summer. Subsequent work exploring whether individual growth and water temperature interact to influence near-term metamorphosis may allow managers to apply these results to other lamprey populations.

New Approach Needed To Address Declining Forestry Research Capacity And Relevancy in the US: A Call-To-Action - Robert G. Wagner; Alexander L. Friend; Emily J. Silver; Julio Rojas; Thomas R. Fox; Terry Baker; Robert Simpson (Journal of Forestry, 2025)
Recent dramatic reductions in research funding and personnel for university and government organizations by the new federal administration will reduce forestry research capacity in the coming years. However, these cuts only highlight the long-standing decline in forestry research capacity that has been occurring over the past several decades. These reductions will continue to impair the country’s ability to meet the scale and complexity of challenges facing US forests. At some point in the future, there will be an opportunity to rebuild and reshape forestry research capacity to address these challenges. Now is the time to plan the future of forestry research. Successfully rebuilding this capacity will require national support from a broad coalition of forest management organizations. Receiving this support will require substantially increasing the relevancy of research to forest managers relative to what has occurred in recent decades. We offer several suggestions for this rebuilding effort, including: 1) developing a periodic national survey of forest managers to clearly identify the most important problems they face on the ground, 2) regularly communicating results of the survey to forest researchers, program leaders of research funding agencies, policy makers, legislators, and others responsible for allocating forest research effort and funding, and 3) building on the science delivery successes of stakeholder-driven organizations such as the forest manager / university research cooperatives around the country.

Data-informed model reduction for inference and prediction from non-identifiable models - Matthew J. Simpson (Journal of Theoretical Biology, 2025)

Forest terpenes and stress: Examining the associations of filtered vs. non-filtered air in a real-life natural environment - Chaja M. Levy; Anne M. Riederer; Christopher D. Simpson; Amanda J. Gassett; Abigail J. Gilbert; Michael H. Paulsen; Lalith K. Silva; Deepak Bhandari; Cody A. Newman; Benjamin C. Blount; Peter H. Kahn; Gregory N. Bratman (Environmental Research, 2025)

Individual variability in lactate response to cycling prescribed using physiological thresholds and peak work rate: a crossover within-participant repeated measures study - Lauren J. Pacitti; Kaitlyn E. Shikaze; Nia Simpson-Stairs; Jonathan Stringer; Brendon J. Gurd (European Journal of Applied Physiology, 2025)

Investigation regarding the physiological effects of cobalt on physiological functions in Drosophila, crayfish, and crab: Behavioral, cardiac, neural, and synaptic properties - Jaycie E. Gard; Kaitlyn E. Brock; Elizabeth R. Elliott; Alaina C. Taul; Jeremy Nadolski; Jiwoo Kim; Shelby McCubbin; Jordon Hecht; Remy Ronen; Sonya M. Bierbower; Jayden P. Alcorn; Nikitha Dharanipragada; et al. (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Innovation in apatite Lu-Hf geochronology opens new opportunity for copper systems in southern Australia during the Nuna destruction - Jie Yu; Martin Hand; Justin L. Payne; Laura J. Morrissey; Alexander Simpson; Stijn Glorie; Yan-Jing Chen (Mineralium Deposita, 2025)
Precambrian iron oxide copper-gold (IOCG) systems have commonly experienced multiple mineralising and tectonothermal events and identifying their timing and geodynamic framework is challenging. World-class IOCG deposits in the Olympic Cu-Au Province, South Australia, are dominated by hematite and formed in the upper crust, while the magnetite-dominated Cu deposits hosted in granulite facies rocks are considered to represent the deeper expression of giant IOCG system. However, the application of novel in-situ Lu-Hf apatite geochronology reveals the magnetite-hosted Cu mineralisation is significantly younger and unrelated to the well-known ~ 1590 Ma Gawler Craton IOCG systems. Apatite Lu-Hf ages from the granulite that predates Cu mineralisation give ages of 1490 Ma. Infiltration of Cu-bearing fluids resulted in recrystallisation of apatite, LREE mobilisation and formation of secondary monazite. Lu-Hf ages for syn-mineralisation apatite give 1460 Ma, consistent with c. 1460 Ma U-Pb ages from secondary monazite. In contrast to the apatite in situ Lu-Hf ages, all apatite types produce a single U-Pb age of c. 1460 Ma, demonstrating the ability of Lu-Hf to preserve a more complete history of apatite formation than U-Pb in high- to medium-temperature rock systems. The timing of mineralisation coincides with the onset of Nuna fragmentation, representing a previously unrecognised driver for mineral system formation in southern Australia that installed Cu in crust previously dehydrated during a long history of granulite-grade tectonic events. The recognition of this Cu system in rocks generally considered unprospective shows that continental breakup can rejuvenate metallic systems in otherwise unprospective crust.

Physiological response of milkfish ( Chanos chanos ) to capture in a fly fishing catch‐and‐release recreational fishery - Andy J. Danylchuk; Lucas P. Griffin; Michael Lawrence; Sascha Clark Danylchuk; Eleanor Brighton; Gail Fordham; George Curd; Kyle Simpson; Devan Vd Merwe; Steven J. Cooke (Fisheries Management and Ecology, 2025)
Recreational angling for novel marine species and related tourism development can be important in a Blue Economy. The milkfish ( Chanos chanos ) is growing in popularity as a target of fly fishing‐based catch‐and‐release (C&R) recreational fisheries, largely because of their challenge to catch and powerful swimming abilities, resulting in fight times that can exceed 1 h. Anecdotal sentiments by anglers claim that milkfish can fight for long periods of time because they do not accumulate blood lactate. To test this hypothesis, we measured blood lactate and blood glucose for 21 milkfish caught by fly fishing in the remote Alphonse Group of islands, Republic of Seychelles. Fight times ranged 5–78.3 min. Blood lactate and blood glucose concentrations increased with fight times that did not exceed 60 min. Total length of milkfish was not correlated to blood lactate or blood glucose concentrations. Ours is the first study on C&R of milkfish that debunks the anecdote that milkfish can fight for long periods of time because they do not accumulate blood lactate. Our study also revealed that milkfish may begin to physiologically recover after fight times longer than 60 min. In the context of C&R, our study indicates that anglers should limit fight times to 20–30 min when possible to reduce angling‐induced physiological stress and other potential impacts (e.g., depredation) on milkfish in recreational fisheries.

Saprotrophic Capabilities of Neurospora crassa on Charred Plant Biomass - Hunter J. Simpson; Jonathan S. Schilling (Environmental Microbiology, 2025)
Neurospora crassa is a popular model organism for laboratory research, yet its natural ecology remains mysterious. Its proliferation on charred plant biomass (wood and grasses) in fire‐affected environments is often linked to the heat tolerance or heat−/chemical‐induced germination of N. crassa spores; however, this link is not consistent across ecosystems or substrate types. Another possible, yet unvalidated, explanation is that N. crassa has an enhanced capacity for degrading charred (i.e., pyrolyzed) plant biomass. We assessed this adaptation for N. crassa by quantifying the decay of wood and grasses that were pyrolyzed to relevant extents (untreated, heated at 225°C or 350°C for 20 min) and by comparing this decay with non‐fire‐associated fungi. Neurospora crassa did not have an enhanced ability to degrade pyrolyzed substrates. Additionally, N. crassa struggled to degrade any wood substrate ( 20% mass loss). These results, paired with chemical analyses of substrates pre‐ and post‐decay, support a fire‐response strategy for N. crassa , rather than a fire‐adaptive ability to degrade charred substrates. This fungus likely proliferates on charred biomass by rapidly colonising heat‐sterilised substrates after heat‐ or smoke‐induced spore germination and then consuming unpyrolyzed lignocellulose beneath a charred exterior.

Metabolomics identified distinct molecular-level responses in Daphnia magna after exposure to phenanthrene and its oxygen and nitrogen containing analogs - Salwa Hajir; Karl J. Jobst; Sonya Kleywegt; André J. Simpson; Myrna J. Simpson (Chemosphere, 2025)

Long chain n-alkanes in lake sediment track differences in adjacent land vegetation. - Bowen Xiao; Dënë Cheecham-Uhrich; David C. Eickmeyer; Linda E. Kimpe; Vilmantas Prėskienis; E. Henriikka Kivilä; Meiling Man; Myrna J. Simpson; Irena Creed; Milla Rautio; Jules M. Blais (Organic Geochemistry, 2025)

A generalised sigmoid population growth model with energy dependence: Application to quantify the tipping point for Antarctic shallow seabed algae - Elise Mills; Graeme F. Clark; Matthew J. Simpson; Mark Baird; Matthew P. Adams (Environmental Modelling & Software, 2025)

Voxel-wise insights into early Alzheimer’s disease pathology progression: the association with APOE and memory decline - Maha Wybitul; Nicolas Langer; Christoph Hock; Anton Gietl; Valerie Treyer; Michael Weiner; Paul Aisen; Ronald-Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; et al. (GeroScience, 2025)
Longitudinal investigation of the Apolipoprotein E (APOE) genotype’s impact on Alzheimer’s disease (AD) biomarker progression, focusing on amyloid beta (Aβ) accumulation and gray matter (GM) atrophy, integrating cognitive decline and baseline levels. Longitudinal florbetapir-PET and T1-weighted MRI data from 100 cognitively normal (CN) and mild cognitive impaired (MCI) participants both with considerable global Aβ accumulation (“high Aβ accumulators”) were analyzed using a voxel-wise approach. Associations of APOE genotype and memory decline with Aβ accumulation and GM atrophy were examined separately for each neuroimaging modality, controlling for baseline Aβ levels and diagnosis. Alternatively, the effect of baseline diagnosis, while controlling for memory decline, was investigated. A multimodal analysis evaluated interactions between genotype, memory decline, and GM atrophy on Aβ accumulation. High Aβ accumulators displayed extensive Aβ pathology predominantly in the medial orbito-frontal cortex, cingulate cortex, and precuneus, along with GM atrophy in temporal, occipital, orbito-frontal, and parietal areas. ɛ4 carriers with memory decline exhibited greater Aβ accumulation and GM atrophy in selective regions compared to non-carriers with memory decline, while no genotype difference was observed in individuals without decline. No interaction effect was observed for MCI diagnosis. Regional associations between the two biomarkers were similarly dependent on genotype and memory decline. ɛ4 carriers exhibiting memory decline present an accelerated neurobiological pattern at predementia stages, supporting early ɛ4 carrier monitoring and interventions in this at-risk group. Importantly, memory decline might be more informative than MCI regarding AD pathology progression emphasizing the importance of repeated cognitive assessments.

Dissolved organic matter molecular composition controls potential biodegradability - Meiling Man; Myrna J. Simpson (Organic Geochemistry, 2025)

Environmental and dietary factors associated with urinary OH-PAHs in mid-pregnancy in a large multi-site study - Anne M. Riederer; Allison R. Sherris; Adam A. Szpiro; Melissa M. Melough; Christopher D. Simpson; Christine T. Loftus; Drew B. Day; Erin R. Wallace; Leonardo Trasande; Emily S. Barrett; Ruby HN. Nguyen; Kurunthachalam Kannan; et al. (Environmental Research, 2025)

Strain-level identification of bacteria persisting in food and in food processing facilities: when do two isolates represent the same strain and which tools identify a strain? - Vi D Pham; David J Simpson; Michael G Gänzle (Current Opinion in Food Science, 2025)

Vertebrates in trade that pose high invasion risk to the United States - Wesley M. Daniel; Helen R. Sofaer; Catherine S. Jarnevich; Richard A. Erickson; Brett A. DeGregorio; Peder S. Engelstad; Jonathan Freedman; Susan Canavan; E.M. Dean; Michael J. Adams; Charmayne L. Anderson; Mindy Barnett; et al. (Biological Conservation, 2025)

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

Effects of macro vs. micro initialization and ocean initial-condition memory on the evolution of ensemble spread in the CESM2 large ensemble - Clara Deser; Who M. Kim; Robert C. J. Wills; Isla R. Simpson; Steve Yeager; Gokhan Danabasoglu; Keith Rodgers; Nan Rosenbloom (Climate Dynamics, 2025)
“Single Model initial-condition Large Ensembles” (SMILEs) conducted with Earth system models have transformed our ability to quantify internal climate variability and forced climate change at local and regional scales. An important consideration in their experimental design is the choice of initialization procedure as this influences the duration of initial-condition memory, with implications for interpreting the temporal evolution of both the ensemble-mean and ensemble-spread. Here we leverage the strategic design of the 100-member Community Earth System Model version 2 (CESM2) SMILE to investigate the dependence of ensemble spread on the method of initialization (micro- vs. macro- perturbations) and the effects of ocean initial-condition memory. We find that the evolution of ensemble spread in 10-year low-pass filtered data is relatively insensitive to the method of initialization beyond the second decade, with the notable exception of the tropical Indo-Pacific in the 4th decade, when macro-initialization significantly enhances ensemble spread, possibly as a result of a state-dependent response to major volcanic activity. Initial-condition memory associated with the chosen Atlantic Meridional Overturning Circulation (AMOC) states unfolds in two stages: First, in the North Atlantic lasting 4–5 decades, and subsequently, in the Indo-Pacific sector of the Southern Ocean appearing 35-years after initialization and lasting 3–4 decades. Known AMOC dynamics explain the first stage, but the role of AMOC and the mechanisms responsible for the delayed appearance of initial-condition memory in the Southern Ocean remain to be fully elucidated. Implications and recommendations for the design of future SMILEs are provided.

An evaluation of the seasonal Caribbean hydroclimate in low and high-resolution CESM and other CMIP6 models - Carlos J. Martinez; Isla R. Simpson; John T. Fasullo; Andreas F. Prein (Climate Dynamics, 2025)

Eating disorder risk among Australian youth starting a diet in the community - Melissa J. Pehlivan; Mirei Okada; Jane Miskovic-Wheatley; Sarah Barakat; Stephen Touyz; Stephen J. Simpson; Kristi Griffiths; Andrew Holmes; Sarah Maguire (Appetite, 2024)

Germline copy number variants and endometrial cancer risk - Cassie E. Stylianou; George A. R. Wiggins; Vanessa L. Lau; Joe Dennis; Andrew N. Shelling; Michelle Wilson; Peter Sykes; Frederic Amant; Daniela Annibali; Wout De Wispelaere; Douglas F. Easton; Peter A. Fasching; et al. (Human Genetics, 2024)
Known risk loci for endometrial cancer explain approximately one third of familial endometrial cancer. However, the association of germline copy number variants (CNVs) with endometrial cancer risk remains relatively unknown. We conducted a genome-wide analysis of rare CNVs overlapping gene regions in 4115 endometrial cancer cases and 17,818 controls to identify functionally relevant variants associated with disease. We identified a 1.22-fold greater number of CNVs in DNA samples from cases compared to DNA samples from controls ( p = 4.4 × 10 –63 ). Under three models of putative CNV impact (deletion, duplication, and loss of function), genome-wide association studies identified 141 candidate gene loci associated ( p < 0.01) with endometrial cancer risk. Pathway analysis of the candidate loci revealed an enrichment of genes involved in the 16p11.2 proximal deletion syndrome, driven by a large recurrent deletion (chr16:29,595,483-30,159,693) identified in 0.15% of endometrial cancer cases and 0.02% of control participants. Together, these data provide evidence that rare copy number variants have a role in endometrial cancer susceptibility and that the proximal 16p11.2 BP4-BP5 region contains 25 candidate risk gene(s) that warrant further analysis to better understand their role in human disease.

Reporting population size in wastewater-based epidemiology: A scoping review - Mackay Price; Bradley S. Simpson; Benjamin J. Tscharke; Fahad Ahmed; Emma L. Keller; Hannah Sussex; Melanie Kah; Katarzyna Sila-Nowicka; Andrew Chappell; Cobus Gerber; Sam Trowsdale (Science of The Total Environment, 2024)

Ice-marginal volcanic sequence in Iceland found on a nondescript gradual hillslope: An unexpected record of ice thickness late in deglaciation - Audrey R. Putnam; Kirsten L. Siebach; Candice C. Bedford; Sarah L. Simpson; Michael T. Thorpe; Joseph J. Tamborski; Elizabeth B. Rampe (Journal of Volcanology and Geothermal Research, 2024)

Measuring the Response Diversity of Ecological Communities Experiencing Multifarious Environmental Change - Francesco Polazzo; Romana Limberger; Frank Pennekamp; Samuel R. P.‐J. Ross; Gavin L. Simpson; Owen L. Petchey (Global Change Biology, 2024)
The diversity in organismal responses to environmental changes (i.e., response diversity) plays a crucial role in shaping community and ecosystem stability. However, existing measures of response diversity only consider a single environmental variable, whereas natural communities are commonly exposed to changes in multiple environmental variables simultaneously. Thus far, no approach exists to integrate multifarious environmental change and the measurement of response diversity. Here, we show how to consider and quantify response diversity in the context of multifarious environmental change, and in doing so introduce a distinction between response diversity to a defined or anticipated environmental change, and the response capacity to any possible set of (defined or undefined) future environmental changes. First, we describe and illustrate the concepts with empirical data. We reveal the role of the trajectory of environmental change in shaping response diversity when multiple environmental variables fluctuate over time. We show that, when the trajectory of the environmental change is undefined (i.e., there is no information or a priori expectation about how an environmental condition will change in future), we can quantify the response capacity of a community to any possible environmental change scenario. That is, we can estimate the capacity of a system to respond under a range of realistic or extreme environmental changes, with utility for predicting future responses to even multifarious environmental change. Finally, we investigate determinants of response diversity within a multifarious environmental change context. We identify factors such as the diversity of species responses to each environmental variable, the relative influence of different environmental variables and temporal means of environmental variable values as important determinants of response diversity. In doing so, we take an important step towards measuring and understanding the insurance capacity of ecological communities exposed to multifarious environmental change.

Complementary value of molecular, phenotypic, and functional aging biomarkers in dementia prediction - Andreas Engvig; Karl Trygve Kalleberg; Lars T. Westlye; Esten Høyland Leonardsen; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; et al. (GeroScience, 2024)
DNA methylation age (MA), brain age (BA), and frailty index (FI) are putative aging biomarkers linked to dementia risk. We investigated their relationship and combined potential for prediction of cognitive impairment and future dementia risk using the ADNI database. Of several MA algorithms, DunedinPACE and GrimAge2, associated with memory, were combined in a composite MA alongside BA and a data-driven FI in predictive analyses. Pairwise correlations between age- and sex-adjusted measures for MA (aMA), aBA, and aFI were low. FI outperformed BA and MA in all diagnostic tasks. A model including age, sex, and aFI achieved an area under the curve (AUC) of 0.94 for differentiating cognitively normal controls (CN) from dementia patients in a held-out test set. When combined with clinical biomarkers (apolipoprotein E ε4 allele count, memory, executive function), a model including aBA and aFI predicted 5-year dementia risk among MCI patients with an out-of-sample AUC of 0.88. In the prognostic model, BA and FI offered complementary value (both β s 0.50). The tested MAs did not improve predictions. Results were consistent across FI algorithms, with data-driven health deficit selection yielding the best performance. FI had a stronger adverse effect on prognosis in males, while BA’s impact was greater in females. Our findings highlight the complementary value of BA and FI in dementia prediction. The results support a multidimensional view of dementia, including an intertwined relationship between the biomarkers, sex, and prognosis. The tested MA’s limited contribution suggests caution in their use for individual risk assessment of dementia.

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

The repeatability of a cycling exercise-heat stress test in a male population - Jake Shaw; E. Cole; Andrew J. Simpson; Christopher J. Tyler; Andrew T. Garrett (Journal of Thermal Biology, 2024)

Response of Root Respiration to Warming and Nitrogen Addition Depends on Tree Species - T. J. Muratore; M. A. Knorr; M. J. Simpson; R. B. Stephens; R. P. Phillips; S. D. Frey (Global Change Biology, 2024)
Roots contribute a large fraction of CO 2 efflux from soils, yet the extent to which global change factors affect root‐derived fluxes is poorly understood. We investigated how red maple ( Acer rubrum ) and red oak ( Quercus rubra ) root biomass and respiration respond to long‐term (15 years) soil warming, nitrogen addition, or their combination in a temperate forest. We found that ecosystem root respiration was decreased by 40% under both single‐factor treatments (nitrogen addition or warming) but not under their combination (heated × nitrogen). This response was driven by the reduction of mass‐specific root respiration under warming and a reduction in maple root biomass in both single‐factor treatments. Mass‐specific root respiration rates for both species acclimated to soil warming, resulting in a 43% reduction, but were not affected by N addition or the combined heated × N treatment. Notably, the addition of nitrogen to warmed soils alleviated thermal acclimation and returned mass‐specific respiration rates to control levels. Oak roots contributed disproportionately to ecosystem root respiration despite the decrease in respiration rates as their biomass was maintained or enhanced under warming and nitrogen addition. In contrast, maple root respiration rates were consistently higher than oak, and this difference became critical in the heated × nitrogen treatment, where maple root biomass increased, contributing significantly more CO 2 relative to single‐factor treatments. Our findings highlight the importance of accounting for the root component of respiration when assessing soil carbon loss in response to global change and demonstrate that combining warming and N addition produces effects that cannot be predicted by studying these factors in isolation.

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

Unraveling the effects of acrylonitrile butadiene styrene (ABS) microplastic ageing on the sorption and toxicity of ionic liquids with 2,4-D and glyphosate herbicides - Natalia Lisiecka; Anna Parus; Maria Simpson; Arkadiusz Kloziński; Joanna Zembrzuska; Robert Frankowski; Agnieszka Zgoła-Grześkowiak; Marta Woźniak-Karczewska; Katarzyna Siwińska-Ciesielczyk; Michał Niemczak; Mariusz Sandomierski; Christian Eberlein; et al. (Chemosphere, 2024)

Aridity affects soil organic carbon concentration and chemical stability by different forest types and soil processes across Chinese natural forests - Shan Xu; Yuanxi Yang; Guodong Sun; Qiang Zhang; Yinghui Wang; Hui Zeng; Myrna J. Simpson; Junjian Wang (Science of The Total Environment, 2024)

Characterization of natural organic matter in Wyoming-type bentonites irradiated at varied moisture levels - C.M. James Neurauter; Nivetha Srikanthan; Huan Tong; Mehran Behazin; Myrna J. Simpson (Applied Geochemistry, 2024)

Recent and near‐term future changes in impacts‐relevant seasonal hydroclimate in the world's Mediterranean climate regions - Richard Seager; Yutian Wu; Annalisa Cherchi; Isla R. Simpson; Timothy J. Osborn; Yochanan Kushnir; Jelena Lukovic; Haibo Liu; Jennifer Nakamura (International Journal of Climatology, 2024)
Change over recent decades in the world's five Mediterranean Climate Regions (MCRs) of quantities of relevance to water resources, ecosystems and fire are examined for all seasons and placed in the context of changes in large‐scale circulation. Near‐term future projections are also presented. It is concluded that, based upon agreement between observational data sets and modelling frameworks, there is strong evidence of radiatively‐driven drying of the Chilean MCR in all seasons and southwest Australia in winter. Observed drying trends in California in fall, southwest southern Africa in fall, the Pacific Northwest in summer and the Mediterranean in summer agree with radiatively‐forced models but are not reproduced in a model that also includes historical sea surface temperature (SST) forcing, raising doubt about the human‐origin of these trends. Observed drying in the Mediterranean in winter is stronger than can be accounted for by radiative forcing alone and is also outside the range of the SST‐forced ensemble. It is shown that near surface vapour pressure deficit (VPD) is increasing almost everywhere but that, surprisingly, this is contributed to in the Southern Hemisphere subtropics to mid‐latitudes by a decline in low‐level specific humidity. The Southern Hemisphere drying, in terms of precipitation and specific humidity, is related to a poleward shift and strengthening of the westerlies with eddy‐driven subsidence on the equatorward side. Model projections indicate continued drying of Southern Hemisphere MCRs in winter and spring, despite ozone recovery and year‐round drying in the Mediterranean. Projections for the North American MCR are uncertain, with a large contribution from internal variability, with the exception of drying in the Pacific Northwest in summer. Overall the results indicate continued aridification of MCRs other than in North America with important implications for water resources, agriculture and ecosystems.

Drivers of population dynamics of at-risk populations change with pathogen arrival - Alexander T. Grimaudo; Joseph R. Hoyt; R. Andrew King; Rickard S. Toomey; Chris Simpson; Cory Holliday; Alexander Silvis; Rick T. Doyle; Joseph A. Kath; Mike P. Armstrong; Virgil Brack; Richard J. Reynolds; et al. (Biological Conservation, 2024)

Association of physical function with connectivity in the sensorimotor and dorsal attention networks: why examining specific components of physical function matters - Madeline C. Boyd; Jonathan H. Burdette; Michael E. Miller; Robert G. Lyday; Christina E. Hugenschmidt; W. Jack Rejeski; Sean L. Simpson; Laura D. Baker; Chal E. Tomlinson; Stephen B. Kritchevsky; Paul J. Laurienti (GeroScience, 2024)
Declining physical function with aging is associated with structural and functional brain network organization. Gaining a greater understanding of network associations may be useful for targeting interventions that are designed to slow or prevent such decline. Our previous work demonstrated that the Short Physical Performance Battery (eSPPB) score and body mass index (BMI) exhibited a statistical interaction in their associations with connectivity in the sensorimotor cortex (SMN) and the dorsal attention network (DAN). The current study examined if components of the eSPPB have unique associations with these brain networks. Functional magnetic resonance imaging was performed on 192 participants in the BNET study, a longitudinal and observational trial of community-dwelling adults aged 70 or older. Functional brain networks were generated for resting state and during a motor imagery task. Regression analyses were performed between eSPPB component scores (gait speed, complex gait speed, static balance, and lower extremity strength) and BMI with SMN and DAN connectivity. Gait speed, complex gait speed, and lower extremity strength significantly interacted with BMI in their association with SMN at rest. Gait speed and complex gait speed were interacted with BMI in the DAN at rest while complex gait speed, static balance, and lower extremity strength interacted with BMI in the DAN during motor imagery. Results demonstrate that different components of physical function, such as balance or gait speed and BMI, are associated with unique aspects of brain network organization. Gaining a greater mechanistic understanding of the associations between low physical function, body mass, and brain physiology may lead to the development of treatments that not only target specific physical function limitations but also specific brain networks.

Prenatal exposure to polycyclic aromatic hydrocarbons and executive functions at school age: Results from a combined cohort study - Yu Ni; Adam A. Szpiro; Christine T. Loftus; Tomomi Workman; Alexis Sullivan; Erin R. Wallace; Anne M. Riederer; Drew B. Day; Laura E. Murphy; Ruby H.N. Nguyen; Sheela Sathyanarayana; Emily S. Barrett; et al. (International Journal of Hygiene and Environmental Health, 2024)

3D printed and smart alginate wound dressings with pH-responsive drug and nanoparticle release - Tao Huang; Zhe Sun; Daniel E. Heath; Neil O'Brien-Simpson; Andrea J. O'Connor (Chemical Engineering Journal, 2024)

Changes in litter and nitrogen deposition differentially alter forest soil organic matter biogeochemistry - Isla Wrightson; Maryam Tabatabaei Anaraki; John Den Uyl; Knute J. Nadelhoffer; Kate Lajtha; Myrna J. Simpson (Geochimica et Cosmochimica Acta, 2024)

Contractile vacuoles: a rapidly expanding (and occasionally diminishing?) understanding - Kiran J. More; Harpreet Kaur; Alastair G.B. Simpson; Frederick W. Spiegel; Joel B. Dacks (European Journal of Protistology, 2024)

Crustal architecture and tectonic development of western Queensland, Australia, based on deep seismic reflection profiling: Implications for Proterozoic continental assembly and dispersal - Russell J. Korsch; Michael P. Doublier; Dominic D. Brown; Janelle M. Simpson; Andrew J. Cross; Ross D. Costelloe; Wenping Jiang (Tectonophysics, 2024)

Bioprotective lactobacilli in Crescenza and Gouda cheese models to inhibit fungal spoilage - Zheng Zhao; David J. Simpson; Michael G. Gänzle (International Dairy Journal, 2024)

Environmental DNA highlights the influence of salinity and agricultural run-off on coastal fish assemblages in the Great Barrier Reef region - Aashi Parikh; Johan Pansu; Adam Stow; Michael St J. Warne; Christine Chivas; Paul Greenfield; Frédéric Boyer; Stuart Simpson; Rachael Smith; Jacob Gruythuysen; Geoffrey Carlin; Natalie Caulfield; et al. (Environmental Pollution, 2024)

Analysis of natural organic matter chemistry in bentonite clay under compaction using different dry densities and duration - Meiling Man; Huan Tong; Nivetha Srikanthan; Muhammed O. Usman; Claire S. Tully; James J. Noël; Mehran Behazin; W. Jeffrey Binns; Peter G. Keech; Myrna J. Simpson (Applied Geochemistry, 2024)

Randomized trial in rural Native American homes heated with wood stoves: results from the EldersAIR study - Curtis W. Noonan; Ethan S. Walker; Erin O. Semmens; Annie Belcourt; Johna Boulafentis; Crissy Garcia; Jon Graham; Nolan Hoskie; Eugenia Quintana; Julie Simpson; Paul Smith; Howard L. Teasley; et al. (Air Quality, Atmosphere & Health, 2024)

Mitogenomic evidence of population differentiation of thorny skate, Amblyraja radiata , in the North Atlantic - John S. S. Denton; Jeff Kneebone; Lei Yang; Arve Lynghammar; David McElroy; Shannon Corrigan; Klara Jakobsdóttir; Carolyn Miri; Mark Simpson; Gavin J. P. Naylor (Journal of Fish Biology, 2024)
Management of thorny skate ( Amblyraja radiata ) in the Northwest Atlantic has posed a conservation dilemma for several decades due to the species' lack of response to strong conservation efforts in the US Gulf of Maine and the Canadian Scotian Shelf, confusion over the relationship between two reproductive size morphs of differing life histories that are sympatric in the Northwest Atlantic, and conflicting data on regional population connectivity throughout the species' broader range. To better assess potential A. radiata regional population differentiation and genetic links to life‐history variation, we analysed complete mitochondrial genome sequences from 527 specimens collected across the species' North Atlantic geographic range, with particular emphasis on the Northwest Atlantic region. A high level of genetic diversity was evident across the North Atlantic, but significant genetic differentiation was identified between specimens inhabiting the Northwest (Gulf of Maine and Newfoundland) and Northeast (Greenland, Iceland, North Sea, and Arctic Circle) Atlantic. In the Northwest Atlantic, significant differentiation between the Gulf of Maine and Newfoundland regions was revealed; however, the overall level of differentiation was very low. No genetic difference was identified between the large and small reproductive morphs. The results of this study advance our understanding of A. radiata population structure in the North Atlantic but do not resolve all the questions confounding our understanding of the species' biology and evolutionary history.

Geometric effects of fragmentation are likely to mitigate diversity loss following habitat destruction in real‐world landscapes - Colleen Smith; Juan A. Bonachela; Dylan T. Simpson; Natalie J. Lemanski; Rachael Winfree (Global Ecology and Biogeography, 2024)
Aim Habitat conversion is the number one threat to biodiversity. The loss of biodiversity due to habitat loss might be exacerbated if species are harmed by fragmentation per se—the breaking apart of natural habitat that remains (hereafter fragmentation ). However, the evidence that species are harmed by habitat fragmentation is mixed. Studies at the patch scale tend to show that fragmentation reduces diversity due to negative demographic effects on species' dispersal, survival and fecundity. In contrast, studies at the landscape scale tend to show that fragmentation increases diversity. This discrepancy may be partly due to geometric effects, defined as greater species turnover between patches in more fragmented landscapes. Although these effects have been demonstrated theoretically and are expected to be stronger across larger spatial extents, it is unclear whether they are likely to occur in real‐world settings with both realistic landscape patterns and communities. Here, we investigated the possibility of geometric effects using simulations combined with real‐world landscape and community data. Location New Jersey, northeastern USA. Time period Current. Taxa studied Bees. Methods We focused on landscape sizes within the typical range for protected areas (36–576 ha), simulated forest loss using real landscape patterns, and simulated forest‐bee communities based on field data we collected. Results We found weak but positive effects of fragmentation: immediately following forest destruction, the most fragmented forests harboured up to 7.3% more species than the least fragmented forests of the same area, in agreement with observational studies of biodiversity along fragmentation gradients. In contrast to expectations, however, the overall effects of fragmentation did not change with spatial extent. Conclusions Our results suggest that fragmentation can mitigate biodiversity loss immediately following habitat destruction, but that the benefits do not vary strongly with spatial extent in real‐world landscapes and at extents relevant to land management.

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

Monitoring the use of novel psychoactive substances in Australia by wastewater-based epidemiology - Emma L. Jaunay; Richard Bade; Kara R. Paxton; Dhayaalini Nadarajan; Daniel C. Barry; Yuze Zhai; Benjamin J. Tscharke; Jake W. O'Brien; Jochen Mueller; Jason M. White; Bradley S. Simpson; Cobus Gerber (Science of The Total Environment, 2024)

Current extent and future opportunities for living shorelines in Australia - Rebecca L. Morris; Erin Campbell-Hooper; Elissa Waters; Melanie J. Bishop; Catherine E. Lovelock; Ryan J. Lowe; Elisabeth M.A. Strain; Paul Boon; Anthony Boxshall; Nicola K. Browne; James T. Carley; Benedikt J. Fest; et al. (Science of The Total Environment, 2024)

Modelling count data with partial differential equation models in biology - Matthew J. Simpson; Ryan J. Murphy; Oliver J. Maclaren (Journal of Theoretical Biology, 2024)

Rapid removal and replacement of dissolved organic matter during circulation through ultramafic crust - Susan Q. Lang; Bryan Benitez-Nelson; Malayika Vincent; Ronald Soong; Flavio V.C. Kock; Daniel H. Lysak; Amy Jenne; André J. Simpson (Earth and Planetary Science Letters, 2024)

Anthropogenic, biogenic, and photochemical influences on surface formaldehyde and its significant decadal (2006–2017) decrease in the Lewiston-Clarkston valley of the northwestern United States - R. Li; B.T. Jobson; M. Wen; A.L. Li; Y. Huangfu; W. Zhang; R. Hardy; P. O'Keeffe; J. Simpson; M. Fauci; N. Paden (Chemosphere, 2024)

Ecological and social justice should proceed hand-in-hand in conservation - Haydn Washington; John J. Piccolo; Helen Kopnina; Fergus O'Leary Simpson (Biological Conservation, 2024)

IncobotulinumtoxinA in the Treatment of Musician’s Focal Hand Dystonia: A Placebo-Controlled, Crossover Trial - David Simpson; Alexandra Nmashie; Mary Catherine George; Chuanjie Wu; Alexander Pantelyat; Eckart Altenmüller; Michael Chen; David Feng; Steven J Frucht (Toxicon, 2024)

Metabolomics revealed disruptions in amino acid and antioxidant biochemistry in Daphnia magna exposed to industrial effluents associated with plastic and polymer production - Erico A. Oliveira Pereira; Lisa M. Labine; Sonya Kleywegt; Karl J. Jobst; André J. Simpson; Myrna J. Simpson (Environmental Research, 2024)

The last of US: survival of cryopreserved salamander sperm depends on cryodiluent - Devin Chen; Li-Dunn Chen; Shaina S. Lampert; Austin Simpson; Carrie K. Kouba; Andy J. Kouba (Cryobiology, 2023)

Norepinephrine depletion in the brain sex-dependently modulates aspects of spatial learning and memory in female and male rats - Ali Gheidi; Cameron J. Davidson; Serena C. Simpson; Majd A. Yahya; Nareen Sadik; Alixandria T. Mascarin; Shane A. Perrine (Psychopharmacology, 2023)

Sorption of ionic liquids in soil enriched with polystyrene microplastic reveals independent behavior of cations and anions - Natalia Lisiecka; Tomasz Ciesielski; Olga Sopata; Anna Parus; Marta Woźniak-Karczewska; Maria Simpson; Robert Frankowski; Agnieszka Zgoła-Grześkowiak; Arkadiusz Kloziński; Katarzyna Siwińska-Ciesielczyk; Łukasz Klapiszewski; Michał Niemczak; et al. (Chemosphere, 2023)

Distinct dynamics of plant- and microbial-derived soil organic matter in relation to varying climate and soil properties in temperate agroecosystems - Meiling Man; Edward G. Gregorich; Michael H. Beare; Benjamin H. Ellert; Myrna J. Simpson (Geochimica et Cosmochimica Acta, 2023)

Evaluating the trophic transfer of PCBs from fish to humans: Insights from a synergism of environmental monitoring and physiologically-based pharmacokinetic modeling - Adam M. Simpson; Samuel A. Nutile; Olivia C. Hodgson; Ashley E. Russell; Jeremiah D. Keyes; Cody C. Wood; Ronald J. Buckanovich (Environmental Pollution, 2023)

New computational tools and experiments reveal how geometry affects tissue growth in 3D printed scaffolds - Daniel J. VandenHeuvel; Brenna L. Devlin; Pascal R. Buenzli; Maria A. Woodruff; Matthew J. Simpson (Chemical Engineering Journal, 2023)

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

Environmental regulations in the United States lead to improvements in untreated stormwater quality over four decades - Ian M. Simpson; John S. Schwartz; Jon M. Hathaway; Ryan J. Winston (Water Research, 2023)

Assessment of salinity and heat impacts on natural organic matter composition in bentonite for used nuclear fuel storage - Huan Tong; Mehran Behazin; Myrna J. Simpson (Applied Geochemistry, 2023)

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Comparison of the ‘Seattle’ and ‘International’ Criteria Electrocardiogram Interpretation in Division II Female Collegiate Athletes: A Preliminary Study - Ludmila Cosio-Lima; N. Kumar Brooke; L. Adlof; J. Simpson; A. Crawley; Y. Lee (Journal of Science in Sport and Exercise, 2023)

Integrating fecal isotopes and molecular scatology to non-invasively study the spatial ecology of elusive carnivorans: a case study with wild jaguars (Panthera onca) - Brooke E. Crowley; Claudia Wultsch; Emily M. B. Simpson; Marcella J. Kelly (European Journal of Wildlife Research, 2023)

Improving the representation of groundwater processes in a large-scale water resources model - Helen Elizabeth Baron; Virginie D. J. Keller; R. Horan; Donald John MacAllister; Mike Simpson; Christopher R. Jackson; Helen A. Houghton-Carr; Nathan Rickards; Kaushal K. Garg; Muddu Sekhar; Alan MacDonald; Gwyn Rees (Hydrological Sciences Journal, 2023)

Compositional changes in the humin fraction resulting from the long-term cultivation of an Irish grassland soil: Evidence from FTIR and multi-NMR spectroscopies - Guixue Song; Andre J. Simpson; Michael H.B. Hayes (Science of The Total Environment, 2023)

One step antimicrobial coatings for medical device applications based on low fouling polymers containing selenium nanoparticles - Fanyi Li; Tao Huang; Paul Pasic; Christopher D. Easton; Nicolas H. Voelcker; Daniel E. Heath; Neil M. O'Brien-Simpson; Andrea J. O'Connor; Helmut Thissen (Chemical Engineering Journal, 2023)

ACMT Position Statement: End the Use of the Term “Excited Delirium” - Andrew I. Stolbach; Paul I. Dargan; Howard A. Greller; Richard J. Hamilton; Kelly Johnson-Arbor; Brian Patrick Murray; Daniel Ovakim; Laura Tormoehlen; Lewis S. Nelson; Sukhshant Atti; Jeffrey N. Bernstein; Caitlin Bonney; et al. (Journal of Medical Toxicology, 2023)

Deficiency of the mitochondrial ribosomal subunit, MRPL50, causes autosomal recessive syndromic premature ovarian insufficiency - Shabnam Bakhshalizadeh; Daniella H. Hock; Nicole A. Siddall; Brianna L. Kline; Rajini Sreenivasan; Katrina M. Bell; Franca Casagranda; Sadishkumar Kamalanathan; Jayaprakash Sahoo; Niya Narayanan; Dukhabandhu Naik; Varun Suryadevara; et al. (Human Genetics, 2023)
Premature ovarian insufficiency (POI) is a common cause of infertility in women, characterised by amenorrhea and elevated FSH under the age of 40 years. In some cases, POI is syndromic in association with other features such as sensorineural hearing loss in Perrault syndrome. POI is a heterogeneous disease with over 80 causative genes known so far; however, these explain only a minority of cases. Using whole-exome sequencing (WES), we identified a MRPL50 homozygous missense variant (c.335T > A; p.Val112Asp) shared by twin sisters presenting with POI, bilateral high-frequency sensorineural hearing loss, kidney and heart dysfunction. MRPL50 encodes a component of the large subunit of the mitochondrial ribosome. Using quantitative proteomics and western blot analysis on patient fibroblasts, we demonstrated a loss of MRPL50 protein and an associated destabilisation of the large subunit of the mitochondrial ribosome whilst the small subunit was preserved. The mitochondrial ribosome is responsible for the translation of subunits of the mitochondrial oxidative phosphorylation machinery, and we found patient fibroblasts have a mild but significant decrease in the abundance of mitochondrial complex I. These data support a biochemical phenotype associated with MRPL50 variants. We validated the association of MRPL50 with the clinical phenotype by knockdown/knockout of mRpL50 in Drosophila , which resulted abnormal ovarian development. In conclusion, we have shown that a MRPL50 missense variant destabilises the mitochondrial ribosome, leading to oxidative phosphorylation deficiency and syndromic POI, highlighting the importance of mitochondrial support in ovarian development and function.

Fine-scale variability in coral bleaching and mortality during a marine heatwave - Shreya Yadav; Ty N. F. Roach; Michael J. McWilliam; Carlo Caruso; Mariana Rocha de Souza; Catherine Foley; Corinne Allen; Jenna Dilworth; Joel Huckeba; Erika P. Santoro; Renee Wold; Jacquelyn Simpson; et al. (Frontiers in Marine Science, 2023)
Coral bleaching and mortality can show significant spatial and taxonomic heterogeneity at local scales, highlighting the need to understand the fine-scale drivers and impacts of thermal stress. In this study, we used structure-from-motion photogrammetry to track coral bleaching, mortality, and changes in community composition during the 2019 marine heatwave in Kāneʻohe Bay, Hawaiʻi. We surveyed 30 shallow reef patches every 3 weeks for the duration of the bleaching event (August-December) and one year after, resulting in a total of 210 large-area, high-resolution photomosaics that enabled us to follow the fate of thousands of coral colonies through time. We also measured environmental variables such as temperature, sedimentation, depth, and wave velocity at each of these sites, and extracted estimates of habitat complexity (rugosity R and fractal dimension D) from digital elevation models to better understand their effects on patterns of bleaching and mortality. We found that up to 80% of corals experienced moderate to severe bleaching in this period, with peak bleaching occurring in October when heat stress (Degree Heating Weeks) reached its maximum. Mortality continued to accumulate as bleaching levels dropped, driving large declines in more heat-susceptible species (77% loss of Pocillopora cover) and moderate declines in heat-tolerant species (19% and 23% for Porites compressa and Montipora capitata , respectively). Declines in live coral were accompanied by a rapid increase in algal cover across the survey sites. Spatial differences in bleaching were significantly linked to habitat complexity and coral species composition, with reefs that were dominated by Pocillopora experiencing the most severe bleaching. Mortality was also influenced by species composition, fractal dimension, and site-level differences in thermal stress. Our results show that spatial heterogeneity in the impacts of bleaching are driven by a mix of environmental variation, habitat complexity, and differences in assemblage composition.

Nitrogen Addition Increases Freeze Resistance in Black Mangrove (Avicennia germinans) Shrubs in a Temperate-Tropical Ecotone - Ilka C. Feller; Uta Berger; Samantha K. Chapman; Emily M. Dangremond; Nicole G. Dix; J. Adam Langley; Catherine E. Lovelock; Todd Z. Osborne; Audrey C. Shor; Loraé T. Simpson (Ecosystems, 2023)

Spectral classification by generative adversarial linear discriminant analysis - Ziyi Cao; Shijie Zhang; Youlin Liu; Casey J. Smith; Alex M. Sherman; Yechan Hwang; Garth J. Simpson (Analytica Chimica Acta, 2023)

Hydrologic responses of single land use urban and forested watersheds and their implications to improving urban drainage design - Ian M. Simpson; Ryan J. Winston; R. Andrew Tirpak; Jay D. Dorsey; James H. Stagge; Jon M. Hathaway (Journal of Hydrology, 2023)

Sea temperature is the primary driver of recent and predicted fish community structure across Northeast Atlantic shelf seas - Louise A. Rutterford; Stephen D. Simpson; Bjarte Bogstad; Jennifer A. Devine; Martin J. Genner (Global Change Biology, 2023)
Climate change has strongly influenced the distribution and abundance of marine fish species, leading to concern about effects of future climate on commercially harvested stocks. Understanding the key drivers of large‐scale spatial variation across present‐day marine assemblages enables predictions of future change. Here we present a unique analysis of standardised abundance data for 198 marine fish species from across the Northeast Atlantic collected by 23 surveys and 31,502 sampling events between 2005 and 2018. Our analyses of the spatially comprehensive standardised data identified temperature as the key driver of fish community structure across the region, followed by salinity and depth. We employed these key environmental variables to model how climate change will affect both the distributions of individual species and local community structure for the years 2050 and 2100 under multiple emissions scenarios. Our results consistently indicate that projected climate change will lead to shifts in species communities across the entire region. Overall, the greatest community‐level changes are predicted at locations with greater warming, with the most pronounced effects at higher latitudes. Based on these results, we suggest that future climate‐driven warming will lead to widespread changes in opportunities for commercial fisheries across the region.

Comparing environmental DNA collection methods for sampling community composition on marine infrastructure - Jason B. Alexander; Michael J. Marnane; Justin I. McDonald; Sherralee S. Lukehurst; Travis S. Elsdon; Tiffany Simpson; Shawn Hinz; Michael Bunce; Euan S. Harvey (Estuarine, Coastal and Shelf Science, 2023)

Daphnia magna sub-lethal exposure to phthalate pollutants elicits disruptions in amino acid and energy metabolism - Erico A. Oliveira Pereira; Lisa M. Labine; Sonya Kleywegt; Karl J. Jobst; André J. Simpson; Myrna J. Simpson (Aquatic Toxicology, 2023)

Extreme eutrophication and salinisation in the Coorong estuarine-lagoon ecosystem of Australia's largest river basin (Murray-Darling) - L.M. Mosley; S. Priestley; J. Brookes; S. Dittmann; J. Farkaš; M. Farrell; A.J. Ferguson; M. Gibbs; M. Hipsey; J. Huang; O. Lam-Gordillo; S.L. Simpson; et al. (Marine Pollution Bulletin, 2023)

Monitoring the effects of urban and forested land uses on runoff quality: Implications for improved stormwater management - Ian M. Simpson; Ryan J. Winston; Jay D. Dorsey (Science of The Total Environment, 2023)

Generalized moisture diffusivity for food drying through multiscale modeling - Zachary G. Welsh; Matthew J. Simpson; Md Imran H. Khan; M.A. Karim (Journal of Food Engineering, 2023)

Gene flow connects key leopard (Panthera pardus) populations despite habitat fragmentation and persecution - Declan R. Morris; Todd J. McWhorter; Wayne S. J. Boardman; Greg Simpson; Jeanette Wentzel; Jannie Coetzee; Ferreira Du Plessis; Yoshan Moodley (Biodiversity and Conservation, 2023)

Application of metabolomic methods to evaluate the impact of pollutants on soil organisms: Recent progress and future perspectives - Myrna J. Simpson (Current Opinion in Environmental Science & Health, 2023)

Genome screening, reporting, and genetic counseling for healthy populations - Selina Casalino; Erika Frangione; Monica Chung; Georgia MacDonald; Sunakshi Chowdhary; Chloe Mighton; Hanna Faghfoury; Yvonne Bombard; Lisa Strug; Trevor J. Pugh; Jared Simpson; Saranya Arnoldo; et al. (Human Genetics, 2023)

Assessment of heat and radiation impacts on natural organic matter composition in bentonite for used nuclear fuel disposal - Huan Tong; Mehran Behazin; Myrna J. Simpson (Applied Clay Science, 2023)

Effects of interactions between anthropogenic stressors and recurring perturbations on ecosystem resilience and collapse - David A. Keith; Doug H. Benson; Ian R. C. Baird; Laura Watts; Christopher C. Simpson; Martin Krogh; Sarsha Gorissen; Jose R. Ferrer‐Paris; Tanya J. Mason (Conservation Biology, 2023)
Insights into declines in ecosystem resilience and their causes and effects can inform preemptive action to avoid ecosystem collapse and loss of biodiversity, ecosystem services, and human well‐being. Empirical studies of ecosystem collapse are rare and hampered by ecosystem complexity, nonlinear and lagged responses, and interactions across scales. We investigated how an anthropogenic stressor could diminish ecosystem resilience to a recurring perturbation by altering a critical ecosystem driver. We studied groundwater‐dependent, peat‐accumulating, fire‐prone wetlands known as upland swamps in southeastern Australia. We hypothesized that underground mining (stressor) reduces resilience of these wetlands to landscape fires (perturbation) by diminishing groundwater, a key ecosystem driver. We monitored soil moisture as an indicator of ecosystem resilience during and after underground mining. After landscape fire, we compared responses of multiple state variables representing ecosystem structure, composition, and function in swamps within the mining footprint with unmined reference swamps. Soil moisture declined without recovery in swamps with mine subsidence (i.e., undermined), but was maintained in reference swamps over 8 years (effect size 1.8). Relative to burned reference swamps, burned undermined swamps showed greater loss of peat via substrate combustion; reduced cover, height, and biomass of regenerating vegetation; reduced postfire plant species richness and abundance; altered plant species composition; increased mortality rates of woody plants; reduced postfire seedling recruitment; and extirpation of a hydrophilic animal. Undermined swamps therefore showed strong symptoms of postfire ecosystem collapse, whereas reference swamps regenerated vigorously. We found that an anthropogenic stressor diminished the resilience of an ecosystem to recurring perturbations, predisposing it to collapse. Avoidance of ecosystem collapse hinges on early diagnosis of mechanisms and preventative risk reduction. It may be possible to delay or ameliorate symptoms of collapse or to restore resilience, but the latter appears unlikely in our study system due to fundamental alteration of a critical ecosystem driver. Efectos de las interacciones entre los estresantes antropogénicos y las perturbaciones recurrentes sobre la resiliencia y el colapso de los ecosistemas

Examining current best-practices for the use of wild post-larvae capture, culture, and release for fisheries enhancement - Laura E. Richardson; Philippe Lenfant; Leo J. Clarke; Amelie Fontcuberta; Anaïs Gudefin; Gilles Lecaillon; Lewis Le Vay; Andrew N. Radford; Stephen D. Simpson (Frontiers in Marine Science, 2023)
Demand for marine fisheries is rising despite global impacts on the productive capacity of wild fish stocks due to overfishing, habitat loss, and global warming. Fisheries enhancement programs—aimed at augmenting stocks by releasing juveniles into the wild—are expected to play an increasingly important auxiliary role in addressing capture-based fishery limitations into the future. However, concerns exist over the impacts and efficacy of aquaculture-based enhancement (ABE), releasing captive-bred fish into wild populations. An alternative but understudied approach for fisheries enhancement is wild post-larvae capture, culture, and release (PCCR). Here, we provide an overview of the PCCR process, from initial planning to measuring success, providing an overview of its implementation in a viable finfish fishery, the white seabream Diplodus sargus in the Mediterranean. We discuss management application of PCCR-based enhancement and its limitations, highlighting existing knowledge gaps and future research required to realize the full potential of this alternative approach. Notwithstanding some limitations–including limited uptake for full evaluation, some species restrictions, density-dependent mortality, and the remaining open challenge for stock enhancement generally of tracking released fish through to reproduction–PCCR offers potential as a credible auxiliary management tool for fisheries restoration.

Profile likelihood-based parameter and predictive interval analysis guides model choice for ecological population dynamics - Matthew J. Simpson; Shannon A. Walker; Emma N. Studerus; Scott W. McCue; Ryan J. Murphy; Oliver J. Maclaren (Mathematical Biosciences, 2023)

Contrasting Effects of Nitrogen Addition on Leaf Photosynthesis and Respiration in Black Mangrove in North Florida - Matthew A. Sturchio; Jeff Chieppa; Lorae T. Simpson; Ilka C. Feller; Samantha K. Chapman; Michael J. Aspinwall (Estuaries and Coasts, 2023)

Soil organic matter molecular composition with long‐term detrital alterations is controlled by site‐specific forest properties - Laura Castañeda‐Gómez; Kate Lajtha; Richard Bowden; Fathima Nahidha Mohammed Jauhar; Juan Jia; Xiaojuan Feng; Myrna J. Simpson (Global Change Biology, 2023)
Forest ecosystems are important global soil carbon (C) reservoirs, but their capacity to sequester C is susceptible to climate change factors that alter the quantity and quality of C inputs. To better understand forest soil C responses to altered C inputs, we integrated three molecular composition published data sets of soil organic matter (SOM) and soil microbial communities for mineral soils after 20 years of detrital input and removal treatments in two deciduous forests: Bousson Forest (BF), Harvard Forest (HF), and a coniferous forest: H.J. Andrews Forest (HJA). Soil C turnover times were estimated from radiocarbon measurements and compared with the molecular‐level data (based on nuclear magnetic resonance and specific analysis of plant‐ and microbial‐derived compounds) to better understand how ecosystem properties control soil C biogeochemistry and dynamics. Doubled aboveground litter additions did not increase soil C for any of the forests studied likely due to long‐term soil priming. The degree of SOM decomposition was higher for bacteria‐dominated sites with higher nitrogen (N) availability while lower for the N‐poor coniferous forest. Litter exclusions significantly decreased soil C, increased SOM decomposition state, and led to the adaptation of the microbial communities to changes in available substrates. Finally, although aboveground litter determined soil C dynamics and its molecular composition in the coniferous forest (HJA), belowground litter appeared to be more influential in broadleaf deciduous forests (BH and HF). This synthesis demonstrates that inherent ecosystem properties regulate how soil C dynamics change with litter manipulations at the molecular‐level. Across the forests studied, 20 years of litter additions did not enhance soil C content, whereas litter reductions negatively impacted soil C concentrations. These results indicate that soil C biogeochemistry at these temperate forests is highly sensitive to changes in litter deposition, which are a product of environmental change drivers.

Optimization and Scale Up of Spray Dried CPZEN-45 Aerosol Powders for Inhaled Tuberculosis Treatment - Ian E. Stewart; Phillip G. Durham; Jacob M. Sittenauer; Aranza P. Barreda; Grayson W. Stowell; Carmella Moody; Jeffery B. Mecham; Catherine Simpson; Sharon Daily; Sara E. Maloney; Mark D. Williams; Diana Severynse-Stevens; et al. (Pharmaceutical Research, 2022)

Phosphorus fertiliser value of sewage sludge ash applied to soils differing in phosphate buffering and phosphate sorption capacity - Michela Battisti; Richard J. Simpson; Adam Stefanski; Alan E. Richardson; Rebecca E. Haling (Nutrient Cycling in Agroecosystems, 2022)

Fire‐related threats and transformational change in Australian ecosystems - David A. Keith; Stuart P. Allen; Rachael V. Gallagher; Berin D. E. Mackenzie; Tony D. Auld; Sarah Barrett; Anne Buchan; Valerie English; Carl Gosper; Dave Kelly; Allen McIllwee; Rachel T. Melrose; et al. (Global Ecology and Biogeography, 2022)
Aim Megafire events generate immediate concern for wildlife and human well‐being, but their broader ecological impacts likely extend beyond individual species and single fire events. In the first mechanistic study of fire effects focussed on ecosystems, we aimed to assess the sensitivity and exposure of ecosystems to multiple fire‐related threats, placing impacts in the context of changing fire regimes and their interactions with other threats. Location Southern and eastern Australia. Time period 2019–2020. Major species studied Australian ecosystems. Methods We defined 15 fire‐related threats to ecosystems based on mechanisms associated with: (a) direct effects of fire regime components; (b) interactions between fire and physical environmental processes; (c) effects of fire on biological interactions; and (d) interactions between fire and human activity. We estimated the sensitivity and exposure of a sample of 92 ecosystem types to each threat type based on published relationships and spatial analysis of the 2019–2020 fires. Results Twenty‐nine ecosystem types assessed had more than half of their distribution exposed to one or more threat types, and only three of those were listed as nationally threatened. Three fire‐related threat types posed the most severe threats to large numbers of ecosystem types: high frequency fire; pre‐fire drought; and post‐fire invasive predator activity. The ecosystem types most affected ranged from rain forests to peatlands, and included some, such as sclerophyllous eucalypt forests and heathlands, that are traditionally regarded as fire‐prone and fire‐adapted. Main conclusions Most impacts of the 2019–2020 fires on ecosystems became apparent only when they were placed in the context of the whole fire regime and its interactions with other threatening processes, and were not direct consequences of the megafire event itself. Our mechanistic approach enables ecosystem‐specific management responses for the most threatened ecosystem types to be targeted at underlying causes of degradation and decline.

Population density estimate of leopards (Panthera pardus) in north-western Mpumalanga, South Africa, determined using spatially explicit capture–recapture methods - Declan R. Morris; Wayne S. J. Boardman; Lourens H. Swanepoel; Greg Simpson; Jannie Coetzee; Gerrie J. Camacho; Todd J. McWhorter (Mammalian Biology, 2022)

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Late Ordovician subsurface carbonates and fossil assemblages from the area immediately west and northwest of Peak Hill in central New South Wales and their regional correlation - Y. Y. Zhen; T. J. Wells; C. J. Simpson; J. Parslow (Australian Journal of Earth Sciences, 2022)

Scientific impact, direction and highlights of Plant and Soil in the 30 years since Professor Hans Lambers became Editor in Chief - Timothy S. George; Ismail Cakmak; Richard J. Simpson; Alexia Stokes; Philip J. White (Plant and Soil, 2022)

Organic anions facilitate the mobilization of soil organic phosphorus and its subsequent lability to phosphatases - Alan E. Richardson; Timothy S. George; Maarten Hens; Emmanuel Delhaize; Peter R. Ryan; Richard J. Simpson; Peter J. Hocking (Plant and Soil, 2022)

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Quantification and Degradation of 2,2-Dibromo-3-Nitrilopropionamide (DBNPA) in Bioethanol Fermentation Coproducts - J. V. Simpson; C. L. Wiatr (World Journal of Microbiology and Biotechnology, 2022)
2,2-Dibromo-3-nitrilopropionamide (DBNPA) has been used as a biocide in industrial water applications due to its instantaneous antimicrobial activity and rapid chemical breakdown. In this study, DBNPA is considered a potential alternative for antibiotics used for bacterial control during corn-to-ethanol fermentation. A method using LC/MS/MS was developed to accurately quantify DBNPA in water. When this method was applied to quantify DBNPA concentration in a fermentation matrix, DBNPA was found to be unstable and to decay rapidly, preventing validation of the method or quantitation. This method was then used to evaluate the degradation rate of DBNPA in whole stillage, which is the nonvolatile residue produced by removal of ethanol from corn-based fermentation beer by distillation through the relative decrease in measured signal. In addition, a method was developed and validated to quantify bromide, one of the degradation products of DBNPA, in whole stillage using LC/MS/MS. The degradation rate of DBNPA in whole stillage was found to display first-order kinetics with a calculated half-life of 85 min. Laboratory analytical chemistry results on DBNPA degradation were confirmed based on a bacterial viability assay in field trials.

Global maps of soil temperature - Jonas J. Lembrechts; Johan van den Hoogen; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Julia Kemppinen; Martin Kopecký; Miska Luoto; Ilya M. D. Maclean; Thomas W. Crowther; Joseph J. Bailey; Stef Haesen; et al. (Global Change Biology, 2022)
Research in global change ecology relies heavily on global climatic grids derived from estimates of air temperature in open areas at around 2 m above the ground. These climatic grids do not reflect conditions below vegetation canopies and near the ground surface, where critical ecosystem functions occur and most terrestrial species reside. Here, we provide global maps of soil temperature and bioclimatic variables at a 1‐km 2 resolution for 0–5 and 5–15 cm soil depth. These maps were created by calculating the difference (i.e. offset) between in situ soil temperature measurements, based on time series from over 1200 1‐km 2 pixels (summarized from 8519 unique temperature sensors) across all the world's major terrestrial biomes, and coarse‐grained air temperature estimates from ERA5‐Land (an atmospheric reanalysis by the European Centre for Medium‐Range Weather Forecasts). We show that mean annual soil temperature differs markedly from the corresponding gridded air temperature, by up to 10°C (mean = 3.0 ± 2.1°C), with substantial variation across biomes and seasons. Over the year, soils in cold and/or dry biomes are substantially warmer (+3.6 ± 2.3°C) than gridded air temperature, whereas soils in warm and humid environments are on average slightly cooler (−0.7 ± 2.3°C). The observed substantial and biome‐specific offsets emphasize that the projected impacts of climate and climate change on near‐surface biodiversity and ecosystem functioning are inaccurately assessed when air rather than soil temperature is used, especially in cold environments. The global soil‐related bioclimatic variables provided here are an important step forward for any application in ecology and related disciplines. Nevertheless, we highlight the need to fill remaining geographic gaps by collecting more in situ measurements of microclimate conditions to further enhance the spatiotemporal resolution of global soil temperature products for ecological applications.

Anthropogenic Mixing in Seasonally Stratified Shelf Seas by Offshore Wind Farm Infrastructure - Robert M. Dorrell; Charlie J. Lloyd; Ben J. Lincoln; Tom P. Rippeth; John R. Taylor; Colm-cille P. Caulfield; Jonathan Sharples; Jeff A. Polton; Brian D. Scannell; Deborah M. Greaves; Rob A. Hall; John H. Simpson (Frontiers in Marine Science, 2022)
The offshore wind energy sector has rapidly expanded over the past two decades, providing a renewable energy solution for coastal nations. Sector development has been led in Europe, but is growing globally. Most developments to date have been in well-mixed, i.e., unstratified, shallow-waters near to shore. Sector growth is, for the first time, pushing developments to deep water, into a brand new environment: seasonally stratified shelf seas. Seasonally stratified shelf seas, where water density varies with depth, have a disproportionately key role in primary production, marine ecosystem and biogeochemical cycling. Infrastructure will directly mix stratified shelf seas. The magnitude of this mixing, additional to natural background processes, has yet to be fully quantified. If large enough it may erode shelf sea stratification. Therefore, offshore wind growth may destabilize and fundamentally change shelf sea systems. However, enhanced mixing may also positively impact some marine ecosystems. This paper sets the scene for sector development into this new environment, reviews the potential physical and environmental benefits and impacts of large scale industrialization of seasonally stratified shelf seas and identifies areas where research is required to best utilize, manage, and mitigate environmental change.

Aortic haemodynamics: the effects of habitual endurance exercise, age and muscle sympathetic vasomotor outflow in healthy men - Denis J. Wakeham; Tony G. Dawkins; Rachel N. Lord; Jack S. Talbot; Freya M. Lodge; Bryony A. Curry; Lydia L. Simpson; Christopher J. A. Pugh; Robert E. Shave; Jonathan P. Moore (European Journal of Applied Physiology, 2022)
Purpose We determined the effect of habitual endurance exercise and age on aortic pulse wave velocity (aPWV), augmentation pressure (AP) and systolic blood pressure (aSBP), with statistical adjustments of aPWV and AP for heart rate and aortic mean arterial pressure, when appropriate. Furthermore, we assessed whether muscle sympathetic nerve activity (MSNA) correlates with AP in young and middle-aged men. Methods Aortic PWV, AP, aortic blood pressure (applanation tonometry; SphygmoCor) and MSNA (peroneal microneurography) were recorded in 46 normotensive men who were either young or middle-aged and endurance-trained runners or recreationally active nonrunners (10 nonrunners and 13 runners within each age-group). Between-group differences and relationships between variables were assessed via ANOVA/ANCOVA and Pearson product-moment correlation coefficients, respectively. Results Adjusted aPWV and adjusted AP were similar between runners and nonrunners in both age groups (all, P > 0.05), but higher with age (all, P < 0.001), with a greater effect size for the age-related difference in AP in runners (Hedges’ g , 3.6 vs 2.6). aSBP was lower in young ( P = 0.009; g = 2.6), but not middle-aged ( P = 0.341; g = 1.1), runners compared to nonrunners. MSNA burst frequency did not correlate with AP in either age group (young: r = 0.00, P = 0.994; middle-aged: r = − 0.11, P = 0.604). Conclusion There is an age-dependent effect of habitual exercise on aortic haemodynamics, with lower aSBP in young runners compared to nonrunners only. Statistical adjustment of aPWV and AP markedly influenced the outcomes of this study, highlighting the importance of performing these analyses. Further, peripheral sympathetic vasomotor outflow and AP were not correlated in young or middle-aged normotensive men.

Spatiotemporal Patterns in the Biomass of Drift Macroalgae in the Indian River Lagoon, Florida, United States - Lauren M. Hall; Lori J. Morris; Robert H. Chamberlain; M. Dennis Hanisak; Robert W. Virnstein; Richard Paperno; Bernhard Riegl; L. Rex Ellis; Ali Simpson; Charles A. Jacoby (Frontiers in Marine Science, 2022)
Drift macroalgae plays key roles in the ecology of many coastal systems, including the Indian River Lagoon. In the lagoon, changes in the biomass of drift macroalgae may have interacted with an unprecedented bloom of phytoplankton in 2011. Patterns in the biomass of drift macroalgae were identified using new and original analyses of data from several sampling programs collected between 1997 and 2019. All available data show a relatively low biomass of drift macroalgae in 2010–2012, and surveys of fixed transects and seining as part of a fisheries independent monitoring program also recorded low biomass in 2016. Low light availability and potentially stressful temperatures appeared to be the main influences as indicated by the results of incubations in tanks to determine environmental tolerances and data on ambient conditions. Decreased biomass of drift macroalgae had implications for cycling of nutrients because carbon, nitrogen, and phosphorus not stored in the tissues of drift macroalgae became available for uptake by other primary producers, including phytoplankton. The estimated 14–18% increases in concentrations of these elements in the IRL could have promoted longer and more intense phytoplankton blooms, which would have reduced light availability and increased stress on algae and seagrasses. An improved understanding of such feedback and the ecological roles played by drift macroalgae will support more effective management of nutrient loads and the system by accounting for cycling of nutrients among primary producers.

Modelling the effects of cold temperature during the reproductive stage on the yield of chickpea (Cicer arietinum L.) - Muhuddin Rajin Anwar; David J. Luckett; Yashvir S. Chauhan; Ryan H. L. Ip; Lancelot Maphosa; Marja Simpson; Annie Warren; Rosy Raman; Mark F. Richards; Georgina Pengilley; Kristy Hobson; Neroli Graham (International Journal of Biometeorology, 2022)
During the reproductive stage, chilling temperatures and frost reduce the yield of chickpea and limit its adaptation. The adverse effects of chilling temperature and frost in terms of the threshold temperatures, impact of cold duration, and genotype-by-environment-by-management interactions are not well quantified. Crop growth models that predict flowering time and yield under diverse climates can identify combinations of cultivars and sowing time to reduce frost risk in target environments. The Agricultural Production Systems Simulator (APSIM-chickpea) model uses daily temperatures to model basic crop growth but does not include penalties for either frost damage or cold temperatures during flowering and podding stages. Regression analysis overcame this limitation of the model for chickpea crops grown at 95 locations in Australia using 70 years of historic data incorporating three cultivars and three sowing times (early, mid, and late). We modified model parameters to include the effect of soil water on thermal time calculations, which significantly improved the prediction of flowering time. Simulated data, and data from field experiments grown in Australia (2013 to 2019), showed robust predictions for flowering time ( n = 29; R 2 = 0.97), and grain yield ( n = 22; R 2 = 0.63–0.70). In addition, we identified threshold cold temperatures that significantly affected predicted yield, and combinations of locations, variety, and sowing time where the overlap between peak cold temperatures and peak flowering was minimal. Our results showed that frost and/or cold temperature–induced yield losses are a major limitation in some unexpected Australian locations, e.g., inland, subtropical latitudes in Queensland. Intermediate sowing maximise yield, as it avoids cold temperature, late heat, and drought stresses potentially limiting yield in early and late sowing respectively.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Land Use History Mediates Soil Biogeochemical Responses to Drought in Temperate Forest Ecosystems - Ernest D. Osburn; Julia S. Simpson; Brian D. Strahm; J. E. Barrett (Ecosystems, 2022)

Timescales and thermal evolution of large silicic magma reservoirs during an ignimbrite flare-up: perspectives from zircon - Adam Curry; Sean P. Gaynor; J. H. F. L. Davies; Maria Ovtcharova; Guy Simpson; Luca Caricchi (Contributions to Mineralogy and Petrology, 2021)
Four voluminous ignimbrites (150–500 km 3 ) erupted in rapid succession at 27 Ma in the central San Juan caldera cluster, Colorado. To reconstruct the timescales and thermal evolution of these magma reservoirs, we used zircon ID-TIMS U–Pb geochronology, zircon LA-ICP-MS geochemistry, thermal modeling, and zircon age and crystallization modeling. Zircon geochronology reveals dispersed zircon age spectra in all ignimbrites, with decreasing age dispersion through time that we term a ‘chimney sweeping’ event. Zircon whole-grain age modeling suggests that 2σ zircon age spans represent approximately one-quarter of total zircon crystallization timescales due to the averaging effect of whole-grain, individual zircon ages, resulting in zircon crystallization timescales of 0.8–2.7 m.y. Thermal and zircon crystallization modeling combined with Ti-in-zircon temperatures indicates that magma reservoirs were built over millions of years at relatively low magmatic vertical accretion rates (VARs) of 2–5 × 10 –3 m y −1 (2–5 × 10 –6 km 3 y −1 km −2 ), and we suggest that such low VARs were characteristic of the assembly of the greater San Juan magmatic body. Though we cannot unequivocally discern between dispersed zircon age spectra caused by inheritance (xenocrystic or antecrystic) versus prolonged crystallization from the same magma reservoir (autocrystic), our findings suggest that long-term magma input at relatively low VARs produced thermally mature upper crustal magma reservoirs resulting in protracted zircon crystallization timescales. Compiling all U–Pb ID-TIMS zircon ages of large ignimbrites, we interpret the longer timescales of subduction-related ignimbrites as a result of longer term, lower flux magmatism, and the shorter timescales of Snake River Plain ignimbrites as a result of shorter term, higher flux magmatism.

Bird rookery nutrient over-enrichment as a potential accelerant of mangrove cay decline in Belize - L. T. Simpson; S. W. J. Canty; J. R. Cissell; M. K. Steinberg; J. A. Cherry; I. C. Feller (Oecologia, 2021)

A method and its application to determine the amount of cannabinoids in sewage sludge and biosolids - Aaron J. Pandopulos; Bradley S. Simpson; Richard Bade; Jake W. O’Brien; Meena K. Yadav; Jason M. White; Cobus Gerber (Environmental Science and Pollution Research, 2021)

The Toxicology Investigators Consortium 2020 Annual Report - Meghan B. Spyres; Kim Aldy; Lynn A Farrugia; A. Min Kang; Jennifer S. Love; Sharan L. Campleman; Shao Li; Alexandra Amaducci; Evan Schwarz; Paul M. Wax; Jeffery Brent; J. Acciani; et al. (Journal of Medical Toxicology, 2021)

Biomarkers in Ringed Seals Reveal Recent Onset of Borealization in the High- Compared to the Mid-Latitude Canadian Arctic - Camille de la Vega; Claire Mahaffey; David J. Yurkowski; Louisa Norman; Elysia Simpson; Sophie Smout; Steven H. Ferguson; Rachel M. Jeffreys (Frontiers in Marine Science, 2021)
Warming of the Arctic has resulted in environmental and ecological changes, termed borealization, leading to the northward shift of temperate species. Borealization has occurred across all trophic levels, altering the structure of the food web. The onset and rate of borealization likely varies with latitude, depending on local warming and advection of warmer water into the Arctic. In order to assess latitudinal trends in food web structure in the Arctic, we analyzed stable nitrogen isotopes of specific amino acids alongside bulk stable carbon isotopes in ringed seal muscle tissue from the Canadian Arctic Archipelago (high-Arctic) and Southern Baffin Bay (mid-Arctic) from 1990 to 2016. Our results indicate a shift in food web structure in the high-Arctic that has occurred more recently when compared with the mid-Arctic. Specifically, over the past 25 years, the trophic position of ringed seals from the mid-Arctic was largely constant, whereas the trophic position of ringed seals decreased in the high-Arctic, reaching similar values observed in the mid-Arctic in 2015–2016. This suggests a potential shortening of the food chain length in the high-Arctic, possibly driven by changes in zooplankton communities feeding complexity in association with sea ice decline. This study identifies a temporal offset in the timing of borealization in the Canadian Arctic, resulting in different response of food webs to ecological changes, depending on latitude.

The quorum‐sensing systems of Vibrio campbellii DS40M4 and BB120 are genetically and functionally distinct - Chelsea A. Simpson; Blake D. Petersen; Nicholas W. Haas; Logan J. Geyman; Aimee H. Lee; Ram Podicheti; Robert Pepin; Laura C. Brown; Douglas B. Rusch; Michael P. Manzella; Kai Papenfort; Julia C. van Kessel (Environmental Microbiology, 2021)
Summary Vibrio campbellii BB120 (previously classified as Vibrio harveyi ) is a fundamental model strain for studying quorum sensing in vibrios. A phylogenetic evaluation of sequenced Vibrio strains in Genbank revealed that BB120 is closely related to the environmental isolate V. campbellii DS40M4. We exploited DS40M4's competence for exogenous DNA uptake to rapidly generate greater than 30 isogenic strains with deletions of genes encoding BB120 quorum‐sensing system homologues. Our results show that the quorum‐sensing circuit of DS40M4 is distinct from BB120 in three ways: (i) DS40M4 does not produce an acyl homoserine lactone autoinducer but encodes an active orphan LuxN receptor, (ii) the quorum regulatory small RNAs (Qrrs) are not solely regulated by autoinducer signalling through the response regulator LuxO and (iii) the DS40M4 quorum‐sensing regulon is much smaller than BB120 (~100 genes vs. ~400 genes, respectively). Using comparative genomics to expand our understanding of quorum‐sensing circuit diversity, we observe that conservation of LuxM/LuxN proteins differs widely both between and within Vibrio species. These strains are also phenotypically distinct: DS40M4 exhibits stronger interbacterial cell killing, whereas BB120 forms more robust biofilms and is bioluminescent. These results underscore the need to examine wild isolates for a broader view of bacterial diversity in the marine ecosystem.

The effects of normoxic endurance exercise on erythropoietin (EPO) production and the impact of selective β1 and non-selective β1 + β2 adrenergic receptor blockade - Rod J. Azadan; Nadia H. Agha; Hawley E. Kunz; Forrest L. Baker; Preteesh L. Mylabathula; Tracy A. Ledoux; Daniel P. O’Connor; Charles R. Pedlar; Richard J. Simpson (European Journal of Applied Physiology, 2021)

Light at night reduces digestive efficiency of developing birds: an experiment with king quail - Tuul Sepp; Emily Webb; Richard K. Simpson; Mathieu Giraudeau; Kevin J. McGraw; Pierce Hutton (The Science of Nature, 2021)

Increasing whole-body energetic stress does not augment fasting-induced changes in human skeletal muscle - Hashim Islam; Alessandra Amato; Jacob T. Bonafiglia; Fasih A. Rahman; Nicholas Preobrazenski; Andrew Ma; Craig A. Simpson; Joe Quadrilatero; Brendon J. Gurd (Pflügers Archiv - European Journal of Physiology, 2021)

Lung abnormalities do not influence aerobic capacity in school children born preterm - Christopher A. O’Dea; Karla Logie; Andrew C. Wilson; J. Jane Pillow; Conor Murray; Georgia Banton; Shannon J. Simpson; Graham L. Hall; Andrew Maiorana (European Journal of Applied Physiology, 2021)

Zircon petrochronology in large igneous provinces reveals upper crustal contamination processes: new U–Pb ages, Hf and O isotopes, and trace elements from the Central Atlantic magmatic province (CAMP) - J. H. F. L. Davies; A. Marzoli; H. Bertrand; N. Youbi; M. Ernesto; N. D. Greber; M. Ackerson; G. Simpson; A.-S. Bouvier; L. Baumgartner; T. Pettke; F. Farina; et al. (Contributions to Mineralogy and Petrology, 2021)
Zircon occasionally crystallizes in evolved melt pockets in mafic large igneous province (LIP) magmas, and in these cases, it is used to provide high-precision age constraints on LIP events. The precision and accuracy of high-precision ages from LIPs are crucially important, because they may be implicated in mass extinctions. However, why zircon crystallizes in these magmas is not clearly understood, since their mafic compositions should limit zircon saturation. Here, we investigate the occurrence of zircon (and baddeleyite) in intrusive and extrusive mafic rocks from Central Atlantic Magmatic Province (CAMP) using petrography, trace-element analysis, Ti temperatures, Hf and oxygen isotopes, and high-precision U–Pb geochronology, along with petrological and thermal modeling. We provide new ages for CAMP sills that intruded into Paleozoic sediments in Brazil, indicating that the high and low Ti magmatism in this area occurred synchronously over 264 ± 57 ka. We show that upper crustal assimilation, especially of shales, during the emplacement of the CAMP likely led to zircon saturation. Assimilation of upper crustal sediments is also supported by high δ 18 O values and some rare negative εHf values in the zircon crystals. The only extrusive sample analyzed was the North Mountain basalt in Nova Scotia, Canada. This sample contains a large age variation in its zircon crystals (up to 4 Ma), and the older crystals have slightly more negative εHf values suggesting the presence of small (micron scale) xenocrystic cores associated with very late-stage sediment assimilation. However, the CAMP dataset as a whole suggests that the presence of xenocrystic cores is rare. Assuming no xenocrystic cores, and considering the zircon undersaturated nature of LIP mafic melts, the oldest zircon age clusters in a population should record the magma emplacement (or time when assimilation occurred), and the younger ages in a population are more likely to reflect Pb loss, especially given the high U concentrations of LIP zircon. Our identification of heterogeneous isotopic and elemental compositions in LIP zircon indicates that zircon in these magmas saturate in isolated minute melt pockets just before the system cools below its solidus.

Small-scale spatial structure affects predator-prey dynamics and coexistence - Anudeep Surendran; Michael J. Plank; Matthew J. Simpson (Theoretical Ecology, 2020)

Crop rotations differ in soil carbon stabilization efficiency, but the response to quality of structural plant inputs is ambiguous - Alison E. King; Katelyn A. Congreves; Bill Deen; Kari E. Dunfield; Myrna J. Simpson; R. Paul Voroney; Claudia Wagner-Riddle (Plant and Soil, 2020)

Correction to: Factors Influencing Carbon Stocks and Accumulation Rates in Eelgrass Meadows Across New England, USA - A. B. Novak; M. C. Pelletier; P. Colarusso; J. Simpson; M. N. Gutierrez; A. Arias-Ortiz; M. Charpentier; P. Masque; P. Vella (Estuaries and Coasts, 2020)

Factors Influencing Carbon Stocks and Accumulation Rates in Eelgrass Meadows Across New England, USA - A. B. Novak; M. C. Pelletier; P. Colarusso; J. Simpson; M. N. Gutierrez; A. Arias-Ortiz; M. Charpentier; P. Masque; P. Vella (Estuaries and Coasts, 2020)
Increasing the protection of coastal vegetated ecosystems has been suggested as one strategy to compensate for increasing carbon dioxide (CO 2 ) in the atmosphere as the capacity of these habitats to sequester and store carbon exceeds that of terrestrial habitats. Seagrasses are a group of foundation species that grow in shallow coastal and estuarine systems and have an exceptional ability to sequester and store large quantities of carbon in biomass and, particularly, in sediments. However, carbon stocks (C org stocks) and carbon accumulation rates (C org accumulation) in seagrass meadows are highly variable both spatially and temporally, making it difficult to extrapolate this strategy to areas where information is lacking. In this study, C org stocks and C org accumulation were determined at 11 eelgrass meadows across New England, representing a range of eutrophication and exposure conditions. In addition, the environmental factors and structural characteristics of meadows related to variation in C org stocks were identified. The objectives were accomplished by assessing stable isotopes of δ 13 C and δ 15 N as well as %C and %N in plant tissues and sediments, measuring grain size and 210 Pb of sediment cores, and through assessing site exposure. Variability in C org stocks in seagrass meadows is well predicted using commonly measured environmental variables such as grain size distribution. This study allows incorporation of data and insights for the northwest Atlantic, where few studies on carbon sequestration by seagrasses have been conducted.

High silicon concentrations in grasses are linked to environmental conditions and not associated with C 4 photosynthesis - William H. Brightly; Sue E. Hartley; Colin P. Osborne; Kimberley J. Simpson; Caroline A. E. Strömberg (Global Change Biology, 2020)
The uptake and deposition of silicon (Si) as silica phytoliths is common among land plants and is associated with a variety of functions. Among these, herbivore defense has received significant attention, particularly with regard to grasses and grasslands. Grasses are well known for their high silica content, a trait which has important implications ranging from defense to global Si cycling. Here, we test the classic hypothesis that C 4 grasses evolved stronger mechanical defenses than C 3 grasses through increased phytolith deposition, in response to extensive ungulate herbivory (“C 4 ‐grazer hypothesis”). Despite mixed support, this hypothesis has received broad attention, even outside the realm of plant biology. Because C 3 and C 4 grasses typically dominate in different climates, with the latter more abundant in hot, dry regions, we also investigated the effects of water availability and temperature on Si deposition. We compiled a large dataset of grasses grown under controlled environmental conditions. Using phylogenetically informed generalized linear mixed models and character evolution models, we evaluated whether photosynthetic pathway or growth condition influenced Si concentration. We found that C 4 grasses did not show consistently elevated Si concentrations compared with C 3 grasses. High temperature treatments were associated with increased concentration, especially in taxa adapted to warm regions. Although the effect was less pronounced, reduced water treatment also promoted silica deposition, with slightly stronger response in dry habitat species. The evidence presented here rejects the “C 4 ‐grazer hypothesis.” Instead, we propose that the tendency for C 4 grasses to outcompete C 3 species under hot, dry conditions explains previous observations supporting this hypothesis. These findings also suggest a mechanism via which anthropogenic climate change may influence silica deposition in grasses and, by extension, alter the important ecological and geochemical processes it affects.

Cetuximab Exhibits Sex Differences in Lymphatic Exposure after Intravenous Administration in Rats in the Absence of Differences in Plasma Exposure - Esther Kuilamu; Christopher Subasic; Gary J Cowin; Fiona Simpson; Rodney F Minchin; Lisa M Kaminskas (Pharmaceutical Research, 2020)

SoilTemp: A global database of near‐surface temperature - Jonas J. Lembrechts; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Martin Kopecký; Jonathan Lenoir; Miska Luoto; Ilya M. D. Maclean; Olivier Roupsard; Eduardo Fuentes‐Lillo; Rafael A. García; Loïc Pellissier; et al. (Global Change Biology, 2020)
Current analyses and predictions of spatially explicit patterns and processes in ecology most often rely on climate data interpolated from standardized weather stations. This interpolated climate data represents long‐term average thermal conditions at coarse spatial resolutions only. Hence, many climate‐forcing factors that operate at fine spatiotemporal resolutions are overlooked. This is particularly important in relation to effects of observation height (e.g. vegetation, snow and soil characteristics) and in habitats varying in their exposure to radiation, moisture and wind (e.g. topography, radiative forcing or cold‐air pooling). Since organisms living close to the ground relate more strongly to these microclimatic conditions than to free‐air temperatures, microclimatic ground and near‐surface data are needed to provide realistic forecasts of the fate of such organisms under anthropogenic climate change, as well as of the functioning of the ecosystems they live in. To fill this critical gap, we highlight a call for temperature time series submissions to SoilTemp, a geospatial database initiative compiling soil and near‐surface temperature data from all over the world. Currently, this database contains time series from 7,538 temperature sensors from 51 countries across all key biomes. The database will pave the way toward an improved global understanding of microclimate and bridge the gap between the available climate data and the climate at fine spatiotemporal resolutions relevant to most organisms and ecosystem processes.

A Citizen Science State of the World’s Wetlands Survey - R. J. McInnes; N. C. Davidson; C. P. Rostron; M. Simpson; C. M. Finlayson (Wetlands, 2020)

Evidence for substantial acetate presence in cutaneous earthworm mucus - Ganna S. Shutenko; Brian P. Kelleher; André J. Simpson; Ronald Soong; Yalda Liaghati Mobarhan; Olaf Schmidt (Journal of Soils and Sediments, 2020)

Genomic sequencing highlights the diverse molecular causes of Perrault syndrome: a peroxisomal disorder (PEX6), metabolic disorders (CLPP, GGPS1), and mtDNA maintenance/translation disorders (LARS2, TFAM) - Elena J. Tucker; Rocio Rius; Sylvie Jaillard; Katrina Bell; Phillipa J. Lamont; André Travessa; Juliette Dupont; Lurdes Sampaio; Jérôme Dulon; Sandrine Vuillaumier-Barrot; Sandra Whalen; Arnaud Isapof; et al. (Human Genetics, 2020)

Development of fly tolerance to consuming a high-protein diet requires physiological, metabolic and transcriptional changes - Ihor S. Yurkevych; Lindsey J. Gray; Dmytro V. Gospodaryov; Nadia I. Burdylyuk; Kenneth B. Storey; Stephen J. Simpson; Oleh Lushchak (Biogerontology, 2020)

Small-scale spatial structure influences large-scale invasion rates - Michael J. Plank; Matthew J. Simpson; Rachelle N. Binny (Theoretical Ecology, 2020)

Architectural Geoheritage, Engaging the Observer and the Geotourism Potential of the Lighthouse Hotel Rock Wall, Bunbury, Western Australia - Samantha J. Richards; David Newsome; Greg Simpson (Geoheritage, 2020)

Root proliferation and phosphorus acquisition in response to stratification of soil phosphorus by two contrasting Trifolium subterraneum cultivars - Jonathan W. McLachlan; Richard J. Flavel; Chris N. Guppy; Richard J. Simpson; Rebecca E. Haling (Plant and Soil, 2020)

Clifford Charles Townsend (1926 – 2018) - B. Townsend; P. J. Cribb; D. A. Simpson (Kew Bulletin, 2020)

Energetic Carrying Capacity of Submersed Aquatic Vegetation in Semi-Permanent Wetlands Important to Waterfowl in the Upper Midwest - Margaret C. Gross; Joseph D. Lancaster; John W. Simpson; Brendan T. Shirkey; Sarah E. McClain; Christopher N. Jacques; J. Brian Davis; Heath M. Hagy (Wetlands, 2020)

Root proliferation in response to P stress and space: implications for the study of root acclimation to low P supply and P acquisition efficiency - Jonathan W. McLachlan; Rebecca E. Haling; Richard J. Simpson; Richard J. Flavel; Chris N. Guppy (Plant and Soil, 2020)

Quantifying Soft Tissue Artefacts and Imaging Variability in Motion Capture of the Fingers - C. D. Metcalf; C. Phillips; A. Forrester; J. Glodowski; K. Simpson; C. Everitt; A. Darekar; L. King; D. Warwick; A. S. Dickinson (Annals of Biomedical Engineering, 2020)
This study assessed the accuracy of marker-based kinematic analysis of the fingers, considering soft tissue artefacts (STA) and marker imaging uncertainty. We collected CT images of the hand from healthy volunteers with fingers in full extension, mid- and full-flexion, including motion capture markers. Bones and markers were segmented and meshed. The bone meshes for each volunteer’s scans were aligned using the proximal phalanx to study the proximal interphalangeal joint (PIP), and using the middle phalanx to study the distal interphalangeal joint (DIP). The angle changes between positions were extracted. The HAWK protocol was used to calculate PIP and DIP joint flexion angles in each position based on the marker centroids. Finally the marker locations were ‘corrected’ relative to the underlying bones, and the flexion angles recalculated. Static and dynamic marker imaging uncertainty was evaluated using a wand. A strong positive correlation was observed between marker- and CT-based joint angle changes with 0.980 and 0.892 regression slopes for PIP and DIP, respectively, and Root Mean Squared Errors below 4°. Notably for the PIP joint, correlation was worsened by STA correction. The 95% imaging uncertainty interval was

Fiber-specific and whole-muscle LRP130 expression in rested, exercised, and fasted human skeletal muscle - Hashim Islam; Andrew Ma; Alessandra Amato; Alexanne Cuillerier; Yan Burelle; Craig A. Simpson; Joe Quadrilatero; Brendon J. Gurd (Pflügers Archiv - European Journal of Physiology, 2020)

Soil phosphorus pools with addition of fertiliser phosphorus in a long-term grazing experiment - Timothy I. McLaren; Ronald J. Smernik; Michael J. McLaughlin; Therese M. McBeath; Malcolm R. McCaskill; Fiona A. Robertson; Richard J. Simpson (Nutrient Cycling in Agroecosystems, 2020)

The impact of acute and chronic exercise on Nrf2 expression in relation to markers of mitochondrial biogenesis in human skeletal muscle - Hashim Islam; Jacob T. Bonafiglia; Patrick C. Turnbull; Craig A. Simpson; Christopher G. R. Perry; Brendon J. Gurd (European Journal of Applied Physiology, 2020)

Characterization of Phase Transformations for Amorphous Solid Dispersions of a Weakly Basic Drug upon Dissolution in Biorelevant Media - Ahmed Elkhabaz; Sreya Sarkar; Garth J. Simpson; Lynne S. Taylor (Pharmaceutical Research, 2019)

Climate warming alters subsoil but not topsoil carbon dynamics in alpine grassland - Juan Jia; Zhenjiao Cao; Chengzhu Liu; Zhenhua Zhang; Li Lin; Yiyun Wang; Negar Haghipour; Lukas Wacker; Hongyan Bao; Thorston Dittmar; Myrna J. Simpson; Huan Yang; et al. (Global Change Biology, 2019)
Subsoil contains more than half of soil organic carbon (SOC) globally and is conventionally assumed to be relatively unresponsive to warming compared to the topsoil. Here, we show substantial changes in carbon allocation and dynamics of the subsoil but not topsoil in the Qinghai‐Tibetan alpine grasslands over 5 years of warming. Specifically, warming enhanced the accumulation of newly synthesized ( 14 C‐enriched) carbon in the subsoil slow‐cycling pool (silt‐clay fraction) but promoted the decomposition of plant‐derived lignin in the fast‐cycling pool (macroaggregates). These changes mirrored an accumulation of lipids and sugars at the expense of lignin in the warmed bulk subsoil, likely associated with shortened soil freezing period and a deepening root system. As warming is accompanied by deepening roots in a wide range of ecosystems, root‐driven accrual of slow‐cycling pool may represent an important and overlooked mechanism for a potential long‐term carbon sink at depth. Moreover, given the contrasting sensitivity of SOC dynamics at varied depths, warming studies focusing only on surface soils may vastly misrepresent shifts in ecosystem carbon storage under climate change.

Perspectives on in situ Sensors for Ocean Acidification Research - Akash R. Sastri; James R. Christian; Eric P. Achterberg; Dariia Atamanchuk; Justin J. H. Buck; Philip Bresnahan; Patrick J. Duke; Wiley Evans; Stephen F. Gonski; Bruce Johnson; S. Kim Juniper; Steve Mihaly; et al. (Frontiers in Marine Science, 2019)

Evolving and Sustaining Ocean Best Practices and Standards for the Next Decade - Jay Pearlman; Mark Bushnell; Laurent Coppola; Johannes Karstensen; Pier Luigi Buttigieg; Francoise Pearlman; Pauline Simpson; Michele Barbier; Frank E. Muller-Karger; Cristian Munoz-Mas; Peter Pissierssens; Cyndy Chandler; et al. (Frontiers in Marine Science, 2019)

Inbreeding depression causes reduced fecundity in Golden Retrievers - Erin T. Chu; Missy J. Simpson; Kelly Diehl; Rodney L. Page; Aaron J. Sams; Adam R. Boyko (Mammalian Genome, 2019)

Comparison of metabolomic responses of earthworms to sub-lethal imidacloprid exposure in contact and soil tests - Vivek D. Dani; Brian P. Lankadurai; Edward G. Nagato; André J. Simpson; Myrna J. Simpson (Environmental Science and Pollution Research, 2019)

Cerebrospinal Fluid Ceruloplasmin, Haptoglobin, and Vascular Endothelial Growth Factor Are Associated with Neurocognitive Impairment in Adults with HIV Infection - A. R. Kallianpur; H. Gittleman; S. Letendre; R. Ellis; J. S. Barnholtz-Sloan; W. S. Bush; R. Heaton; D. C. Samuels; D. R. Franklin; D. Rosario-Cookson; D. B. Clifford; A. C. Collier; et al. (Molecular Neurobiology, 2019)

Metabolomic responses to pre-chlorinated and final effluent wastewater with the addition of a sub-lethal persistent contaminant in Daphnia magna - Nicole D. Wagner; Paul A. Helm; André J. Simpson; Myrna J. Simpson (Environmental Science and Pollution Research, 2019)

White matter damage, neuroinflammation, and neuronal integrity in HAND - Aljoharah Alakkas; Ronald J. Ellis; Caitlin Wei-Ming Watson; Anya Umlauf; Robert K. Heaton; Scott Letendre; Ann Collier; Christina Marra; David B. Clifford; Benjamin Gelman; Ned Sacktor; Susan Morgello; et al. (Journal of NeuroVirology, 2019)

Seasonality of pCO 2 in a hard‐water lake of the northern Great Plains: The legacy effects of climate and limnological conditions over 36 years - Kerri Finlay; Richard J. Vogt; Gavin L. Simpson; Peter R. Leavitt (Limnology and Oceanography, 2019)
Biogeochemical processes are active year‐round in ice‐covered lakes, such that processes in one season can affect limnological conditions in subsequent seasons. However, the extent and nature of these legacy effects are poorly understood, particularly for the CO 2 content of lakes and when considering gas exchange with the atmosphere. Here, we used a unique 36‐yr dataset of weekly limnological measurements of Buffalo Pound Lake in the northern Great Plains to assess seasonal changes in CO 2 concentration and flux and determine how dependent lake pCO 2 is on limnological conditions of previous seasons. We found that the lake was a net source of CO 2 to the atmosphere (mean 18.5 ± 7.4 mol CO 2 m −2 yr −1 ), with spring potentially accounting for the majority (~ 64% ± 20%) of CO 2 efflux, assuming ice in spring was permeable to gas exchange (32.9% ± 19.8% if not). Analysis with generalized additive models (GAMs) demonstrated that current and antecedent seasonal conditions combined to explain 72.6% of deviance in spring pCO 2 , but that the strength of model predictions and the importance of antecedent conditions diminished in GAMs of summer (43.6%) and fall (23.3%) CO 2 levels. This research suggests that pCO 2 is regulated by a combination of coeval and historical environmental conditions and shows that quantification of seasonal and annual fluxes requires a mechanistic understanding of the legacy effects of preceding time intervals.

Differential stimulation and suppression of phytoplankton growth by ammonium enrichment in eutrophic hardwater lakes over 16 years - Vanessa J. Swarbrick; Gavin L. Simpson; Patricia M. Glibert; Peter R. Leavitt (Limnology and Oceanography, 2019)
Previous research suggests that fertilization of surface waters with chemically reduced nitrogen (N), including ammonium (NH 4 + ), may either enhance or suppress phytoplankton growth. To identify the factors influencing the net effect of NH 4 + , we fertilized natural phytoplankton assemblages from two eutrophic hardwater lakes with growth‐saturating concentrations of NH 4 Cl in 241 incubation experiments conducted biweekly May–August during 1996–2011. Phytoplankton biomass (as chlorophyll a ) was significantly ( p 4 + increased with abundance of diatoms, cryptophytes, and unicellular cyanobacteria, particularly when water temperatures and soluble reactive phosphorus (SRP) concentrations were low. In contrast, phytoplankton was often stimulated by NH 4 + when chlorophytes and non‐N 2 ‐fixing cyanobacteria were abundant, and temperatures and SRP concentrations were high. Progressive intensification of NH 4 + effects over 16 yr reflects changes in both spring (cooler water, increased diatoms and cryptophytes) and summer lake conditions (more chlorophytes, earlier cyanobacteria blooms), suggesting that the seasonal effects of NH 4 + will vary with future climate change and modes of N enrichment.

Changes in nutritional values induced by butachlor in juvenile diploid and triploid Clarias gariepinus - A. Karami; S. Karbalaei; M. Ebrahimi; A. Ismail; M. F. Jahromi; S. L. Simpson; P. Eghtesadi Araghi; R. P. Lim; J. B. Liang (International Journal of Environmental Science and Technology, 2018)

Identification of powdery mildew resistance QTL in strawberry (Fragaria × ananassa) - Helen M. Cockerton; Robert J. Vickerstaff; Amanda Karlström; Fiona Wilson; Maria Sobczyk; Joe Q. He; Daniel J. Sargent; Andy J. Passey; Kirsty J. McLeary; Katalin Pakozdi; Nicola Harrison; Maria Lumbreras-Martinez; et al. (Theoretical and Applied Genetics, 2018)

Regional variability in the atmospheric nitrogen deposition signal and its transfer to the sediment record in Greenland lakes - N. J. Anderson; C. J. Curtis; E. J. Whiteford; V. J. Jones; S. McGowan; G. L. Simpson; J. Kaiser (Limnology and Oceanography, 2018)
Disruption of the nitrogen cycle is a major component of global environmental change. δ 15 N in lake sediments is increasingly used as a measure of reactive nitrogen input but problematically, the characteristic depleted δ 15 N signal is not recorded at all sites. We used a regionally replicated sampling strategy along a precipitation and N‐deposition gradient in SW Greenland to assess the factors determining the strength of δ 15 N signal in lake sediment cores. Analyses of snowpack N and δ 15 N‐NO 3 and water chemistry were coupled with bulk sediment δ 15 N. Study sites cover a gradient of snowpack δ 15 N (ice sheet: −6‰; coast 10‰), atmospheric N deposition (ice sheet margin: ∼ 0.2 kg ha −1 yr −1 ; coast: 0.4 kg ha −1 yr −1 ) and limnology. Three 210 Pb‐dated sediment cores from coastal lakes showed a decline in δ 15 N of ca. 1‰ from ∼ 1860, reflecting the strongly depleted δ 15 N of snowpack N, lower in‐lake total N (TN) concentration (∼ 300 μ g N L −1 ) and a higher TN‐load. Coastal lakes have 3.7–7.1× more snowpack input of nitrate than inland sites, while for total deposition the values are 1.7–3.6× greater for lake and whole catchment deposition. At inland sites and lakes close to the ice‐sheet margin, a lower atmospheric N deposition rate and larger in‐lake TN pool resulted in greater reliance on N‐fixation and recycling (mean sediment δ 15 N is 0.5–2.5‰ in most inland lakes; n = 6). The primary control of the transfer of the atmospheric δ 15 N deposition signal to lake sediments is the magnitude of external N inputs relative to the in‐lake N‐pool.

It's not just what you have, but how you use it: solar‐positional and behavioural effects on hummingbird colour appearance during courtship - Richard K. Simpson; Kevin J. McGraw (Ecology Letters, 2018)
Animals exhibit a diversity of colours that can play key roles in mating interactions. However, we presently lack an understanding of the relative importance of the environment, behaviour and natural reflective properties of colourful ornaments in shaping an individual's colour appearance during mating displays. We investigated interactions among structurally based plumage, display environments and courtship shuttle displays of male Costa's hummingbirds ( Calypte costae ) to test how these elements may differentially contribute to colour appearance during shuttles. Male position relative to the sun was the strongest predictor of colour appearance, with shuttle behaviours and feather reflectance playing smaller roles. Furthermore, male solar orientation and shuttling behaviour (e.g. shuttle width) were repeatable among displays, whereas male colour appearance mostly was not. These results emphasise the contributions of behaviour and environment to colour‐signalling and suggest that relying on reflectance measurements of colourful ornaments alone provides an incomplete picture of ecologically relevant visual phenotypes of displaying animals.

Ozone pollution will compromise efforts to increase global wheat production - Gina Mills; Katrina Sharps; David Simpson; Håkan Pleijel; Malin Broberg; Johan Uddling; Fernando Jaramillo; William J Davies; Frank Dentener; Maurits Van den Berg; Madhoolika Agrawal; Shahibhushan B. Agrawal; et al. (Global Change Biology, 2018)
Introduction of high‐performing crop cultivars and crop/soil water management practices that increase the stomatal uptake of carbon dioxide and photosynthesis will be instrumental in realizing the United Nations Sustainable Development Goal ( SDG ) of achieving food security. To date, however, global assessments of how to increase crop yield have failed to consider the negative effects of tropospheric ozone, a gaseous pollutant that enters the leaf stomatal pores of plants along with carbon dioxide, and is increasing in concentration globally, particularly in rapidly developing countries. Earlier studies have simply estimated that the largest effects are in the areas with the highest ozone concentrations. Using a modelling method that accounts for the effects of soil moisture deficit and meteorological factors on the stomatal uptake of ozone, we show for the first time that ozone impacts on wheat yield are particularly large in humid rain‐fed and irrigated areas of major wheat‐producing countries (e.g. United States, France, India, China and Russia). Averaged over 2010–2012, we estimate that ozone reduces wheat yields by a mean 9.9% in the northern hemisphere and 6.2% in the southern hemisphere, corresponding to some 85 Tg (million tonnes) of lost grain. Total production losses in developing countries receiving Official Development Assistance are 50% higher than those in developed countries, potentially reducing the possibility of achieving UN SDG 2. Crucially, our analysis shows that ozone could reduce the potential yield benefits of increasing irrigation usage in response to climate change because added irrigation increases the uptake and subsequent negative effects of the pollutant. We show that mitigation of air pollution in a changing climate could play a vital role in achieving the above‐mentioned UN SDG , while also contributing to other SDG s related to human health and well‐being, ecosystems and climate change.

Environmental exposure and parental collection does not affect detection or semi-quantitative load assessment of bacteria in nasal swab specimens from children - Nada Townsi; Shannon J. Simpson; Chisha T. Sikazwe; Glenys R. Chidlow; Graham L. Hall; J. Jane Pillow; Andrew C. Wilson; David W. Smith; Ingrid A. Laing (Infectious Diseases, 2018)

Safety, tolerability and pharmacokinetics of GSK3008348, a novel integrin αvβ6 inhibitor, in healthy participants - Charlotte H. Maden; David Fairman; Michelle Chalker; Maria J. Costa; William A. Fahy; Nadia Garman; Pauline T. Lukey; Tim Mant; Simon Parry; Juliet K. Simpson; Robert J. Slack; Stuart Kendrick; et al. (European Journal of Clinical Pharmacology, 2018)

Effects of sprint interval training on ectopic lipids and tissue-specific insulin sensitivity in men with non-alcoholic fatty liver disease - Jack A. Sargeant; Stephen Bawden; Guruprasad P. Aithal; Elizabeth J. Simpson; Ian A. Macdonald; Mark C. Turner; Jessica Cegielski; Kenneth Smith; James L. Dorling; Penny A. Gowland; Myra A. Nimmo; James A. King (European Journal of Applied Physiology, 2018)

Biological activity and LC-MS/MS profiling of extracts from the Australian medicinal plant Acacia ligulata (Fabaceae) - Diana Jæger; Bradley S. Simpson; Chi P. Ndi; Anna K. Jäger; Christoph Crocoll; Birger Lindberg Møller; Philip Weinstein; Susan J. Semple (Natural Product Research, 2018)

Differences in nutrient foraging among Trifolium subterraneum cultivars deliver improved P-acquisition efficiency - Rebecca E. Haling; Lawrie K. Brown; Adam Stefanski; Daniel R. Kidd; Megan H. Ryan; Graeme A. Sandral; Timothy S. George; Hans Lambers; Richard J. Simpson (Plant and Soil, 2018)

The carboxylate composition of rhizosheath and root exudates from twelve species of grassland and crop legumes with special reference to the occurrence of citramalate - Daniel R. Kidd; Megan H. Ryan; Dorothee Hahne; Rebecca E. Haling; Hans Lambers; Graeme A. Sandral; Richard J. Simpson; Gregory R. Cawthray (Plant and Soil, 2018)

A cross correlation method for chemical profiles in minerals, with an application to zircons of the Kilgore Tuff (USA) - L. C. Probst; T. E. Sheldrake; M. J. Gander; G. Wallace; G. Simpson; L. Caricchi (Contributions to Mineralogy and Petrology, 2018)

Fishes in a changing world: learning from the past to promote sustainability of fish populations - T. A. C. Gordon; H. R. Harding; F. K. Clever; I. K. Davidson; W. Davison; D. W. Montgomery; R. C. Weatherhead; F. M. Windsor; J. D. Armstrong; A. Bardonnet; E. Bergman; J. R. Britton; et al. (Journal of Fish Biology, 2018)
Populations of fishes provide valuable services for billions of people, but face diverse and interacting threats that jeopardize their sustainability. Human population growth and intensifying resource use for food, water, energy and goods are compromising fish populations through a variety of mechanisms, including overfishing, habitat degradation and declines in water quality. The important challenges raised by these issues have been recognized and have led to considerable advances over past decades in managing and mitigating threats to fishes worldwide. In this review, we identify the major threats faced by fish populations alongside recent advances that are helping to address these issues. There are very significant efforts worldwide directed towards ensuring a sustainable future for the world's fishes and fisheries and those who rely on them. Although considerable challenges remain, by drawing attention to successful mitigation of threats to fish and fisheries we hope to provide the encouragement and direction that will allow these challenges to be overcome in the future.

Understanding fish populations - S. D. Simpson; I. Barber; I. J. Winfield (Journal of Fish Biology, 2018)

Diet has independent effects on the pace and shape of aging in Drosophila melanogaster - C. Ruth Archer; Ugofilippo Basellini; John Hunt; Stephen J. Simpson; Kwang Pum Lee; Annette Baudisch (Biogerontology, 2018)

Large‐scale bleaching of corals on the Great Barrier Reef - T. P. Hughes; J. T. Kerry; T. Simpson (Ecology, 2018)
In 2015–2016, record temperatures triggered a pan‐tropical episode of coral bleaching. In the southern hemisphere summer of March–April 2016, we used aerial surveys to measure the level of bleaching on 1,156 individual reefs throughout the 2,300 km length of the Great Barrier Reef, the world's largest coral reef system. The accuracy of the aerial scores was ground‐truthed with detailed underwater surveys of bleaching at 260 sites (104 reefs), allowing us to compare aerial and underwater bleaching data with satellite‐derived temperatures and with associated model predictions of bleaching. The severity of bleaching on individual reefs in 2016 was tightly correlated with the level of local heat exposure: the southernmost region of the Great Barrier Reef escaped with only minor bleaching because summer temperatures there were close to average. Gradients in nutrients and turbidity from inshore to offshore across the Great Barrier Reef had minimal effect on the severity of bleaching. Similarly, bleaching was equally severe on reefs that are open or closed to fishing, once the level of satellite‐derived heat exposure was accounted for. The level of post‐bleaching mortality, measured underwater after 7–8 months, was tightly correlated with the aerial scores measured at the peak of bleaching. Similarly, reefs with a high aerial bleaching score also experienced major shifts in species composition due to extensive mortality of heat‐sensitive species. Reefs with low bleaching scores did not change in composition, and some showed minor increases in coral cover. Two earlier mass bleaching events occurred on the Great Barrier Reef in 1998 and 2002, that were less severe than 2016. In 2016, 60% of corals affected) was four times higher in 2016. The geographic footprint of each of the three events is distinctive, and matches satellite‐derived sea surface temperature patterns. Our aerial surveys indicate that past exposure to bleaching in 1998 and 2002 did not lessen the severity of bleaching in 2016. This data set of aerial bleaching scores provides a historical baseline for comparison with future bleaching events. No copyright restrictions apply to the use of this data set other than citing this publication.

Carbon Storages along a Climate Induced Coastal Wetland Gradient - L. T. Simpson; T. Z. Osborne; L. J. Duckett; I. C. Feller (Wetlands, 2017)

Unwrapping the rhizosheath - Jiayin Pang; Megan H. Ryan; Kadambot H. M. Siddique; Richard J. Simpson (Plant and Soil, 2017)

Localised hydrodynamics influence vulnerability of coral communities to environmental disturbances - George Shedrawi; James L. Falter; Kim J. Friedman; Ryan J. Lowe; Morgan S. Pratchett; Christopher J. Simpson; Conrad W. Speed; Shaun K. Wilson; Zhenlin Zhang (Coral Reefs, 2017)

Time Dependent Behaviour of Trabecular Bone at Multiple Load Levels - Shuqiao Xie; Krishnagoud Manda; Robert J. Wallace; Francesc Levrero-Florencio; A. Hamish R. W. Simpson; Pankaj Pankaj (Annals of Biomedical Engineering, 2017)

Belowground solutions to global challenges: special issue from the 9th symposium of the International Society of Root Research - Megan H. Ryan; Hong Liao; Richard J. Simpson (Plant and Soil, 2017)

Root morphology and its contribution to a large root system for phosphorus uptake by Rytidosperma species (wallaby grass) - Heidi A. Waddell; Richard J. Simpson; Megan H. Ryan; Hans Lambers; Denys L. Garden; Alan E. Richardson (Plant and Soil, 2017)

Root morphology acclimation to phosphorus supply by six cultivars of Trifolium subterraneum L - Robert P. Jeffery; Richard J. Simpson; Hans Lambers; Daniel R. Kidd; Megan H. Ryan (Plant and Soil, 2017)

Characterization of carbon monoxide, methane and nonmethane hydrocarbons in emerging cities of Saudi Arabia and Pakistan and in Singapore - Barbara Barletta; Isobel J. Simpson; Nicola J. Blake; Simone Meinardi; Louisa K. Emmons; Omar S. Aburizaiza; Azhar Siddique; Jahan Zeb; Liya E. Yu; Haider A. Khwaja; Muhammad A. Farrukh; Donald R. Blake (Journal of Atmospheric Chemistry, 2017)

Wetland Ecosystem Services and the Ramsar Convention: an Assessment of Needs - Robert J. McInnes; Matthew Simpson; Beatriz Lopez; Robbie Hawkins; Robert Shore (Wetlands, 2017)

Acute oxytocin improves memory and gaze following in male but not female nursery-reared infant macaques - Elizabeth A. Simpson; Annika Paukner; Valentina Sclafani; Stefano S. K. Kaburu; Stephen J. Suomi; Pier F. Ferrari (Psychopharmacology, 2017)

Evaluating the accuracy of self-report for the diagnosis of HIV-associated neurocognitive disorder (HAND): defining “symptomatic” versus “asymptomatic” HAND - Lisa C. Obermeit; Jessica Beltran; Kaitlin B. Casaletto; Donald R. Franklin; Scott Letendre; Ronald Ellis; Christine Fennema-Notestine; Florin Vaida; Ann C. Collier; Christina M. Marra; David Clifford; Benjamin Gelman; et al. (Journal of NeuroVirology, 2017)

Population distribution, host-switching, and chemical sensing in the symbiotic shrimp Lysmata pederseni: implications for its mating system in a changing reef seascape - J. Antonio Baeza; Rodrigo Guéron; Lunden Simpson; Louis J. Ambrosio (Coral Reefs, 2016)

Assessment of Damage and Adaptation Strategies for Structures and Infrastructure from Storm Surge and Sea Level Rise for a Coastal Community in Rhode Island, United States - Christopher Small; Tyler Blanpied; Alicia Kauffman; Conor O’Neil; Nicholas Proulx; Mathew Rajacich; Hailey Simpson; Jeffrey White; Malcolm Spaulding; Christopher Baxter; J. Swanson (Journal of Marine Science and Engineering, 2016)
This paper presents an evaluation of inundation, erosion, and wave damage for a coastal community in Rhode Island, USA. A methodology called the Coastal Environmental Risk Index (CERI) was used that incorporates levels of inundation including sea level rise, wave heights using STWAVE, and detailed information about individual structures from an E911 database. This information was input into damage functions developed by the U.S. Army Corps of Engineers following Hurricane Sandy. Damage from erosion was evaluated separately from local published erosion rates. Using CERI, two different adaptation strategies were evaluated that included a combination of dune restoration, protective berms, and a tide gate. A total of 151 out of 708 structures were estimated to be protected from inundation and wave action by the combined measures. More importantly, the use of CERI allowed for the assessment of the impact of different adaptation strategies on both individual structures and an entire community in a Geographical Information Systems (GIS) environment. This tool shows promise for use by coastal managers to assess damage and mitigate risk to coastal communities.

Growth and root dry matter allocation by pasture legumes and a grass with contrasting external critical phosphorus requirements - Rebecca E. Haling; Zongjian Yang; Natalie Shadwell; Richard A. Culvenor; Adam Stefanski; Megan H. Ryan; Graeme A. Sandral; Daniel R. Kidd; Hans Lambers; Richard J. Simpson (Plant and Soil, 2016)

Analysis of compound heterozygotes reveals that the mouse floxed Pax6 tm1Ued allele produces abnormal eye phenotypes - Natalie J. Dorà; Aaron J. F. Crookshanks; Karen K. Y. Leung; T. Ian Simpson; John O. Mason; David J. Price; John D. West (Transgenic Research, 2016)

Apolipoprotein E ε4 genotype status is not associated with neuroimaging outcomes in a large cohort of HIV+ individuals - Sarah A. Cooley; Robert H. Paul; Christine Fennema-Notestine; Erin E. Morgan; Florin Vaida; Qianqian Deng; Jie Ashley Chen; Scott Letendre; Ronald Ellis; David B. Clifford; Christina M. Marra; Ann C. Collier; et al. (Journal of NeuroVirology, 2016)

Persistent CSF but not plasma HIV RNA is associated with increased risk of new-onset moderate-to-severe depressive symptoms; a prospective cohort study - Edward R. Hammond; Rosa M. Crum; Glenn J. Treisman; Shruti H. Mehta; David B. Clifford; Ronald J. Ellis; Benjamin B. Gelman; Igor Grant; Scott L. Letendre; Christina M. Marra; Susan Morgello; David M. Simpson; et al. (Journal of NeuroVirology, 2016)

Soil–climate interactions explain variation in foliar, stem, root and reproductive traits across temperate forests - Angela H. Simpson; Sarah J. Richardson; Daniel C. Laughlin (Global Ecology and Biogeography, 2016)
Aim The individual effects of climate and soil properties on functional trait distributions have become increasingly clear with recent syntheses of large datasets. However, the distribution of traits in a given climate may depend on the fertility of the soil. Our aim was to quantify how soil–climate interactions explain community‐level variation in functional traits from every plant organ to improve predictions of plant community responses to environmental change. Location Temperate forests throughout New Zealand. Methods We measured traits of foliar, stem, root and reproductive tissue for 64 species and calculated abundance‐weighted mean trait values on 324 forest plots. Multiple linear regression was used to model the variation in each of the traits as functions of mean annual temperature (MAT), vapour pressure deficit (VPD), soil pH, soil total phosphorus (P) and their interactions. Results Soil–climate interactions explained significant variation in functional traits. For example, specific leaf area (SLA) was highest in high‐P soil within a wet and warm climate; however, strong interactions indicate that SLA was lowest in wet and warm climates in low‐P soil. Root tissue density was lowest in warm climates and high‐P soil, but it was high in warm climates and low‐P soil and in cold climates and high‐P soil. According to model predictions, the largest potential responses of vegetation to warming may occur in fertile and wet environments. Main conclusions Pervasive soil–climate interactions demonstrate that interpreting simple bivariate relationships between traits and climate must be done with caution because the adaptive value of traits in a given climate depends on the fertility of the soil. Predictions of vegetation responses to climate change will improve significantly by incorporating local‐scale soil properties into modelling frameworks. Rising global temperatures may shift community‐level trait values in opposite directions depending on whether the soil is fertile or infertile.

Using Functional Near Infrared Spectroscopy (fNIRS) to Study Dynamic Stereoscopic Depth Perception - Laura M. Ward; Gordon Morison; William A. Simpson; Anita J. Simmers; Uma Shahani (Brain Topography, 2016)

Rhizosphere carboxylates and morphological root traits in pasture legumes and grasses - Daniel R. Kidd; Megan H. Ryan; Rebecca E. Haling; Hans Lambers; Graeme A. Sandral; Zongjian Yang; Richard A. Culvenor; Gregory R. Cawthray; Adam Stefanski; Richard J. Simpson (Plant and Soil, 2016)

The fate of fertiliser P in soil under pasture and uptake by subterraneum clover – a field study using 33P-labelled single superphosphate - Timothy I. McLaren; Michael J. McLaughlin; Therese M. McBeath; Richard J. Simpson; Ronald J. Smernik; Christopher N. Guppy; Alan E. Richardson (Plant and Soil, 2016)

Molecular tools for bathing water assessment in Europe: Balancing social science research with a rapidly developing environmental science evidence-base - David M. Oliver; Nick D. Hanley; Melanie van Niekerk; David Kay; A. Louise Heathwaite; Sharyl J. M. Rabinovici; Julie L. Kinzelman; Lora E. Fleming; Jonathan Porter; Sabina Shaikh; Rob Fish; Sue Chilton; et al. (Ambio, 2016)

Enigmatic spheres from the Upper Triassic Lockatong Formation, Newark Basin of eastern Pennsylvania: evidence for microbial activity in marginal-lacustrine strandline deposits - Edward L. Simpson; David L. Fillmore; Michael J. Szajna; Emily Bogner; Margariete G. Malenda; Kelsey M. Livingston; Brian Hartline (Palaeobiodiversity and Palaeoenvironments, 2015)

Prioritization of knowledge needs for sustainable aquaculture: a national and global perspective - Aisla C Jones; Angela Mead; Michel J Kaiser; Melanie C V Austen; Alex W Adrian; Neil A Auchterlonie; Kenneth D Black; Lucy R Blow; Charlotte Bury; Janet H Brown; Gavin M Burnell; Elaine Connolly; et al. (Fish and Fisheries, 2015)
Aquaculture is currently the fastest expanding global animal food production sector and is a key future contributor to food security. An increase in food security will be dependent upon the development and improvement of sustainable practices. A prioritization exercise was undertaken, focusing on the future knowledge needs to underpin UK sustainable aquaculture (both domestic and imported products) using a ‘task force’ group of 36 ‘practitioners’ and 12 ‘research scientists’ who have an active interest in sustainable aquaculture. A long list of 264 knowledge needs related to sustainable aquaculture was developed in conjunction with the task force. The long list was further refined through a three stage process of voting and scoring, including discussions of each knowledge need. The top 25 knowledge needs are presented, as scored separately by ‘practitioners’ or ‘research scientists’. There was similar agreement in priorities identified by these two groups. The priority knowledge needs will provide guidance to structure ongoing work to make science accessible to practitioners and help to prioritize future science policy needs and funding. The process of knowledge exchange, and the mechanisms by which this can be achieved, effectively emerged as the top priority for sustainable aquaculture. Viable alternatives to wild fish‐based aquaculture feeds, resource constraints that will potentially limit expansion of aquaculture, sustainable offshore aquaculture and the treatment of sea lice also emerged as strong priorities. Although the exercise was focused on UK needs for sustainable aquaculture, many of the emergent issues are considered to have global application.

Visuo-Vestibular Information Processing by Unipolar Brush Cells in the Rabbit Flocculus - Robert A. Hensbroek; Tom J. H. Ruigrok; Boeke J. van Beugen; Jun Maruta; John I. Simpson (The Cerebellum, 2015)

CSF biomarkers of monocyte activation and chemotaxis correlate with magnetic resonance spectroscopy metabolites during chronic HIV disease - Albert M. Anderson; Christine Fennema-Notestine; Anya Umlauf; Michael J. Taylor; David B. Clifford; Christina M. Marra; Ann C. Collier; Benjamin B. Gelman; Justin C. McArthur; J. Allen McCutchan; David M. Simpson; Susan Morgello; et al. (Journal of NeuroVirology, 2015)

Chemical characterization and in vitro toxicity of diesel exhaust particulate matter generated under varying conditions - Julie Richman Fox; David P. Cox; Bertram E. Drury; Timothy R. Gould; Terrance J. Kavanagh; Michael H. Paulsen; Lianne Sheppard; Christopher D. Simpson; James A. Stewart; Timothy V. Larson; Joel D. Kaufman (Air Quality, Atmosphere & Health, 2015)

Long‐term changes in organic matter and mercury transport to lakes in the sporadic discontinuous permafrost zone related to peat subsidence - Jennifer B. Korosi; Jamylynn McDonald; Kristen A. Coleman; Michael J. Palmer; John P. Smol; Myrna J. Simpson; Jules M. Blais (Limnology and Oceanography, 2015)
Permafrost‐supported peatlands near the southern limit of permafrost are experiencing dramatic landscape changes as a result of recent climate warming, which have the potential to impact aquatic ecosystems through changes in terrestrial run‐off. Our objectives were to determine how terrestrial organic matter inputs to aquatic ecosystems in the southern Northwest Territories (Canada) changed as a result of peat subsidence, and whether terrestrial organic matter can be linked to sedimentary mercury. To accomplish this, we analyzed lipid biomarkers, lignin‐derived phenols, and other geochemical proxies in sediment cores from two lakes (KAK‐1 and TAH‐7) affected by recent peat subsidence. Both lakes experienced substantial shifts in organic matter proxies through time, but the trajectory of change differed, reflecting local heterogeneity in hydrological setting and other environmental factors. In KAK‐1, recent peat subsidence corresponded to a decrease in lignin‐derived phenol yield, increased inferred lignin oxidation, and δ 15 N depletion. In TAH‐7, peat subsidence was likely initiated by a local forest fire, and resulted in an increase in the n ‐alkanol ratio C 30 /(C 30 + C 28 ) (consistent with a warmer, wetter climate), lignin‐derived phenol yield (mainly syringyls), and δ 13 C depletion. In TAH‐7, total mercury inputs were positively correlated to terrestrial carbon inputs, suggesting allochthonous carbon is an important vector for mercury transport to the lake. In both lakes, an increase in the C 23 /(C 23 + C 29 ) n ‐alkane ratio was observed and suggests increased organic matter input from Sphagnum mosses. Our results demonstrate how terrestrial landscape changes occurring as a result of peat subsidence can influence carbon accumulation in aquatic ecosystems in discontinuous permafrost zones.

Profiling the Role of Deacylation-Reacylation in the Lymphatic Transport of a Triglyceride-Mimetic Prodrug - Sifei Han; Luojuan Hu; Tim Quach; Jamie S. Simpson; Natalie L. Trevaskis; Christopher J. H. Porter (Pharmaceutical Research, 2015)

Fitness level impacts salivary antimicrobial protein responses to a single bout of cycling exercise - Hawley Kunz; Nicolette C. Bishop; Guillaume Spielmann; Mira Pistillo; Justin Reed; Teja Ograjsek; Yoonjung Park; Satish K. Mehta; Duane L. Pierson; Richard J. Simpson (European Journal of Applied Physiology, 2015)

Nutritional ecology beyond the individual: a conceptual framework for integrating nutrition and social interactions - Mathieu Lihoreau; Camille Buhl; Michael A. Charleston; Gregory A. Sword; David Raubenheimer; Stephen J. Simpson (Ecology Letters, 2015)
Over recent years, modelling approaches from nutritional ecology (known as Nutritional Geometry) have been increasingly used to describe how animals and some other organisms select foods and eat them in appropriate amounts in order to maintain a balanced nutritional state maximising fitness. These nutritional strategies profoundly affect the physiology, behaviour and performance of individuals, which in turn impact their social interactions within groups and societies. Here, we present a conceptual framework to study the role of nutrition as a major ecological factor influencing the development and maintenance of social life. We first illustrate some of the mechanisms by which nutritional differences among individuals mediate social interactions in a broad range of species and ecological contexts. We then explain how studying individual‐ and collective‐level nutrition in a common conceptual framework derived from Nutritional Geometry can bring new fundamental insights into the mechanisms and evolution of social interactions, using a combination of simulation models and manipulative experiments.

Modeling spatiotemporal dynamics of outbreaking species: influence of environment and migration in a locust - Sophie Veran; Stephen J. Simpson; Gregory A. Sword; Edward Deveson; Sylvain Piry; James E. Hines; Karine Berthier (Ecology, 2015)
Many pest species exhibit huge fluctuations in population abundance. Understanding their large‐scale and long‐term dynamics is necessary to develop effective control and management strategies. Occupancy models represent a promising approach to unravel interactions between environmental factors and spatiotemporal dynamics of outbreaking populations. Here, we investigated population dynamics of the Australian plague locust, Chortoicetes terminifera , using density data collected between 1988 and 2010 by the Australian Plague Locust Commission over more than 3 million km 2 in eastern Australia. We applied multistate and autologistic multi‐season occupancy models to test competing hypotheses about environmental and demographic processes affecting the large‐scale dynamics of the Australian plague locust. We found that rainfall and land cover predictors best explained the spatial variability in outbreak probability across eastern Australia. Outbreaks are more likely to occur in temperate than tropical regions, with a faster and more continuous response to rainfall in desert than in agricultural areas. Our results also support the hypothesis that migration tends to propagate outbreaks only locally (over distances lower than 400 km) rather than across climatic regions. Our study suggests that locust outbreak forecasting and management systems could be improved by implementing key environmental factors and migration in hierarchical spatial models. Finally, our modeling framework can be seen as a step towards bridging the gap between mechanistic and more phenomenological models in the spatial analysis of fluctuating populations.

Genome-wide association study for refractive astigmatism reveals genetic co-determination with spherical equivalent refractive error: the CREAM consortium - Qing Li; Robert Wojciechowski; Claire L. Simpson; Pirro G. Hysi; Virginie J. M. Verhoeven; Mohammad Kamran Ikram; René Höhn; Veronique Vitart; Alex W. Hewitt; Konrad Oexle; Kari-Matti Mäkelä; Stuart MacGregor; et al. (Human Genetics, 2015)

Brain morphometric correlates of metabolic variables in HIV: the CHARTER study - S. L. Archibald; J. A. McCutchan; C. Sanders; T. Wolfson; T. L. Jernigan; R. J. Ellis; B. M. Ances; A. C. Collier; J. C. McArthur; S. Morgello; D. M. Simpson; C. Marra; et al. (Journal of NeuroVirology, 2014)

Separate and combined effects of 21-day bed rest and hypoxic confinement on body composition - Tadej Debevec; Tarsi C. Bali; Elizabeth J. Simpson; Ian A. Macdonald; Ola Eiken; Igor B. Mekjavic (European Journal of Applied Physiology, 2014)

Predicted responses of arctic and alpine ecosystems to altered seasonality under climate change - Jessica G Ernakovich; Kelly A. Hopping; Aaron B. Berdanier; Rodney T. Simpson; Emily J. Kachergis; Heidi Steltzer; Matthew D. Wallenstein (Global Change Biology, 2014)
Global climate change is already having significant impacts on arctic and alpine ecosystems, and ongoing increases in temperature and altered precipitation patterns will affect the strong seasonal patterns that characterize these temperature‐limited systems. The length of the potential growing season in these tundra environments is increasing due to warmer temperatures and earlier spring snow melt. Here, we compare current and projected climate and ecological data from 20 Northern Hemisphere sites to identify how seasonal changes in the physical environment due to climate change will alter the seasonality of arctic and alpine ecosystems. We find that although arctic and alpine ecosystems appear similar under historical climate conditions, climate change will lead to divergent responses, particularly in the spring and fall shoulder seasons. As seasonality changes in the Arctic, plants will advance the timing of spring phenological events, which could increase plant nutrient uptake, production, and ecosystem carbon (C) gain. In alpine regions, photoperiod will constrain spring plant phenology, limiting the extent to which the growing season can lengthen, especially if decreased water availability from earlier snow melt and warmer summer temperatures lead to earlier senescence. The result could be a shorter growing season with decreased production and increased nutrient loss. These contrasting alpine and arctic ecosystem responses will have cascading effects on ecosystems, affecting community structure, biotic interactions, and biogeochemistry.

Statistical Power Calculations for Mixed Pharmacokinetic Study Designs Using a Population Approach - Frank Kloprogge; Julie A. Simpson; Nicholas P. J. Day; Nicholas J. White; Joel Tarning (The AAPS Journal, 2014)

Investigation of insecticide leaching from potted nursery stock and aquatic health benefits of bioretention cells receiving nursery runoff - Grant M. Graves; Jason R. Vogel; Jason B. Belden; Eric J. Rebek; Adam M. Simpson (Environmental Science and Pollution Research, 2014)

HIV-associated distal neuropathic pain is associated with smaller total cerebral cortical gray matter - John R. Keltner; Christine Fennema-Notestine; Florin Vaida; Dongzhe Wang; Donald R. Franklin; Robert H. Dworkin; Chelsea Sanders; J. Allen McCutchan; Sarah L. Archibald; David J. Miller; George Kesidis; Clint Cushman; et al. (Journal of NeuroVirology, 2014)

Detecting Extinction Risk from Climate Change by IUCN Red List Criteria - DAVID A. KEITH; MICHAEL MAHONY; HARRY HINES; JANE ELITH; TRACEY J. REGAN; JOHN B. BAUMGARTNER; DAVID HUNTER; GEOFFREY W. HEARD; NICOLA J. MITCHELL; KIRSTEN M. PARRIS; TRENT PENMAN; BEN SCHEELE; et al. (Conservation Biology, 2014)
Anthropogenic climate change is a key threat to global biodiversity. To inform strategic actions aimed at conserving biodiversity as climate changes, conservation planners need early warning of the risks faced by different species. The IUCN Red List criteria for threatened species are widely acknowledged as useful risk assessment tools for informing conservation under constraints imposed by limited data. However, doubts have been expressed about the ability of the criteria to detect risks imposed by potentially slow‐acting threats such as climate change, particularly because criteria addressing rates of population decline are assessed over time scales as short as 10 years. We used spatially explicit stochastic population models and dynamic species distribution models projected to future climates to determine how long before extinction a species would become eligible for listing as threatened based on the IUCN Red List criteria. We focused on a short‐lived frog species (Assa darlingtoni) chosen specifically to represent potential weaknesses in the criteria to allow detailed consideration of the analytical issues and to develop an approach for wider application. The criteria were more sensitive to climate change than previously anticipated; lead times between initial listing in a threatened category and predicted extinction varied from 40 to 80 years, depending on data availability. We attributed this sensitivity primarily to the ensemble properties of the criteria that assess contrasting symptoms of extinction risk. Nevertheless, we recommend the robustness of the criteria warrants further investigation across species with contrasting life histories and patterns of decline. The adequacy of these lead times for early warning depends on practicalities of environmental policy and management, bureaucratic or political inertia, and the anticipated species response times to management actions. Detección del Riesgo de Extinción a partir del Cambio Climático por medio del Criterio de la Lista Roja de la UICNKeith et al.

Prevalence of polypharmacy in a Scottish primary care population - R. A. Payne; A. J. Avery; M. Duerden; C. L. Saunders; C. R. Simpson; G. A. Abel (European Journal of Clinical Pharmacology, 2014)

Next generation sequencing-based molecular diagnosis of retinitis pigmentosa: identification of a novel genotype-phenotype correlation and clinical refinements - Feng Wang; Hui Wang; Han-Fang Tuan; Duy H. Nguyen; Vincent Sun; Vafa Keser; Sara J. Bowne; Lori S. Sullivan; Hongrong Luo; Ling Zhao; Xia Wang; Jacques E. Zaneveld; et al. (Human Genetics, 2014)

Estimates of twenty-first century sea-level changes for Norway - Matthew J. R. Simpson; Kristian Breili; Halfdan P. Kierulf (Climate Dynamics, 2014)

Differential niche dynamics among major marine invertebrate clades - Melanie J Hopkins; Carl Simpson; Wolfgang Kiessling (Ecology Letters, 2014)
The degree to which organisms retain their environmental preferences is of utmost importance in predicting their fate in a world of rapid climate change. Notably, marine invertebrates frequently show strong affinities for either carbonate or terrigenous clastic environments. This affinity is due to characteristics of the sediments as well as correlated environmental factors. We assessed the conservatism of substrate affinities of marine invertebrates over geological timescales, and found that niche conservatism is prevalent in the oceans, and largely determined by the strength of initial habitat preference. There is substantial variation in niche conservatism among major clades with corals and sponges being among the most conservative. Time‐series analysis suggests that niche conservatism is enhanced during times of elevated nutrient flux, whereas niche evolution tends to occur after mass extinctions. Niche evolution is not necessarily elevated in genera exhibiting higher turnover in species composition.

Erratum to: Direct measurement of roots in soil for single and mixed species using a quantitative DNA-based method - Rebecca E. Haling; Richard J. Simpson; Alan C. McKay; Diana Hartley; Hans Lambers; Kathy Ophel-Keller; Sue Wiebkin; Herdina; Ian T. Riley; Alan E. Richardson (Plant and Soil, 2013)

Latent cytomegalovirus infection and innate immune function following a 75 km cycling time trial - Emily C. P. LaVoy; David C. Nieman; Dru A. Henson; R. Andrew Shanely; Amy M. Knab; Lynn Cialdella-Kam; Richard J. Simpson (European Journal of Applied Physiology, 2013)

Increases in brain white matter abnormalities and subcortical gray matter are linked to CD4 recovery in HIV infection - Christine Fennema-Notestine; Ronald J. Ellis; Sarah L. Archibald; Terry L. Jernigan; Scott L. Letendre; Randy J. Notestine; Michael J. Taylor; Rebecca J. Theilmann; Michelle D. Julaton; David J. Croteau; Tanya Wolfson; Robert K. Heaton; et al. (Journal of NeuroVirology, 2013)

Arthropod food webs become increasingly lipid‐limited at higher trophic levels - Shawn M. Wilder; Michael Norris; Raymond W. Lee; David Raubenheimer; Stephen J. Simpson (Ecology Letters, 2013)
Understanding why food chains are relatively short in length has been an area of research and debate for decades. We tested if progressive changes in the nutritional content of arthropods with trophic position limit the availability of a key nutrient, lipid, for carnivores. Arthropods at higher trophic levels had progressively less lipid and more protein in their bodies compared with arthropods at lower trophic levels. The nutrients present in arthropod bodies were directly related to the nutrients that predators extracted when feeding on those arthropods. As a consequence, nutrient assimilation shifted from lipid‐biased to protein‐biased as arthropods ascended trophic levels from herbivores to secondary carnivores. Successive changes in the nutritional consequences of predation may ultimately set an upper limit on the number of trophic levels in arthropod communities. Further work is needed to examine the influence of lipid and other nutrients on food web traits in a range of ecosystems.

Consistent proportional macronutrient intake selected by adult domestic cats (Felis catus) despite variations in macronutrient and moisture content of foods offered - Adrian K. Hewson-Hughes; Victoria L. Hewson-Hughes; Alison Colyer; Andrew T. Miller; Simon R. Hall; David Raubenheimer; Stephen J. Simpson (Journal of Comparative Physiology B, 2013)

Apolipoprotein E4 genotype does not increase risk of HIV-associated neurocognitive disorders - E. E. Morgan; S. P. Woods; S. L. Letendre; D. R. Franklin; C. Bloss; A. Goate; R. K. Heaton; A. C. Collier; C. M. Marra; B. B. Gelman; J. C. McArthur; S. Morgello; et al. (Journal of NeuroVirology, 2013)

Polymerisation of a T Cell Epitope with an Immunostimulatory C3d Peptide Sequence Enhances Antigen Specific T Cell Responses - Neil M. O’Brien-Simpson; Troy J. Attard; Baihui Zheng; Katrina A. Walsh; Eric C. Reynolds (International Journal of Peptide Research and Therapeutics, 2013)

Taxonomic uncertainty and decision making for biosecurity: spatial models for myrtle/guava rust - J. Elith; J. Simpson; M. Hirsch; M. A. Burgman (Australasian Plant Pathology, 2013)

Mitochondrial DNA variation and HIV-associated sensory neuropathy in CHARTER - Emily R. Holzinger; Todd Hulgan; Ronald J. Ellis; David C. Samuels; Marylyn D. Ritchie; David W. Haas; Asha R. Kallianpur; Cinnamon S. Bloss; David B. Clifford; Ann C. Collier; Benjamin B. Gelman; Christina M. Marra; et al. (Journal of NeuroVirology, 2012)

The mammalian gene function resource: the international knockout mouse consortium - Allan Bradley; Konstantinos Anastassiadis; Abdelkader Ayadi; James F. Battey; Cindy Bell; Marie-Christine Birling; Joanna Bottomley; Steve D. Brown; Antje Bürger; Carol J. Bult; Wendy Bushell; Francis S. Collins; et al. (Mammalian Genome, 2012)

Earthworm metabolomic responses after exposure to aged PCB contaminated soils - Melissa Whitfield Åslund; Myrna J. Simpson; André J. Simpson; Barbara A. Zeeb; Allison Rutter (Ecotoxicology, 2012)

Cannibalism can drive the evolution of behavioural phase polyphenism in locusts - Vishwesha Guttal; Pawel Romanczuk; Stephen J. Simpson; Gregory A. Sword; Iain D. Couzin (Ecology Letters, 2012)
During outbreaks, locust swarms can contain millions of insects travelling thousands of kilometers while devastating vegetation and crops. Such large‐scale spatial organization is preceded locally by a dramatic density‐dependent phenotypic transition in multiple traits. Behaviourally, low‐density ‘solitarious’ individuals avoid contact with one another; above a critical local density, they undergo a rapid behavioural transition to the ‘gregarious phase’ whereby they exhibit mutual attraction. Although proximate causes of this phase polyphenism have been widely studied, the ultimate driving factors remain unclear. Using an individual‐based evolutionary model, we reveal that cannibalism, a striking feature of locust ecology, could lead to the evolution of density‐dependent behavioural phase‐change in juvenile locusts. We show that this behavioural strategy minimizes risk associated with cannibalistic interactions and may account for the empirically observed persistence of locust groups during outbreaks. Our results provide a parsimonious explanation for the evolution of behavioural plasticity in locusts.

Field application of a DNA-based assay to the measurement of roots of perennial grasses - Rebecca E. Haling; Richard J. Simpson; Richard A. Culvenor; Hans Lambers; Alan E. Richardson (Plant and Soil, 2012)

Large scale international replication and meta-analysis study confirms association of the 15q14 locus with myopia. The CREAM consortium - Virginie J. M. Verhoeven; Pirro G. Hysi; Seang-Mei Saw; Veronique Vitart; Alireza Mirshahi; Jeremy A. Guggenheim; Mary Frances Cotch; Kenji Yamashiro; Paul N. Baird; David A. Mackey; Robert Wojciechowski; M. Kamran Ikram; et al. (Human Genetics, 2012)

The impact of 6-month training preparation for an Ironman triathlon on the proportions of naïve, memory and senescent T cells in resting blood - Cormac Cosgrove; Stuart D. R. Galloway; Craig Neal; Angus M. Hunter; Brian K. McFarlin; Guilllaume Spielmann; Richard J. Simpson (European Journal of Applied Physiology, 2012)

Coelomic fluid: a complimentary biological medium to assess sub-lethal endosulfan exposure using 1H NMR-based earthworm metabolomics - Jimmy Yuk; Myrna J. Simpson; André J. Simpson (Ecotoxicology, 2012)

The Chemical Ecology of Soil Organic Matter Molecular Constituents - Myrna J. Simpson; André J. Simpson (Journal of Chemical Ecology, 2012)

Assessment of airborne Asteraceae pollen in Brisbane, Australia - Brett J. Green; Rod W. Simpson; Mary E. Dettmann (Aerobiologia, 2012)

A microsatellite linkage map for the cultivated strawberry (Fragaria × ananassa) suggests extensive regions of homozygosity in the genome that may have resulted from breeding and selection - D. J. Sargent; T. Passey; N. Šurbanovski; E. Lopez Girona; P. Kuchta; J. Davik; R. Harrison; A. Passey; A. B. Whitehouse; D. W. Simpson (Theoretical and Applied Genetics, 2012)

Genetic features of cerebrospinal fluid-derived subtype B HIV-1 tat - Jun Yong Choi; George K. Hightower; Joseph K. Wong; Robert Heaton; Steven Woods; Igor Grant; Thomas D. Marcotte; Ronald J. Ellis; Scott L. Letendre; Ann C. Collier; Christina M. Marra; David B. Clifford; et al. (Journal of NeuroVirology, 2012)

Region‐wide changes in marine ecosystem dynamics: state‐space models to distinguish trends from step changes - Matthew Spencer; Nova Mieszkowska; Leonie A. Robinson; Stephen D. Simpson; Michael T. Burrows; Silvana N. R. Birchenough; Eva Capasso; Polly Cleall‐Harding; Julia Crummy; Callan Duck; Damien Eloire; Matthew Frost; et al. (Global Change Biology, 2012)
Regime shifts are sudden changes in ecosystem structure that can be detected across several ecosystem components. The concept that regime shifts are common in marine ecosystems has gained popularity in recent years. Many studies have searched for the step‐like changes in ecosystem state expected under a simple interpretation of this idea. However, other kinds of change, such as pervasive trends, have often been ignored. We assembled over 300 ecological time series from seven UK marine regions, covering two to three decades. We developed state‐space models for the first principal component of the time series in each region, a common measure of ecosystem state. Our models allowed both trends and step changes, possibly in combination. We found trends in three of seven regions and step changes in two of seven regions. Gradual and sudden changes are therefore important trajectories to consider in marine ecosystems.

Consequences of frugivore‐mediated seed dispersal for the spatial and genetic structures of a neotropical palm - J. CHOO; T. E. JUENGER; B. B. SIMPSON (Molecular Ecology, 2012)
The idiosyncratic behaviours of seed dispersers are important contributors to plant spatial associations and genetic structures. In this study, we used a combination of field, molecular and spatial studies to examine the connections between seed dispersal and the spatial and genetic structures of a dominant neotropical palm Attalea phalerata. Field observation and genetic parentage analysis both indicated that the majority of A. phalerata seeds were dispersed locally over short distances ( 10 m) from maternal palms. Seedlings were also spatially aggregated with juveniles. These patterns are probably associated with the dispersal of seeds by rodents and the survival of recruits at specific microsites or neighbourhoods over successive fruiting periods. Our cross‐cohort analyses found palms in older cohorts and cohort pairs were associated with a lower proportion of offspring and sibling neighbours and exhibited weaker spatial and genetic structures. Such patterns are consistent with increased distance‐ and density‐dependent mortality over time among palms dispersed near maternal palms or siblings. The integrative approaches used for this study allowed us to infer the importance of seed dispersal activities in maintaining the aggregated distribution and significant genetic structures among A. phalerata palms. We further conclude that distance‐ and density‐dependent mortality is a key postdispersal process regulating this palm population.

Associations of whole-blood fatty acids and dietary intakes with prostate cancer in Jamaica - Maria D. Jackson; Susan P. Walker; Candace M. Simpson-Smith; Carole M. Lindsay; Garret Smith; Norma McFarlane-Anderson; Franklyn I. Bennett; Kathleen C. M. Coard; William D. Aiken; Trevor Tulloch; Tomlin J. Paul; Robert L. Wan (Cancer Causes & Control, 2012)

Plant and microbial strategies to improve the phosphorus efficiency of agriculture - Alan E. Richardson; Jonathan P. Lynch; Peter R. Ryan; Emmanuel Delhaize; F. Andrew Smith; Sally E. Smith; Paul R. Harvey; Megan H. Ryan; Erik J. Veneklaas; Hans Lambers; Astrid Oberson; Richard A. Culvenor; et al. (Plant and Soil, 2011)

Strategies and agronomic interventions to improve the phosphorus-use efficiency of farming systems - Richard J. Simpson; Astrid Oberson; Richard A. Culvenor; Megan H. Ryan; Erik J. Veneklaas; Hans Lambers; Jonathan P. Lynch; Peter R. Ryan; Emmanuel Delhaize; F. Andrew Smith; Sally E. Smith; Paul R. Harvey; et al. (Plant and Soil, 2011)

Brain Iron Dysregulation and the Risk of Ageing White Matter Lesions - Ola H. Gebril; J. E. Simpson; Janine Kirby; Carol Brayne; Paul G. Ince (NeuroMolecular Medicine, 2011)

Direct measurement of roots in soil for single and mixed species using a quantitative DNA-based method - Rebecca E. Haling; Richard J. Simpson; Alan C. McKay; Diana Hartley; Hans Lambers; Kathy Ophel-Keller; Sue Wiebkin; Herdina; Ian T. Riley; Alan E. Richardson (Plant and Soil, 2011)

An Assessment of Three Harpacticoid Copepod Species for Use in Ecotoxicological Testing - Daniel J. Ward; Victor Perez-Landa; David A. Spadaro; Stuart L. Simpson; Dianne F. Jolley (Archives of Environmental Contamination and Toxicology, 2011)

Cannibalism in the lifeboat — collective movement in Australian plague locusts - Matthew J. Hansen; Camille Buhl; Sepideh Bazazi; Stephen J. Simpson; Gregory A. Sword (Behavioral Ecology and Sociobiology, 2011)

Internal seiche modes and bottom boundary‐layer dissipation in a temperate lake from acoustic measurements - J. H. Simpson; P. J. Wiles; B. J. Lincoln (Limnology and Oceanography, 2011)
Measurements with Acoustic Doppler Current Profilers (ADCPs) and a thermistor string were used to investigate the seasonal variation of internal seiches in a 5‐km‐long temperate lake and the dissipation induced by the seiches in the bottom boundary layer. Velocity data, from a bottom‐mounted 1.2‐MHz ADCP were analyzed by cross‐spectral analysis to determine the seiche modes. The first vertical mode was generally dominant but the second mode made a significant contribution at times and was present throughout the summer season. The modal periods, which were consistent with normal mode analysis, exhibited a marked seasonal change that correlated closely with the evolution of stratification. Measurements in the bottom boundary layer, by another ADCP, in pulse‐pulse coherent‐mode sampling at 4 Hz, allowed determination of the rate of turbulent kinetic energy dissipation via the Structure Function Method. Episodes of energy dissipation ~ 10 ‐7 W kg ‐1 occurred during peak flow (~ 0.05 m s ‐1 ) in the seiche motion (period ~ 10 h) and coincided with times of significant Reynolds stress. Between these episodes, dissipation fell below the noise level (~ 5 × 10 ‐9 W kg ‐1 ). The ratio of internal wave energy to the boundary‐layer dissipation rate implies a decay time of ~ 75 h, which is similar to that for energy decay in strong seiches, indicating that boundary‐layer dissipation makes a substantial contribution to energy loss from seiche motions. A major mixing event in August caused by near‐resonant wind forcing brought metalimnion water to the surface and induced substantial mixing.

Differential expression of Phaseolus vulgaris genes induced during the interaction with Rhizoctonia solani - M. L. Guerrero-González; M. Rodríguez-Kessler; R. Rodríguez-Guerra; M. González-Chavira; J. Simpson; F. Sanchez; J. F. Jiménez-Bremont (Plant Cell Reports, 2011)

1H NMR metabolomics of earthworm responses to polychlorinated biphenyl (PCB) exposure in soil - Melissa L. Whitfield Åslund; André J. Simpson; Myrna J. Simpson (Ecotoxicology, 2011)

Juvenile coral reef fish use sound to locate habitats - C. A. Radford; J. A. Stanley; S. D. Simpson; A. G. Jeffs (Coral Reefs, 2011)

Clinical factors related to brain structure in HIV: the CHARTER study - Terry L. Jernigan; Sarah L. Archibald; Christine Fennema-Notestine; Michael J. Taylor; Rebecca J. Theilmann; Michelle D. Julaton; Randy J. Notestine; Tanya Wolfson; Scott L. Letendre; Ronald J. Ellis; Robert K. Heaton; Anthony C. Gamst; et al. (Journal of NeuroVirology, 2011)

Federated or cached searches: Providing expected performance from multiple invasive species databases - Jim Graham; Catherine S. Jarnevich; Annie Simpson; Gregory J. Newman; Thomas J. Stohlgren (Frontiers of Earth Science, 2011)

Temporal change in UK marine communities: trends or regime shifts? - M. Spencer; S. N. R. Birchenough; N. Mieszkowska; L. A. Robinson; S. D. Simpson; M. T. Burrows; E. Capasso; P. Cleall‐Harding; J. Crummy; C. Duck; D. Eloire; M. Frost; et al. (Marine Ecology, 2011)
A regime shift is a large, sudden, and long‐lasting change in the dynamics of an ecosystem, affecting multiple trophic levels. There are a growing number of papers that report regime shifts in marine ecosystems. However, the evidence for regime shifts is equivocal, because the methods used to detect them are not yet well developed. We have collated over 300 biological time series from seven marine regions around the UK, covering the ecosystem from phytoplankton to marine mammals. Each time series consists of annual measures of abundance for a single group of organisms over several decades. We summarised the data for each region using the first principal component, weighting either each time series or each biological component ( e.g. plankton, fish, benthos) equally. We then searched for regime shifts using Rodionov’s regime shift detection (RSD) method, which found regime shifts in the first principal component for all seven marine regions. However, there are consistent temporal trends in the data for six of the seven regions. Such trends violate the assumptions of RSD. Thus, the regime shifts detected by RSD in six of the seven regions are likely to be artefacts caused by temporal trends. We are therefore developing more appropriate time series models for both single populations and whole communities that will explicitly model temporal trends and should increase our ability to detect true regime shift events.

Prey nutrient composition has different effects on Pardosa wolf spiders with dissimilar life histories - Kim Jensen; David Mayntz; Søren Toft; David Raubenheimer; Stephen J. Simpson (Oecologia, 2011)

HIV-associated neurocognitive disorders before and during the era of combination antiretroviral therapy: differences in rates, nature, and predictors - Robert K. Heaton; Donald R. Franklin; Ronald J. Ellis; J. Allen McCutchan; Scott L. Letendre; Shannon LeBlanc; Stephanie H. Corkran; Nichole A. Duarte; David B. Clifford; Steven P. Woods; Ann C. Collier; Christina M. Marra; et al. (Journal of NeuroVirology, 2011)

Vegetative reproduction facilitates early expansion of Phyla canescens in a semi-arid floodplain - J. N. Price; M. J. Macdonald; C. L. Gross; R. D. B. Whalley; I. H. Simpson (Biological Invasions, 2011)

A simple model can unify a broad range of phenomena in retinotectal map development - Hugh D. Simpson; Geoffrey J. Goodhill (Biological Cybernetics, 2011)

Group structure in locust migratory bands - Camille Buhl; Gregory A. Sword; Fiona J. Clissold; Stephen J. Simpson (Behavioral Ecology and Sociobiology, 2011)

Isolation and fractionation of soil humin using alkaline urea and dimethylsulphoxide plus sulphuric acid - Guixue Song; Michael H. B. Hayes; Etelvino H. Novotny; Andre J. Simpson (The Science of Nature, 2011)

The impact of acute strenuous exercise on TLR2, TLR4 and HLA.DR expression on human blood monocytes induced by autologous serum - Stephen Booth; Geraint D. Florida-James; Brian K. McFarlin; Guillaume Spielmann; Daniel P. O’Connor; Richard J. Simpson (European Journal of Applied Physiology, 2010)

Root morphology, root-hair development and rhizosheath formation on perennial grass seedlings is influenced by soil acidity - Rebecca E. Haling; Alan E. Richardson; Richard A. Culvenor; Hans Lambers; Richard J. Simpson (Plant and Soil, 2010)

A wide diversity of previously undetected free‐living relatives of diplomonads isolated from marine/saline habitats - Martin Kolisko; Jeffrey D. Silberman; Ivan Cepicka; Naoji Yubuki; Kiyotaka Takishita; Akinori Yabuki; Brian S. Leander; Isao Inouye; Yuji Inagaki; Andrew J. Roger; Alastair G. B. Simpson (Environmental Microbiology, 2010)
Summary Over the last 15 years classical culturing and environmental PCR techniques have revealed a modest number of genuinely new major lineages of protists; however, some new groups have greatly influenced our understanding of eukaryote evolution. We used culturing techniques to examine the diversity of free‐living protists that are relatives of diplomonads and retortamonads, a group of evolutionary and parasitological importance. Until recently, a single organism, Carpediemonas membranifera , was the only representative of this region of the tree. We report 18 new isolates of Carpediemonas ‐like organisms (CLOs) from anoxic marine sediments. Only one is a previously cultured species. Eleven isolates are conspecific and were classified within a new genus, Kipferlia n. gen. The remaining isolates include representatives of three other lineages that likely represent additional undescribed genera (at least). Small‐subunit ribosomal RNA gene phylogenies show that CLOs form a cloud of six major clades basal to the diplomonad‐retortamonad grouping (i.e. each of the six CLO clades is potentially as phylogenetically distinct as diplomonads and retortamonads). CLOs will be valuable for tracing the evolution of diplomonad cellular features, for example, their extremely reduced mitochondrial organelles. It is striking that the majority of CLO diversity was undetected by previous light microscopy surveys and environmental PCR studies, even though they inhabit a commonly sampled environment. There is no reason to assume this is a unique situation – it is likely that undersampling at the level of major lineages is still widespread for protists.

Ice stream influence on West Greenland Ice Sheet dynamics during the Last Glacial Maximum - David H. Roberts; Antony J. Long; Bethan J. Davies; Matthew J. R. Simpson; Christoph Schnabel (Journal of Quaternary Science, 2010)
This paper investigates the processes governing bedrock bedform evolution in ice sheet and ice stream areas in central West Greenland, and explores the evidence for a cross‐shelf ice stream at the Last Glacial Maximum (LGM). To the east of Sisimiut the formation of streamlined bedforms with high elongation ratios and high bedform density has been controlled by geological structure and topography in slow‐flowing ice sheet areas. At the coast, the effects of regional flow convergence, caused by coastal fjord orientation, routed ice into the Sisimiut/Itilleq area where it formed an ice stream onset zone. This funnelled ice into an offshore trough (Holsteinsborg Dyb), resulting in a southwesterly regional ice flow direction and the formation of a topographically routed ice stream (Holsteinsborg Isbrae). To the south of this, striae and bedform evidence show that local valley glaciers initially flowed east to west across the coast, but were later redirected by the Itilleq Fjord ice which turned southwestward due to diffluent flow and deflection by Holsteinsborg Isbrae. Roches moutonnées in this area have low elongation ratios and high bedform density, but do not provide unequivocal support for ice streaming, as they are a product of both bedrock structure and changes in ice flow direction, rather than enhanced flow velocities. Cosmogenic surface exposure ages limit maximum ice sheet surface elevation to ca. 755–810 m above sea level in this region. Such ice thickness enabled Holsteinsborg Isbrae to reach the mid/outer continental shelf during the LGM, and to contribute to the formation of a trough mouth fan and the Outer Hellefisk moraines. Initial deglaciation across this region was driven by rising sea level and increasing air temperatures prior to the Bølling Interstadial at ca. 14.5 cal. ka BP. Between 12 and 10 cal. ka BP both increased air and ocean temperatures post the Younger Dryas, and peak sea‐level rise up to the marine limit, caused accelerated thinning and marginal retreat through calving, although dating evidence suggests ice streams remained along the inner shelf/coast boundary until at least ca. 10 cal. ka BP, their longevity maintained by increased ice thickness and ice discharge. Copyright © 2009 John Wiley & Sons, Ltd.

Altered microbial community structure and organic matter composition under elevated CO 2 and N fertilization in the duke forest - XIAOJUAN FENG; ANDRÉ J. SIMPSON; WILLIAM H. SCHLESINGER; MYRNA J. SIMPSON (Global Change Biology, 2010)
The dynamics and fate of terrestrial organic matter (OM) under elevated atmospheric CO 2 and nitrogen (N) fertilization are important aspects of long‐term carbon sequestration. Despite numerous studies, questions still remain as to whether the chemical composition of OM may alter with these environmental changes. In this study, we employed molecular‐level methods to investigate the composition and degradation of various OM components in the forest floor (O horizon) and mineral soil (0–15 cm) from the Duke forest free air CO 2 enrichment (FACE) experiment. We measured microbial responses to elevated CO 2 and N fertilization in the mineral soil using phospholipid fatty acid (PLFA) profiles. Increased fresh carbon inputs into the forest floor under elevated CO 2 were observed at the molecular‐level by two degradation parameters of plant‐derived steroids and cutin‐derived compounds. The ratios of fungal to bacterial PLFAs and Gram‐negative to Gram‐positive bacterial PLFAs decreased in the mineral soil with N fertilization, indicating an altered soil microbial community composition. Moreover, the acid to aldehyde ratios of lignin‐derived phenols increased with N fertilization, suggesting enhanced lignin degradation in the mineral soil. 1 H nuclear magnetic resonance (NMR) spectra of soil humic substances revealed an enrichment of leaf‐derived alkyl structures with both elevated CO 2 and N fertilization. We suggest that microbial decomposition of SOM constituents such as lignin and hydrolysable lipids was promoted under both elevated CO 2 and N fertilization, which led to the enrichment of plant‐derived recalcitrant structures (such as alkyl carbon) in the soil.

Buoyancy-stirring interactions in a subtropical embayment: a synthesis of measurements and model simulations in Maputo Bay, Mozambique - J D Lencart e Silva; J H Simpson; A M Hoguane; J-L Harcourt-Baldwin (African Journal of Marine Science, 2010)

Body size and risk of prostate cancer in Jamaican men - Maria D. Jackson; Susan P. Walker; Candace M. Simpson; Norma McFarlane-Anderson; Franklyn I. Bennett; Kathleen C. M. Coard; William D. Aiken; Trevor Tulloch; Tomlin J. Paul; Robert L. Wan (Cancer Causes & Control, 2010)

Effect of lime on root growth, morphology and the rhizosheath of cereal seedlings growing in an acid soil - Rebecca E. Haling; Richard J. Simpson; Emmanuel Delhaize; Peter J. Hocking; Alan E. Richardson (Plant and Soil, 2010)

Gross vs. net income: How plant toughness affects performance of an insect herbivore - Fiona J. Clissold; Gordon D. Sanson; Jenny Read; Stephen J. Simpson (Ecology, 2009)
Leaf biomechanical properties are thought to impose a significant obstacle to herbivores and as such influence patterns of herbivory more than leaf chemistry. However, evidence for the role of structural traits in influencing herbivore food choice and performance has come from correlative studies, whereas the underlying mechanisms have been given little attention. By manipulating the biomechanical properties of a host grass species through a combination of lyophilization and milling, and providing water separately, we were able to compare behavioral, physiological, and developmental responses of the Australian plague locust, Chortoicetes terminifera , to the biomechanical properties of plant food (exemplified by toughness) independently of the food's macronutrient content and the insect's demand for water. Increasing leaf toughness was associated with reduced rates of locust growth and prolonged development, with potential ecological consequences. Poorer performance on the tougher foods was primarily a consequence of a reduced rate of nutrient supply, which occurred as a result of (1) smaller meals being eaten more slowly, (2) slowed gut passage rates, which limited how quickly the next meal could be taken, and (3) reduced efficiency of assimilation of nutrients from food in the gut. In addition, there were deleterious changes in the ratio of protein to carbohydrate assimilated from the gut. Prolonged development time was associated with increased total nutrient demands throughout the extended developmental period. Because these demands could not be met by increased consumption, there was a decreased efficiency of conversion of assimilated nutrients to growth. By disentangling the effects of biomechanical properties from macronutrient and water content we have shown that leaf biomechanical traits can influence chewing herbivores independently of leaf chemical traits.

Residual circulation and stratification in the Liverpool Bay region of freshwater influence - Florence Verspecht; Tom P. Rippeth; John H. Simpson; Alejandro J. Souza; Hans Burchard; M. John Howarth (Ocean Dynamics, 2009)

Paleolimnological evidence of the effects on lakes of energy and mass transfer from climate and humans - Peter R. Leavitt; S. C. Fritz; N. J. Anderson; P. A. Baker; T. Blenckner; L. Bunting; J. Catalan; D. J. Conley; W. O. Hobbs; E. Jeppesen; A. Korhola; S. McGowan; et al. (Limnology and Oceanography, 2009)
The premise of this article is that climate effects on lakes can be quantified most effectively by the integration of process‐oriented limnological studies with paleolimnological research, particularly when both disciplines operate within a common conceptual framework. To this end, the energy (E)‐mass ( m ) flux framework (E m flux) is developed and applied to selected retrospective studies to demonstrate that climate variability regulates lake structure and function over diverse temporal and spatial scales through four main pathways: rapid direct transfer of E to the lake surface by irradiance, heat, and wind; slow indirect effects of E via changes in terrestrial development and subsequent m subsidies to lakes; direct influx of m as precipitation, particles, and solutes from the atmosphere; and indirect influx of water, suspended particles, and dissolved substances from the catchment. Sedimentary analyses are used to illustrate the unique effects of each pathway on lakes but suggest that interactions among mechanisms are complex and depend on the landscape position of lakes, catchment characteristics, the range of temporal variation of individual pathways, ontogenetic changes in lake basins, and the selective effects of humans on m transfers. In particular, preliminary synthesis suggests that m influx can overwhelm the direct effects of E transfer to lakes, especially when anthropogenic activities alter m subsidies from catchments.

Adiaspiromycosis Due to Emmonsia crescens is Widespread in Native British Mammals - Andrew M. Borman; Vic R. Simpson; Michael D. Palmer; Christopher J. Linton; Elizabeth M. Johnson (Mycopathologia, 2009)

Characterization of lipophilic drug binding to rat intestinal fatty acid binding protein - Tony Velkov; Maria L. R. Lim; James Horne; Jamie S. Simpson; Christopher J. H. Porter; Martin J. Scanlon (Molecular and Cellular Biochemistry, 2009)

Sequence stratigraphy of Jurassic strata in the lower Surat Basin succession, Queensland - K. L. Hoffmann; J. M. Totterdell; O. Dixon; G. A. Simpson; A. T. Brakel; A. T. Wells; J. L. Mckellar (Australian Journal of Earth Sciences, 2009)

Current and Future Applications of 3-D Global Earth-Ionosphere Models Based on the Full-Vector Maxwell’s Equations FDTD Method - Jamesina J. Simpson (Surveys in Geophysics, 2009)

Identification and Suppression of β-Elimination Byproducts Arising from the Use of Fmoc-Ser(PO3Bzl,H)-OH in Peptide Synthesis - Troy J. Attard; Neil M. O’Brien-Simpson; Eric C. Reynolds (International Journal of Peptide Research and Therapeutics, 2009)

Renal injury at first presentation as a predictor for poor outcome in severe paracetamol poisoning referred to a liver transplant unit - N. Pakravan; K. J. Simpson; W. S. Waring; C. M. Bates; D. N. Bateman (European Journal of Clinical Pharmacology, 2009)

Development of “universal” gene-specific markers from Malus spp. cDNA sequences, their mapping and use in synteny studies within Rosaceae - Daniel J. Sargent; Annalisa Marchese; David W. Simpson; Werner Howad; Felicidad Fernández-Fernández; Amparo Monfort; Pere Arús; Kate M. Evans; Kenneth R. Tobutt (Tree Genetics & Genomes, 2009)

Modern Solid Phase Peptide Synthesis and its Applications - Neil M. O’Brien-Simpson; Nicholas J. Ede; John D. Wade (International Journal of Peptide Research and Therapeutics, 2008)

Urban geochemistry: research strategies to assist risk assessment and remediation of brownfield sites in urban areas - I. Thornton; M. E. Farago; C. R. Thums; R. R. Parrish; R. A. R. McGill; N. Breward; N. J. Fortey; P. Simpson; S. D. Young; A. M. Tye; N. M. J. Crout; R. L. Hough; et al. (Environmental Geochemistry and Health, 2008)

Description of a simple synthetic diet for studying nutritional responses in ants - A. Dussutour; S. J. Simpson (Insectes Sociaux, 2008)

ERP correlates of anticipatory attention: spatial and non-spatial specificity and relation to subsequent selective attention - Corby L. Dale; Gregory V. Simpson; John J. Foxe; Tracy L. Luks; Michael S. Worden (Experimental Brain Research, 2008)

Alpha e-taxonomy: responses from the systematics community to the biodiversity crisis - S. J. Mayo; R. Allkin; W. Baker; V. Blagoderov; I. Brake; B. Clark; R. Govaerts; C. Godfray; A. Haigh; R. Hand; K. Harman; M. Jackson; et al. (Kew Bulletin, 2008)

Nocturnal relocation of adult and juvenile coral reef fishes in response to reef noise - S. D. Simpson; A. Jeffs; J. C. Montgomery; R. D. McCauley; M. G. Meekan (Coral Reefs, 2008)

Within-field variability of Fusarium head blight pathogens and their associated mycotoxins - X.-M. Xu; D. W. Parry; P. Nicholson; M. A. Thomsett; D. Simpson; S. G. Edwards; B. M. Cooke; F. M. Doohan; S. Monaghan; A. Moretti; G. Tocco; G. Mule; et al. (European Journal of Plant Pathology, 2007)

Synthesis of Phosphopeptides in the Fmoc Mode - Troy J. Attard; Neil O’Brien-Simpson; Eric C. Reynolds (International Journal of Peptide Research and Therapeutics, 2007)

The Role of Multiphosphorylated Peptides in Mineralized Tissue Regeneration - Keith J. Cross; N. Laila Huq; Neil M. O’Brien-Simpson; John W. Perich; Troy J. Attard; Eric C. Reynolds (International Journal of Peptide Research and Therapeutics, 2007)

Synthesis and Characterisation of a Multiphosphorylated Phosphophoryn Repeat Motif; H-[Asp-(Ser(P))2]3-Asp-OH - Neil M. O’Brien-Simpson; Troy J. Attard; Ashwini Loganathan; N. Laila Huq; Keith J. Cross; Peter F. Riley; Eric C. Reynolds (International Journal of Peptide Research and Therapeutics, 2007)

Phosphate sensing in Synechocystis sp. PCC 6803: SphU and the SphS–SphR two-component regulatory system - Waraporn Juntarajumnong; Tripty A. Hirani; Joanne M. Simpson; Aran Incharoensakdi; Julian J. Eaton-Rye (Archives of Microbiology, 2007)

Effects of Light on Microalgae Concentrations and Selenium Uptake in Bivalves Exposed to Selenium-Amended Sediments - D. Schlenk; G. Batley; C. King; J. Stauber; M. Adams; S. Simpson; W. Maher; J. T. Oris (Archives of Environmental Contamination and Toxicology, 2007)

Chlorophyll fluorescence, root growth potential, and stomatal conductance as estimates of field performance potential in conifer seedlings - Sylvia J. L’Hirondelle; David G. Simpson; Wolfgang D. Binder (New Forests, 2007)

Spring‐neap modulation of internal tide mixing and vertical nitrate fluxes at a shelf edge in summer - Jonathan Sharples; Jacqueline F. Tweddle; J. A. Mattias Green; Matthew R. Palmer; Young-Nam Kim; Anna E. Hickman; Patrick M. Holligan; C. Mark Moore; Tom P. Rippeth; John H. Simpson; Vladimir Krivtsov (Limnology and Oceanography, 2007)
Measurements of the intra‐tidal and spring‐neap variation in the vertical flux of nitrate into the base of the sub‐surface chlorophyll maximum (SCM) were made at the shelf edge of the Celtic Sea, a region with strong internal mixing driven by an internal tide. The neap tide daily mean nitrate flux was 1.3 (0.9‐1.8, 95% confidence interval) mmol m ‐2 d ‐1 . The spring tide flux was initially estimated as 3.5 (2.3‐5.2, 95% confidence interval) mmol m ‐2 d ‐1 . The higher spring tide nitrate flux was the result of turbulent dissipation occurring within the base of the SCM as compared to deeper dissipation during neap tides and was dominated by short events associated with the passage of internal solitons. Taking into account the likely under‐sampling of these short mixing events raised the spring tide nitrate flux estimate to about 9 mmol m ‐2 d ‐1 . The neap tide nitrate flux was sufficient to support substantial new production and a considerable fraction of the observed rates of carbon fixation. Spring tide fluxes were potentially in excess of the capacity of the phytoplankton community to uptake nitrate. This potential excess nitrate flux during spring tides may be utilized to support new production during the lower mixing associated with the transition toward neap tide. The shelf edge is shown to be a region with a significantly different phytoplankton community as compared to the adjacent Celtic Sea and northeast Atlantic Ocean, highlighting the role of gradients in physical processes leading to gradients in ecosystem structure.

Use of life history information in a population model for Sacramento green sturgeon - Raymond C. P. Beamesderfer; Michele L. Simpson; Gabriel J. Kopp (Environmental Biology of Fishes, 2007)

Bushiness and cytokinin profile in dormant and sprouting tubers of Zantedeschia - S. M. D’Arth; S. I. Simpson; J. F. Seelye; P. E. Jameson (Plant Cell, Tissue and Organ Culture (PCTOC), 2007)

Reply to comment on “Computing residence times for flow towards a pumping well: nomograph solution and validity of the small draw-down approximation”, Technical Note published in Hydrogeology Journal (2005) 13:889–894 - Matthew J. Simpson (Hydrogeology Journal, 2007)

The Role of Cohort Studies in Drug Development: Clinical Evidence of Antiviral Activity of Serotonin Reuptake Inhibitors and HMG-CoA Reductase Inhibitors in the Central Nervous System - Scott L. Letendre; Jennifer Marquie-Beck; Ronald J. Ellis; Steven Paul Woods; Brookie Best; David B. Clifford; Ann C. Collier; Benjamin B. Gelman; Christina Marra; Justin C. McArthur; J. Allen McCutchan; Susan Morgello; et al. (Journal of Neuroimmune Pharmacology, 2007)

The effects of marathon running on expression of the complement regulatory proteins CD55 (DAF) and CD59 (MACIF) on red blood cells - Richard J. Simpson; Geraint D. Florida-James; Greg P. Whyte; Natalie Middleton; Rob Shave; Keith George; Keith Guy (European Journal of Applied Physiology, 2006)

The development and mapping of functional markers in Fragaria and their transferability and potential for mapping in other genera - D. J. Sargent; A. Rys; S. Nier; D. W. Simpson; K. R. Tobutt (Theoretical and Applied Genetics, 2006)

Overwinter Storability of Conifer Planting Stock: Operational Testing of Fall Frost Hardiness - Sylvia J. L’Hirondelle; David G. Simpson; Wolfgang D. Binder (New Forests, 2006)

Iron and cadmium uptake by duodenum of hypotransferrinaemic mice - Kishor B. Raja; Shahnaz E. Jafri; Timothy J. Peters; Robert J. Simpson (BioMetals, 2006)

Morphology and response of roots of pasture species to phosphorus and nitrogen nutrition - J. O. Hill; R. J. Simpson; A. D. Moore; D. F. Chapman (Plant and Soil, 2006)

An enhanced microsatellite map of diploid Fragaria - D. J. Sargent; J. Clarke; D. W. Simpson; K. R. Tobutt; P. Arús; A. Monfort; S. Vilanova; B. Denoyes-Rothan; M. Rousseau; K. M. Folta; N. V. Bassil; N. H. Battey (Theoretical and Applied Genetics, 2006)

The effects of intensive, moderate and downhill treadmill running on human blood lymphocytes expressing the adhesion/activation molecules CD54 (ICAM-1), CD18 (β2 integrin) and CD53 - Richard J. Simpson; Geraint D. Florida-James; Greg P. Whyte; Keith Guy (European Journal of Applied Physiology, 2006)

Transplant tolerance: models, concepts and facts - Nicola J. Monk; Roseanna E. G. Hargreaves; Elizabeth Simpson; Julian P. Dyson; Stipo Jurcevic (Journal of Molecular Medicine, 2006)

Uredinales species pathogenic on species of Myrtaceae - J. A. Simpson; K. Thomas; C. A. Grgurinovic (Australasian Plant Pathology, 2006)

A note on the relationship between temperature and water vapor over oceans, including sea surface temperature effects - C. -L. Shie; W. -K. Tao; J. Simpson (Advances in Atmospheric Sciences, 2006)

Limitations to the Potential of Transgenic Trifolium subterraneum L. Plants that Exude Phytase when Grown in Soils with a Range of Organic P Content - Timothy S. George; Alan E. Richardson; J. Barry Smith; Paul A. Hadobas; Richard J. Simpson (Plant and Soil, 2005)

Geochemical Distribution and Bioavailability of Heavy Metals and Oxalate in Street Sediments from Rio de Janeiro, Brazil: A Preliminary Investigation - John J. McAlister; Bernard J. Smith; Jose Baptista Neto; Julia K. Simpson (Environmental Geochemistry and Health, 2005)

Municipal Forest Benefits and Costs in Five US Cities - Greg McPherson; James R. Simpson; Paula J. Peper; Scott E. Maco; Qingfu Xiao (Journal of Forestry, 2005)
Increasingly, city trees are viewed as a best management practice to control stormwater, an urban-heat–island mitigation measure for cleaner air, a CO2-reduction option to offset emissions, and an alternative to costly new electric power plants. Measuring benefits that accrue from the community forest is the first step to altering forest structure in ways that will enhance future benefits. This article describes the structure, function, and value of street and park tree populations in Fort Collins, Colorado; Cheyenne, Wyoming; Bismarck, North Dakota; Berkeley, California; and Glendale, Arizona. Although these cities spent $13–65 annually per tree, benefits ranged from $31 to $89 per tree. For every dollar invested in management, benefits returned annually ranged from $1.37 to $3.09. Strategies each city can take to increase net benefits are presented.

Encapsulation of protein nanoparticles into uniform-sized microspheres formed in a spinning oil film - W. Thomas Leach; Dale T. Simpson; Tibisay N. Val; Zhongshui Yu; Kwon T. Lim; Eun J. Park; Robert O. Williams; Keith P. Johnston (AAPS PharmSciTech, 2005)

Measurements of Trace Gases in the Inflow of South China Sea Background Air and Outflow of Regional Pollution at Tai O, Southern China - T. Wang; H. Guo; D. R. Blake; Y. H. Kwok; I. J. Simpson; Y. S. Li (Journal of Atmospheric Chemistry, 2005)

Computing residence times for flow towards a pumping well: nomograph solution and validity of the small draw-down approximation - Matthew J. Simpson (Hydrogeology Journal, 2005)

Biasing the brain’s attentional set: II. Effects of selective intersensory attentional deployments on subsequent sensory processing - John J. Foxe; Gregory V. Simpson (Experimental Brain Research, 2005)

Biasing the brain’s attentional set: I. Cue driven deployments of intersensory selective attention - John J. Foxe; Gregory V. Simpson; Seppo P. Ahlfors; Clifford D. Saron (Experimental Brain Research, 2005)

Predominance and association of pathogenic fungi causing Fusarium ear blightin wheat in four European countries - X. -M. Xu; D. W. Parry; P. Nicholson; M. A. Thomsett; D. Simpson; S. G. Edwards; B. M. Cooke; F. M. Doohan; J. M. Brennan; A. Moretti; G. Tocco; G. Mule; et al. (European Journal of Plant Pathology, 2005)

Biogeography of wild Arachis (Leguminosae):distribution and environmental characterisation - Morag E. Ferguson; Andrew Jarvis; H. Tom Stalker; David E. Williams; Luigi Guarino; Jose F.M. Valls; Roy N. Pittman; Charles E. Simpson; Paula J. Bramel (Biodiversity and Conservation, 2005)

Presence of carp, Cyprinus carpio , in the diet of the otter, Lutra lutra - J. R. BRITTON; J. S. SHEPHERD; S. TOMS; V. SIMPSON (Fisheries Management and Ecology, 2005)

Transcriptional profiling of the hyperthermophilic methanarchaeon Methanococcus jannaschii in response to lethal heat and non‐lethal cold shock - Boonchai B. Boonyaratanakornkit; Anjana J. Simpson; Timothy A. Whitehead; Claire M. Fraser; Najib M. A. El‐Sayed; Douglas S. Clark (Environmental Microbiology, 2005)
Summary Temperature shock of the hyperthermophilic methanarchaeon Methanococcus jannaschii from its optimal growth temperature of 85°C to 65°C and 95°C resulted in different transcriptional responses characteristic of both the direction of shock (heat or cold shock) and whether the shock was lethal. Specific outcomes of lethal heat shock to 95°C included upregulation of genes encoding chaperones, and downregulation of genes encoding subunits of the H + transporting ATP synthase. A gene encoding an α subunit of a putative prefoldin was also upregulated, which may comprise a novel element in the protein processing pathway in M. jannaschii . Very different responses were observed upon cold shock to 65°C. These included upregulation of a gene encoding an RNA helicase and other genes involved in transcription and translation, and upregulation of genes coding for proteases and transport proteins. Also upregulated was a gene that codes for an 18 kDa FKBP‐type PPIase, which may facilitate protein folding at low temperatures. Transcriptional profiling also revealed several hypothetical proteins that respond to temperature stress conditions.

Intron Analyses Reveal Multiple Calmodulin Copies in Littorina - R.J. Simpson; C.S. Wilding; J. Grahame (Journal of Molecular Evolution, 2005)

Induction of heat shock protein 70 in rat olfactory epithelium by toxic chemicals: in vitro and in vivo studies - S. A. Simpson; D. J. Alexander; C. J. Reed (Archives of Toxicology, 2005)

Clinical validation of the NeuroScreen - Ronald J Ellis; Scott R Evans; David B Clifford; Lauren R Moo; Justin C McArthur; Ann C Collier; Constance Benson; Ron Bosch; David Simpson; Constantin T Yiannoutsos; Yijun Yang; Kevin Robertson; et al. (Journal of NeuroVirology, 2005)

Nectin-1/HveC Mediates herpes simplex virus type-1 entry into primary human sensory neurons and fibroblasts - Scott A Simpson; Michael D Manchak; Elizabeth J Hager; Claude Krummenacher; J Charles Whitbeck; Myron J Levin; Curt R Freed; Christine L Wilcox; Gary H Cohen; Roselyn J Eisenberg; Lewis I. Pizer (Journal of NeuroVirology, 2005)

Comparison of reference genes for quantitative real-time polymerase chain reaction analysis of gene expression in sugarcane - Hayati M. Iskandar; Robert S. Simpson; Rosanne E. Casu; Graham D. Bonnett; Donald J. Maclean; John M. Manners (Plant Molecular Biology Reporter, 2004)

A genetic linkage map of microsatellite, gene-specific and morphological markers in diploid Fragaria - D. J. Sargent; T. M. Davis; K. R. Tobutt; M. J. Wilkinson; N. H. Battey; D. W. Simpson (Theoretical and Applied Genetics, 2004)

Heat shock protein 70 in the rat nasal cavity: localisation and response to hyperthermia - Sharon A. Simpson; David J. Alexander; Celia J. Reed (Archives of Toxicology, 2004)

First record of Lophodermium conigenum on Pinus in Australia - J. A. Simpson; C. A. Grgurinovic (Australasian Plant Pathology, 2004)

COX-1, COX-2 and the topical effect in NSAID-induced enteropathy - C. M. Hotz-Behofsits; M. J. M. Walley; R. Simpson; I. T. Bjarnason (Inflammopharmacology, 2003)

Mapping quantitative trait loci mediating sensitivity to etomidate - Chris Downing; Elaine H. Shen; Victoria J. Simpson; Thomas E. Johnson (Mammalian Genome, 2003)

Effect of exercise mode on blood glucose disposal during physiological hyperinsulinaemia in humans - K. Tsintzas; E. J. Simpson; N. Seevaratnam; S. Jones (European Journal of Applied Physiology, 2003)

Characteristics of an ozone deposition module II: Sensitivity analysis - D. Simpson; J.-P. Tuovinen; L. Emberson; M. R. Ashmore (Water, Air, & Soil Pollution, 2003)

Plant collecting spread and densities: their potential impact on biogeographical studies in Thailand - J. A. N. Parnell; D. A. Simpson; J. Moat; D. W. Kirkup; P. Chantaranothai; P. C. Boyce; P. Bygrave; S. Dransfield; M. H. P. Jebb; J. Macklin; C. Meade; D. J. Middleton; et al. (Journal of Biogeography, 2003)
Aims To produce representative aggregate maps of plant collection locations in Thailand and discuss their impact on biogeographical studies in Thailand and the surrounding region. Location Thailand. Methods A representative data set comprising 6593 plant specimen records for Thailand has been assembled. The data set contains ± all known collections for fifteen representative plant families and further records for another 104. All records are localized to Changwat (province), 6441 to at least quarter degree square. Results Analysis shows that the spread of collecting activity in Thailand is markedly uneven; 20% of collections come from a single Changwat (Chiang Mai) and 53% of Changwat have fifty or fewer collections. The distribution of collections by Changwat and by quarter degree square is erratic with most squares and Changwat having few collections, both in proportionate and absolute terms. Some of the most densely forested Changwats and squares appear undercollected. Distribution maps for common, easily recognized tree species in the genus Syzygium show distributional gaps. Conclusions Thailand is defined as an undercollected country. Even within the few well‐collected quarter degree squares the spread of collecting is still poor; almost all collections being localized to one of three mountain ranges or their foothills. There are many gaps in collecting activity which make impossible a straightforward interpretation of biogeographical pattern. It is argued that targeted collecting activity is needed, that assembly of this type of data set is therefore essential and that our data set and its interpretation is a model for all countries in the region.

Microphysics, radiation and surface processes in the Goddard Cumulus Ensemble (GCE) model - Wei-Kuo Tao; J. Simpson; D. Baker; S. Braun; M.-D. Chou; B. Ferrier; D. Johnson; A. Khain; S. Lang; B. Lynn; C.-L. Shie; D. Starr; et al. (Meteorology and Atmospheric Physics, 2003)

Movements and Habitat Use by the Endangered Australian Freshwater Mary River cod, Maccullochella peelii mariensis - Robert R. Simpson; Amos J. Mapleston (Environmental Biology of Fishes, 2002)

The relationship between perception and production in songbird vocal imitation: what learned calls can teach us - Vicario D.; Raksin J.; Naqvi N.; Thande N.; Simpson H. (Journal of Comparative Physiology A, 2002)

The regulation of virulence in phytopathogenic Erwinia species: quorum sensing, antibiotics and ecological considerations - Neil A. Whitehead; Joseph T. Byers; Paul Commander; Mark J. Corbett; Sarah J. Coulthurst; Lee Everson; Abigail K.P. Harris; Clare L. Pemberton; Natalie J.L. Simpson; Holly Slater; Debra S. Smith; Martin Welch; et al. (Antonie van Leeuwenhoek, 2002)

Expression of a Truncated Brca1 Protein Delays Lactational Mammary Development in Transgenic Mice - Melissa A. Brown; Hans Nicolai; Kathy Howe; Toyomasa Katagiri; El-Nasir Lalani; Kaylene J. Simpson; Nathan W. Manning; Andrew Deans; Phil Chen; Kum Kum Khanna; Mas Rina Wati; Beatrice L. Griffiths; et al. (Transgenic Research, 2002)

Maristentor dinoferus n. gen., n. sp., a giant heterotrich ciliate (Spirotrichea: Heterotrichida) with zooxanthellae, from coral reefs on Guam, Mariana Islands - Lobban C.; Schefter M.; Simpson A.; Pochon X.; Pawlowski J.; Foissner W. (Marine Biology, 2002)

Reproducibility of the blood lactate threshold, 4 mmol·l -1 marker, heart rate and ratings of perceived exertion during incremental treadmill exercise in humans - Grant S.; McMillan K.; Newell J.; Wood L.; Keatley S.; Simpson D.; Leslie K.; Fairlie-Clark S. (European Journal of Applied Physiology, 2002)

Molecular structures and associations of humic substances in the terrestrial environment - André J. Simpson; William L. Kingery; Michael H. Hayes; Manfred Spraul; Eberhard Humpfer; Peter Dvortsak; Rainer Kerssebaum; Markus Godejohann; Martin Hofmann (The Science of Nature, 2002)

Maristentor dinoferus n. gen., n. sp., a giant heterotrich ciliate (Spirotrichea: Heterotrichida) with zooxanthellae, from coral reefs on Guam, Mariana Islands - Lobban C.; Schefter M.; Simpson A.; Pochon X.; Pawlowski J.; Foissner W. (Marine Biology, 2002)

Identification and molecular characterisation of hordoindolines from barley grain - H.F. Darlington; J. Rouster; L. Hoffmann; N.G. Halford; P.R. Shewry; D.J. Simpson (Plant Molecular Biology, 2001)

The Importance of Nitrogen Oxides for the Exceedance of Critical Thresholds in the Nordic Countries - M. Johansson; R. Suutari; J. Bak; G. Lövblad; M. Posch; D. Simpson; J.-P. Tuovinen; K. Tørseth (Water, Air, & Soil Pollution, 2001)

Modelling and Mapping Ozone Deposition in Europe - L. D. Emberson; M.R. Ashmore; D. Simpson; J.-P. Tuovinen; H.M. Cambridge (Water, Air, & Soil Pollution, 2001)

Aircraft Measurements of Dimethyl Sulfide (DMS) Using a Whole Air Sampling Technique - I. J. Simpson; J. J. Colman; A. L. Swanson; A. R. Bandy; D. C. Thornton; D. R. Blake; F. S. Rowland (Journal of Atmospheric Chemistry, 2001)

Oral quinine pharmacokinetics and dietary salt intake - Paul Newton; Andrew Simpson; Sompon Wanwimolruk; Pius Maliakal; Leopoldo Villegas; Daniel Kuypers; Nicholas J. White (European Journal of Clinical Pharmacology, 2001)

Phytoplankton distribution and survival in the thermocline - Jonathan Sharples; Mark C. Moore; Tom P. Rippeth; Patrick M. Holligan; David J. Hydes; Neil R. Fisher; John H. Simpson (Limnology and Oceanography, 2001)
Observations of the vertical structure of density, concentrations of chlorophyll a and nitrate, and turbulent dissipation rates were made over a period of 25 h in a well‐stratified shelf region in the Western English Channel, between neap and spring tides. Maximum turbulent dissipation at the base of the thermocline occurred almost 5 h after maximum tidal currents. This turbulence aids phytoplankton growth by supplying bottom‐layer nutrients into the subsurface chlorophyll maximum but reduces phytoplankton concentrations in the thermocline by mixing cells from the base of the subsurface maximum into the bottom mixed layer. The turbulent dissipation observations were used to estimate an average nitrate flux into the thermocline of 2.0 (0.8‐3.2, 95% confidence interval) mmol m −2 d −1 , which is estimated to have been capable of supporting new phytoplankton growth at a rate of 160 (64–256) mg C m −2 d −1 . Turbulent entrainment of carbon from the base of the subsurface biomass maximum into the bottom mixed layer was observed to be 290 (120–480) mg C m −2 d −1 . This apparent excess export from the chlorophyll maximum is suggested to be a feature of the spring‐neap cycle, with export dominating as the tidal turbulence increases toward spring tides and erodes the base of the thermocline. The observed rate of carbon export into the bottom mixed layer could account for as much as 25% of the gross annual primary production in stratifying shelf seas. Such turbulent losses, combined with grazing losses and low light levels, suggest that phytoplankton need to be highly adapted to environmental conditions within the thermocline in order to survive.

Poster Session - J. van S. Graver; H. J. Banks; A. K. Sharp; A. Contessi; N. Baldassari; M. Maggioli; Sabine Prozell; Ch. Reichmuth; Maria Otília Carvalho; Ana Paula Pereira; A. Mexia; Sylvia Allen; et al. (Phytoparasitica, 2001)

Components of organic phosphorus in soil extracts that are hydrolysed by phytase and acid phosphatase - J. E. Hayes; A. E. Richardson; R. J. Simpson (Biology and Fertility of Soils, 2000)

Estimating normal and pathological dynamic responses in cerebral blood flow velocity to step changes in end-tidal pCO2 - D. M. Simpson; R. B. Panerai; D. H. Evans; J. Garnham; A. R. Naylor; P. R. F. Bell (Medical & Biological Engineering & Computing, 2000)

Phase relations, singularities and thermobarometry of metamorphic assemblages containing phengite, chlorite, biotite, K-feldspar, quartz and H2O - G. D. H. Simpson; A. B. Thompson; J. A. D. Connolly (Contributions to Mineralogy and Petrology, 2000)

Objective Response Detection in an Electroencephalogram During Somatosensory Stimulation - David M. Simpson; Carlos J. Tierra-Criollo; Renato T. Leite; Eduardo J. B. Zayen; Antonio F. C. Infantosi (Annals of Biomedical Engineering, 2000)

The growth and phosphorus utilisation of plants in sterile media when supplied with inositol hexaphosphate, glucose 1-phosphate or inorganic phosphate - Julie E. Hayes; Richard J. Simpson; Alan E. Richardson (Plant and Soil, 2000)

A comparative transcript map and candidates for mutant phenotypes in the Tyrp1 (brown) deletion complex homologous to human 9p21-23 - Eleanor H. Simpson; Ruth Suffolk; Julia A. Bell; Siobhán A. Jordan; Dabney K. Johnson; Pat R. Hunsicker; Jack S. Weber; Monica J. Justice; Ian J. Jackson (Mammalian Genome, 2000)

Somaclonal variation in cryopreserved embryogenic clones of white spruce [ Picea glauca (Moench) Voss.] - L. L. DeVerno; Y. S. Park; J. M. Bonga; J. D. Barrett; C. Simpson (Plant Cell Reports, 1999)

Centrin in the groove: immunolocalisation of centrin and microtubules in the putatively primitive protistChilomastix cuspidata (Retortamonadida) - N. D. Weerakoon; J. D. I. Harper; A. G. B. Simpson; D. J. Patterson (Protoplasma, 1999)

The ferric-reducing activity of duodenal brush-border membrane vesicles is associated with a b-type haem - David J. Pountney; Kishor B. Raja; Robert J. Simpson<; John M. Wrigglesworth (BioMetals, 1999)

Biochemical and biophysical analysis of the intracellular lipid binding proteins of adipocytes - Melanie A. Simpson; Vince J. LiCata; Natalie Ribarik Coe; David A. Bernlohr (Molecular and Cellular Biochemistry, 1999)

Abstracts of the 6th FECS Conference 1998 Lectures - F. Sherwood Rowland; Donald R. Blake; B. R. Larsen; Anne Lindskog; Peter J. Peterson; W. Peter Williams; T. J. Wallington; M. J. Pilling; N. Carslaw; D. J. Creasey; D. E. Heard; P. Jacobs; et al. (Environmental Science and Pollution Research, 1998)

Genetic variation vis-à-vis molecular polymorphism in groundnut, Arachis hypogaea L. - A.K. Singh; J. Smartt; C.E. Simpson; S.N. Raina (Genetic Resources and Crop Evolution, 1998)

The Validity of Similarity Theory in the Roughness Sublayer Above Forests - I. J. Simpson; G. W. Thurtell; H. H. Neumann; G. Den Hartog; G. C. Edwards (Boundary-Layer Meteorology, 1998)

Changes in the levels of seven proteins involved in polypeptide folding and transport during endosperm development of two barley genotypes differing in storage protein localisation - Søren Møgelsvang; David J. Simpson (Plant Molecular Biology, 1998)

On the role of ?hot towers? in tropical cyclone formation - J. Simpson; J. B. Halverson; B. S. Ferrier; W. A. Petersen; R. H. Simpson; R. Blakeslee; S. L. Durden (Meteorology and Atmospheric Physics, 1998)

Polarity of mutations in tumor-associated microsatellite instability - Rosane Sturzeneker; Luciana A. Haddad; Roberta A. U. Bevilacqua; Andrew J. G. Simpson; Sérgio D. J. Pena (Human Genetics, 1998)

Agrobacterium-mediated transformation of Amaranthus hypochondriacus: light- and tissue-specific expression of a pea chlorophyll a/b-binding protein promoter - A. E. Jofre-Garfias; N. Villegas-Sepúlveda; J. L. Cabrera-Ponce; R. M. Adame-Alvarez; L. Herrera-Estrella; J. Simpson (Plant Cell Reports, 1997)

Announcement - P. D. Markel; B. Bennett; M. A. Besson; L. Gordon; V. J. Simpson; T. E. Johnson (Mammalian Genome, 1997)

Erratum - P. D. Markel; B. Bennett; M. A. Besson; L. Gordon; V. J. Simpson; T. E. Johnson (Mammalian Genome, 1997)

Uptake of 26-Al and 67-Ga into brain and other tissues of normal and hypotransferrinaemic mice - Aleksandar Radunovic´; Fukiko Ueda; Kishor B. Raja; Robert J. Simpson; Jill Templar; Samantha J. King; John S. Lilley; J. Philip Day; Michael W.B. Bradbury (BioMetals, 1997)

Moxonidine and cognitive function: interactions with moclobemide and lorazepam - K. Wesnes; P. M. Simpson; B. Jansson; A. Grahnén; H.-J. Weimann; H. Küppers (European Journal of Clinical Pharmacology, 1997)

Northeastern Conifers: The New Brunswick Tree Improvement Program - J. Dale Simpson (Journal of Forestry, 1997)

Book Review - Helotiales of Australasia: Geoglossaceae, Orbilaceae, Sclerotiniaceae, Hyaloscyphaceae. By B.M. Spooner. Bibliotheca Mycologia No. 116, J. Cramer, Berlin 1987. 711pp. - J Simpson (Australasian Plant Pathology, 1989)

Restriction site polymorphism in genes encoding type 2 but not type 1 gonococcal IgA1 proteases - M. H. Mulks; D. A. Simpson; R. J. Shoberg (Antonie van Leeuwenhoek, 1987)

Short-term consequences of different breeding histories for captive rhesus macaque mothers and young - A. E. Simpson; M. J. A. Simpson (Behavioral Ecology and Sociobiology, 1985)

Hydrogen-stimulated CO2 fixation and coordinate induction of hydrogenase and ribulosebiphosphate carboxylase in a H2-uptake positive strain of Rhizobium japonicum - Frank B. Simpson; Robert J. Maier; Harold J. Evans (Archives of Microbiology, 1979)

Erlon L. Newdick 1888–1975 - Paul J. Eastman; Geddes W. Simpson (American Journal of Potato Research, 1975)

Report of editorial committee - Arthur Hawkins; Ora Smith; A. Frank Ross; R. E. Webb; G. W. Simpson; J. C. Campbell (American Journal of Potato Research, 1959)